Collaborative science narrows knowledge gaps in marine biological invasions to advance a national framework - Romeu S. Ribeiro; Cristina Espírito Santo; Susana Celestino; Marta Mamede; João J. Castro; Teresa Cruz; Teresa Silva; David Jacinto; Cátia Bartilotti; Jorge Lobo-Arteaga; Miriam Tuaty-Guerra; João Canning-Clode; et al. (Marine Pollution Bulletin, 2026)

Wild felids as sentinels of antimicrobial resistance: susceptible Escherichia coli isolates from a protected area in southeastern Brazil - Melrian Menezes Teixeira; Carolina Magri Ferraz; Hilton Entringer; Alessandra Figueiredo de Castro Nassar; Vanessa Castro; Marita Vedovelli Cardozo; Ana Carolina Srbek-Araujo; Gabriel Augusto Marques Rossi (Veterinary Research Communications, 2026)
Antimicrobial resistance (AMR) is a major global health concern, and its monitoring in wildlife is essential from a One Health perspective. Here, we obtained bacterial isolates and assessed the AMR profiles and extended-spectrum β-lactamase (ESBL) production of Escherichia coli isolated from fecal samples of wild felids in a protected Atlantic Forest area in southeastern Brazil. We collected 22 fecal samples and identified depositor species through trichological analysis (ocelot, Leopardus pardalis = 18; jaguar, Panthera onca = 1; puma, Puma concolor = 1; Leopardus sp. = 1; unidentified felid = 1). Bacterial isolation was performed using EMB agar and MacConkey agar supplemented with ceftriaxone or meropenem, and isolates were identified by MALDI-TOF MS. From these, 11 E. coli isolates (ocelot = 9; jaguar = 1; puma = 1) were selected to assess AMR using a standardized disk diffusion assay with 15 antimicrobials and to test for ESBL production. In addition to E. coli , the detected bacterial assemblage included Achromobacter micicolens , Acinetobacter baumannii , Acinetobacter nosocomialis , Acinetobacter vivianii , Enterococcus faecalis , Ochrobactrum intermedium and Stenotrophomonas maltophilia . All E. coli isolates were susceptible to all tested antimicrobials, and none showed evidence of ESBL production. These findings may suggest low selective pressure for AMR in the study area, reflecting limited circulation of antimicrobial-resistant bacteria. As free-ranging carnivores may act as sentinels of environmental change and integrate microbiota from prey, this study provides a baseline for monitoring AMR shifts across populations.

Flies from meat processing facilities are carriers of multidrug-resistant Escherichia coli and diverse Staphylococcaceae species - Matheus Zorzal Bernardes Rangel; Gustavo Guimarães Fernandes Viana; Ana Julia Camuzzi Ferrari Storck; Carolina Magri Ferraz; Sarah Bernardes Simões; Valéria Modolo Peterle; Natalia Pereira; Pamella Almeida Freire Casemiro; Alessandra Figueiredo de Castro Nassar; Vanessa Castro; Bruna Maria Salotti-Souza; Juliano Gonçalves Pereira; et al. (Brazilian Journal of Microbiology, 2026)
Flies are important vectors of antimicrobial resistance (AMR) in food production, but their role in meat processing environments remains poorly characterized. This study isolated Enterobacteriaceae and Staphylococcaceae (including Mammaliicoccus sciuri ) from flies collected in bovine and swine slaughterhouses and meat processing industries. Phenotypic AMR was assessed, and the presence of selected antimicrobial resistance and virulence genes ( mecA , sea , see , sec , stx1 , stx2 , and eae ) was verified. Out of 60 flies collected, a total of 34 isolates were identified using MALDI-TOF with 13 different bacterial species, including Escherichia coli , Citrobacter braakii , C. freundii , Klebsiella pneumoniae , Hafnia alvei , Enterobacter kobei , S. aureus , S. epidermidis , S. saprophyticus , S. simulans , S. warneri , S. xylosus , and M. sciuri . Among Staphylococcaceae isolates, 17.6% were resistant to oxacillin and 23.5% to gentamicin. Regarding the Enterobacteriaceae isolates, 41.2% were resistant to streptomycin. Ten isolates (two E. coli , one S . epidermidis , two S. saprophyticus , one S. simulans , one S . warneri and three M. sciuri ) were considered multidrug-resistant (MDR). Notably, none of the targeted genes ( mecA , sea , see , sec , stx1 , stx2 , eae ) were detected by PCR. These findings suggest that flies can disseminate important resistant opportunistic bacteria in meat processing environments, posing concerns due to the capacity of flies to transmit these bacteria across food, processing facilities, animals and humans. These results underscore the need for continuous AMR surveillance and effective vector control to reduce the risks posed by flies in meat processing environments.

Comparative genomics and molecular characterization of a multidrug-resistant Corynebacterium glucuronolyticum isolated for the first time from the human genitourinary tract in Latin America - Max Roberto Batista Araújo; Louisy Sanches dos Santos; Marcus Vinicius Canário Viana; Eduarda Guimarães Sousa; Fernanda Diniz Prates; Hugo Felix Perini; Marcos Vinicius da Silva; Jailan da Silva Sousa; Bertram Brenig; Bruno Silva Andrade; Ana Luiza Mattos-Guaraldi; Lincoln de Oliveira Sant’Anna; et al. (Brazilian Journal of Microbiology, 2026)

Macrophage modulation accounts for the anti-inflammatory effect of Hypnea cervicornis agglutinin in rat arthritis induced by zymosan - Francisco Glerison da Silva Nascimento; Pedro Henrique de Souza Ferreira Bringel; Diego Freitas de Araujo; Mário Rogério Lima Mota; Maria Gleiciane de Queiroz Martins; Mayara Torquato Lima da Silva; Clareane Avelino Simplício Nobre; Benildo Sousa Cavada; Kyria Santiago do Nascimento; Rondinelle Ribeiro Castro; Ana Maria Sampaio Assreuy (Glycoconjugate Journal, 2026)
Previous study demonstrated that Hypnea cervicornis lectin (HCA) reduces inflammation and nociception via interaction with the lectin carbohydrate-binding site, modulating gene expression of the interleukins IL-1β, TNF-α and of iNOS. This study evaluated the effect of HCA in the rat model of arthritis induced by zymosan in the tibiotarsal joint and the involvement of macrophage-derived mediators. In vitro, macrophages were stimulated with zymosan before being incubated with HCA and the supernatant was injected into the joint. In vivo, HCA was administered by intravenous route after intra-articular injection of zymosan, fMLP, or macrophages supernatant. Hypernociception, edema and leukocyte influx were evaluated in the joints, and inflammatory mediators in the macrophage supernatant or periarticular tissue. In vitro, HCA (100 µg/ml) reduced NO 2 − and IL-1β in the supernatant of macrophages. In vivo, HCA (3 mg/kg) reduced articular hypernociception, edema and leukocyte influx elicited by zymosan, fMLP or by the supernatant of zymosan activated macrophages, as well as the zymosan-induced rolling and adhesion, and gene expression of iNOS and IL-1. HCA attenuated edema and leukocyte influx in the periarticular tissue, revealing preserved chondrocytes in the cartilage. In conclusion, HCA exerts anti-inflammatory effect in the arthritis induced by zymosan in rat tibio-tarsal joints, involving NO and IL-1 released by resident macrophages.

Multitargeted metabarcoding and morphological identification reveal practice-specific soil biodiversity outcomes in Mediterranean cropping systems - Lur Epelde; Ninon Delcourt; Jérôme Cortet; Anders Lanzén; Carlos Garbisu; José Luis Lavín; Luigi P. D'Acqui; Sara Di Lonardo; Martina Grattacaso; Eliana L. Tassi; Fatima-Zahraa El Balghiti; Leila Benidire; et al. (Soil Biology and Biochemistry, 2026)

Optimization of magnetic nanostructured materials for cyanotoxin removal by oxidation and regeneration methods - Alejandro Cao; Natalia Vilariño; Lisandra de Castro Alves; Yolanda Piñeiro; José Rivas; María J. Sainz; Cristina Carrera; Almudena Graña; Ana M. Botana; Luis Rodríguez-Santos; M. Carmen Louzao; Luis M. Botana (Journal of Environmental Sciences, 2026)

Recreational ketamine exposure disrupts redox and inflammatory homeostasis in salivary glands and plasma leading to salivary dysfunction - Emanuelly Camilly Soares Lima-da-Silva; Cristian Kallahan Silva Chagas; Wallacy Watson Pereira Melo; Ana Paula de Andrade Silva; Sabrina Carvalho Cartágenes; Nair Correia de Freitas Castro; Fernando Bezerra; Rommel Rodrigues Burbano; Antonio Hernandes Chaves-Neto; Renata Duarte Souza-Rodrigues; Cristiane do Socorro Ferraz Maia; Rafael Rodrigues Lima (Food and Chemical Toxicology, 2026)

Otolith geochemistry reveals estuarine–coastal connectivity and nursery contribution of Mugil curema in tropical impacted estuaries - Diele Emele Pontes Carvalho de Lima; André Luiz Machado Pessanha; Jorge Pisonero Castro; Ana Méndez-Vicente; Alberto Teodorico Correia (Estuarine, Coastal and Shelf Science, 2026)

Amazonian rhizobacteria increase water deficit tolerance in açaí palm seedlings - Maria Joselina Gomes Ribeiro; Ana Paula Gurjão de Assis; Verônica Daniely Pereira Paes da Silva; Laila Brabo Pacheco; Cecílio Frois Caldeira Júnior; Gisele Barata da Silva; Gledson Luiz Salgado de Castro (South African Journal of Botany, 2026)

Prevalence and spatial distribution of Brucella spp. seropositive equids from the state of Mato Grosso, Brazil - Nilton Ferreira Borges; Marcelo Luís Barros; Isana Souza Silva; Janice Elena Ioris Barddal; Ana Flávia Borges de Freitas; Melissa Harumi Sumiyoshi; Livia Saab Muraro; Sofia de Souza Pereira Gomes; Anderson Castro Soares de Oliveira; Márcio Garcia Ribeiro; Daniel Moura de Aguiar (Journal of Equine Veterinary Science, 2026)

Life cycle and techno-economic assessment of acid washing as a pretreatment in the production of microalgal hydrochar through hydrothermal carbonization - Bruno Silva Henriques; Christhians Leonel Mora Rodríguez; Mariana Marinho Viana França; Diêgo Rafael Félix Olegário; Ana Paula Maciel de Castro; Maurino Magno de Jesus Junior; Bianca Barros Marangon; Nayara Vilela Avelar; Fábio de Ávila Rodrigues; Rejane Nascentes; Maria Lúcia Calijuri (Journal of Environmental Chemical Engineering, 2026)

Natural deep eutectic solvents (NADES): dual functionality in the extraction and stabilization of polyphenols, terpenoids and nitrogen compounds - Gerardo Valles-Salas; Juliana Morales-Castro; Claudia I. Gamboa-Gómez; Blanca E. Morales-Contreras; Walfred Rosas-Flores; L. Araceli Ochoa-Martínez; Juan C. Contreras-Esquivel; Ana M. Ávila-Galván; Orlando A. Manzanares-Meza (Food Chemistry, 2026)

The ocean as a laboratory for animal intelligence - Maria Castro Mariano; Francisco Louro; Patrícia Pinto; João Grave; Victor Callais; Nicolas Collazo; Beatriz Pereira; Daniel Gouveia; Lisandra Tavares; Luís Almeida; Raúl Oliveira; Ana S. Carmo; et al. (acta ethologica, 2026)

Movement of European freshwater mussels under simulated dewatering conditions - Ana Matos; Manuel Lopes-Lima; Paulo Castro; Luigi Fraccarollo; Janusz Golski; Sandra Kaźmierczak; Vanessa Modesto; Martin Österling; Sebastiano Piccolroaz; Ashkan Pilbala; Vincent Prié; Nicoletta Riccardi; et al. (Hydrobiologia, 2026)

Decoupling bioaccumulation and trophic transfer: nanoatrazine accumulates in microalgae but shows limited transfer to zooplankton - Ana Paula Andrade Braga; José Henrique Vallim; Mara Denise Luck Mendes; Vítor Oliveira Levanteza; Márcia Regina Assalin; Marley Mendonça Tavares; Leonardo Fernandes Fraceto; Anderson do Espírito Santo Pereira; Vera Lucia Scherholz Salgado de Castro (Environmental Monitoring and Assessment, 2026)
Nanoformulations of pesticides have been proposed as a strategy to improve agricultural efficiency while potentially reducing environmental contamination. However, little is known about the bioaccumulation and trophic transfer of nanopesticides in aquatic food webs. In this study, the bioaccumulation of poly(ε-caprolactone)-encapsulated nanoatrazine (nATZ-PCL) was evaluated in the microalga Raphidocelis subcapitata , as well as its potential transfer to the zooplanktonic consumer Daphnia magna through dietary and direct exposure pathways. Physicochemical characterization demonstrated that the nATZ-PCL presented relative stability under most tested conditions, although aggregation behavior was observed in the algal culture medium over time. Atrazine accumulation was detected in R. subcapitata , particularly under EC 25 exposure conditions in the absence of natural organic matter (NOM). In contrast, atrazine was not detected above the analytical detection limit in D. magna following either dietary exposure with pre-exposed algae or direct exposure in reconstituted medium. The results suggest that nanoparticle aggregation, reduced bioavailability, limited assimilation efficiency, and depuration processes may have restricted the trophic transfer of nATZ-PCL to the primary consumer. These findings demonstrate that bioaccumulation in primary producers does not necessarily imply efficient transfer across aquatic trophic levels and contribute to a better understanding of the environmental behavior of nATZ-PCL in aquatic systems.

Cytogenotoxic effects of Artocarpus heterophyllus Lam. leaf extracts: implications for the safe use of medicinal plants - Ellen Borges da Rocha; Renata Gomes Gonçalves; Brenda Christie Castro de Oliveira; Alexia Barreto da Silveira; Ana Beatriz Franco de Jesus; Luiz Carnevale Eberhardt; Débora Moura Peixoto; Brena Guerra Paixão; Matheus de Lima Rodrigues; Alexandre Felipe de Araújo Desidério; Dayana Palmeira da Silva Rosa; Helena Regina Pinto Lima; et al. (South African Journal of Botany, 2026)

Physiological and agronomic responses of cucurbit crops to drought and combined heat–drought stress in field conditions - Alejandro Flores-León; Mireya Gil-Molina; Gabriela Campos; Carlos Romero; Ana Pérez-de-Castro; Belén Picó; Antonio José Monforte (Plant Science, 2026)

Functional redundancy and structural flexibility as contrasting plankton strategies under macrotidal pulses - Quedyane Silva da Cruz; Marco Valério Jansen Cutrim; Pedro Augusto Mendes de Castro Melo; Ana Karoline Duarte dos Santos Sá; Yago Bruno Silveira Nunes; Bruna Oliveira Ferreira; Francisco José da Silva Dias; Vinicius Henrique Maciel dos Santos; Taiza Pimentel Santos (Marine Environmental Research, 2026)

A commitment to personal improvement. Motivations of solo women hikers - Ana Castro-Sancho; Antonio Vidal-Matzanke; Pablo Vidal-González (Journal of Outdoor Recreation and Tourism, 2026)

How temperature modulates the combined toxicity of aged polystyrene microplastics and copper in early zebrafish development - Ana Paula Andrade Braga; José Henrique Vallim; Vitor Levanteza; Gabriela Helena da Silva; Marcela Inés Cáceres Wenzel; Diego S.T. Martinez; Vera Lúcia de Castro (Environmental Toxicology and Pharmacology, 2026)

Effect of 2NS translocation on wheat head blast resistance and grain production - Ana Luiza Maria Serpa Andrade; Adriano Francis Dorigan; Fernanda Aparecida Castro Pereira; João Leodato Nunes Maciel; Joyce Dória; José Maria Villela Pádua (European Journal of Plant Pathology, 2026)
Wheat head blast (WHB), caused by the fungus Pyricularia oryzae pathotype Triticum (PoT), is a major disease affecting wheat in the Brazilian Cerrado region. This disease can significantly reduce grain yield because the environmental conditions in the tropical Cerrado biome favor PoT infection of wheat heads. This study aimed to evaluate the effect of the 2NS/AS translocation on WHB resistance and its impact on key yield components across multiple environments in the southern region of Minas Gerais state. As a result, eight wheat cultivars were evaluated under field conditions over five consecutive growing seasons (2021–2025). Disease incidence, grain yield (kg.ha −1 ), and thousand-kernel weight (TKW; g) were assessed. Significant differences ( p ≤ 0.05) were observed for all traits, with selective accuracies ranging from 0.79 to 0.99. Cultivars ORS1403 and TBIODuque exhibited the lowest disease incidence. TBIODuque, along with BRS404, ORSFeroz, and TBIOAton were the highest-yielding genotypes, while BRS404 and ORSFeroz showed the highest TKW. Furthermore, GGE biplot analysis confirmed that the patterns aligned with the average trends, with the TBIODuque cultivar standing out for its higher resistance and yield. Cultivars carrying the 2NS/2AS translocation showed lower average disease incidence to WHB. However, this translocation was not associated with increases in grain yield or TKW. This study provides valuable information to assist researchers in selecting wheat cultivars with partial WHB resistance for the tropical regions of the Brazilian Cerrado biome.

Integrative cytogenetic and molecular analyses in Hypostomus sertanejo reveal the lowest diploid number in the genus (Siluriformes: Loricariidae) - Daniela Rodrigues; Ligia Carla Balini; Bárbara Scorsim; Cláudio Henrique Zawadzki; Alessandra Valéria de Oliveira; Marcos Otávio Ribeiro; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes; Eliane Papa Ambrosio-Albuquerque; Luciana Andreia Borin-Carvalho (Biologia, 2026)
Expanding integrative cytogenetic and molecular analyses is essential for understanding the evolutionary dynamics of chromosome number variation in fishes. This study presents the first cytogenetic characterization of Hypostomus sertanejo , an endemic species native to the semi-arid Jaguaribe River basin in Northeastern Brazil. Cytogenetic analysis revealed a diploid number of 2n = 52, which is the lowest documented for the genus, with a karyotype composed of 22m + 8sm + 16st + 6a and a fundamental number of 98. This value aligns with the ancestral diploid number suggested for the tribe Hypostomini. Fluorescence in situ hybridization identified a single 18S rDNA site coinciding with the nucleolar organizer region, while 5S rDNA was localized to an interstitial position on a unique chromosome pair. Molecular analysis based on COI gene confirmed the identity of H. sertanejo and its distinction from closely related species. These results reveal a distinctive evolutionary trajectory for H. sertanejo relative to other Hypostomus species and highlight the importance of integrating data to elucidate diversification patterns in endemic fish lineages.

From by-product to benefit: the effect of white grape marc extracts on European seabass growth, gut microbiota, immune status, and resistance to Vibrio harveyi - Miguel Castro; Rui Magalhães; Rafaela A. Santos; Isabel M. Cerezo; Bárbara Guedes; Ana Couto; Martín Pérez-Díaz; Ana M. Azevedo; Roberto Bermúdez; María I. Quiroga; Maria Celeiro; Marta Lores; et al. (Frontiers in Marine Science, 2026)
Aquaculture intensification has increased the susceptibility of farmed fish to infectious diseases, which are traditionally managed with antibiotics. Growing environmental concerns and the emergence of antimicrobial resistance, however, have driven the search for more sustainable approaches to disease management. White grape marc, a polyphenol-rich by-product of the wine-making industry with known antimicrobial and antioxidant properties, represents a promising functional extract for aquafeeds. This study evaluated the effects of three white grape marc extracts obtained within the NeoGiANT project, using alcohol (ELN), glycol (PLN), and ketone (ACA) solvents, on growth performance, oxidative status, immune response, disease resistance, and gut microbiota of European seabass ( Dicentrarchus labrax ) juveniles. Fish were fed with four isoproteic and isolipidic diets: a control diet (CTRL) and three diets supplemented with white grape marc extracts at 450 ppm of total polyphenolic content per kg of feed. Fish were distributed into triplicate groups and fed for 48 days. Dietary supplementation did not affect survival, growth performance, or feed utilization. However, fish fed the PLN450 diet showed improved protein efficiency and antioxidant status, with higher catalase activity and reduced lipid peroxidation. Immune and stress-related gene expression also tended to be lower in fish fed the PLN450 diet than in those fed the other diets, while gut microbiota composition remained largely unchanged. Following a Vibrio harveyi challenge, mortality did not differ significantly among groups, although fish receiving the supplemented diets showed higher absolute survival than those receiving the CTRL diet. Overall, NeoGiANT grape marc extracts were safe for inclusion in the diets of European seabass juveniles and provided moderate antioxidant benefits, highlighting the potential of winery by-products as functional ingredients to support more sustainable aquaculture.

Screening of cutaneous secretions from Leptodactylus vastus Lutz, 1930 (Anura: Leptodactylidae): identification of bioactive proteins and anticoagulant activity - Tulíbia Laurindo Silva; Géssica Gomes Barbosa; Pollyanna Michelle da Silva; Thiago Lucas da Silva Lira; Carlos José Correia de Santana; Patrícia Maria Guedes Paiva; Ana Patrícia Silva de Oliveira; Thâmarah de Albuquerque Lima; Romero Marcos Pedrosa Brandão Costa; Mariana S. Castro; Thiago Henrique Napoleão (Toxicon, 2026)

Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

Bioactive properties of paraprobiotics and modelling their antilisterial activity in a miniature laboratory model of white cheese over refrigerated storage - Mahmoud Yolmeh; Fakhreddin Salehi; Yuri Matheus Silva Amaral; Ruann Janser Soares de Castro; Anderson S. Sant’Ana (Food Bioscience, 2026)

Structural modifications induced by high pressure homogenization under acidic and alkaline conditions improve the functionality of pequi almond (Caryocar brasiliense Camb.) proteins - Fábio Ribeiro dos Santos; Jeferson Silva Cunha; Irene Andressa; Flaviana Coelho Pacheco; Julliana da Fonseca Alves; Luiz Fernando Cappa de Oliveira; Ana Flávia Coelho Pacheco; Márcia Cristina Teixeira Ribeiro Vidigal; Bruno Ricardo de Castro Leite Júnior (Food Hydrocolloids, 2026)

New-generation pollutants: copper oxide nanoparticles disrupt freshwater ecosystem functioning, impacting host-parasite dynamics and organic matter decomposition - Ana Rita Pimentão; Cláudia Pascoal; Fernanda Cássio; Bruno B. Castro (Aquatic Toxicology, 2026)

First description of the complete mitochondrial genomes of the species Amblyomma humerale and Amblyomma geayi (Acari: Ixodidae), Amazon, Pará, Brazil - Lucas Henrique da Silva e Silva; Fábio Silva da Silva; Sandro Patroca da Silva; Paulo Henrique Gomes de Castro; Anita Roberta Stone; Leonardo Henrique Almeida Hernández; Daniel Damous Dias; Sâmia Luzia Sena da Silva; Lucia Aline Moura Reis; Hanna Carolina Farias Reis; Liliane Leal das Chagas; Tania Cristina Alves da Silveira da Cunha; et al. (Experimental and Applied Acarology, 2026)
The genus Amblyomma koch, 1844 contains approximately 138 species, which are mainly distributed in the Afrotropical, Oriental, Neotropical and Australasian zoogeographic regions. This is an important group of arthropod vectors responsible for transmitting a wide range of etiological agents that cause infections and diseases in humans and animals, and is therefore of great interest to public and veterinary health.This study describes and characterizes, for the first time, the complete mitochondrial genomes of the species Amblyomma humerale and Amblyomma geayi . The obtained sequences presented a circular molecule structured in 37 functional subunits with 13 Protein-Coding Genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNA (rRNAs), two replication control regions, and two regions called “Tick-box”. The phylogeny reconstructed using the maximum likelihood method, based on the 13 concatenated PCGs, produced a monophyletic group for the genus Amblyomma , including the investigated sequences. A. humerale and A. geayi were grouped into the clades formed by the subgenera Walkeriana and Anastosiella , respectively. By integrating complete sequences, the approach adopted expands the number of comparable characters, reduces biases associated with the use of isolated mitochondrial markers, and contributes to better statistical support for the recovered nodes, resulting in more stable and interpretable phylogenetic topologies. The data and information generated in this study can contribute to future taxonomic and evolutionary research on the genus Amblyomma .

Comprehensive Analysis of Mutations in the Hepatitis Delta Virus Genome Based on Full-Length Sequencing in Individuals Infected with Genotype 3 in Brazil - Tárcio Peixoto Roca; Jackson Alves da Silva Queiroz; Ana Maisa Passos-Silva; Mayara Torquato Lima da Silva; Eugênia de Castro-Silva; Lourdes Maria Pinheiro Borzacov; Juan Miguel Villalobos-Salcedo; Deusilene Vieira; Livia Melo Villar (Archives of Virology, 2026)
HDV has a high genetic diversity among isolates and a high capacity to accumulate mutations over time. The mechanisms involved in the clinical progression of HDV are not fully elucidated. Few studies relate mutations to clinical implications, which makes this variable extremely relevant for research into HDV-3, a genotype associated with worse clinical progression. The aim of this study was to analyze mutations in complete genome sequences of HDV-3 isolated in the Brazilian Western Amazon. During 2010 to 2023, 35 hepatitis Delta patients with mild or advanced fibrosis gave serum samples that were submitted to conventional PCR and sequencing. Synonymous and non-synonymous mutations were analyzed along the delta antigen sequence based on the reference strain NC_076103.1. N-terminal and C-terminal regions of Large HDAg, molecular modeling and docking analyses were performed. 114 non-synonymous substitutions were identified in 76 positions along the HDAg-L. To synonymous mutations, 46 substitutions were found in 44 nucleotide sites. S/L8P/Q/M was the most frequent mutation among the advanced fibrosis group. The D46E and A70T mutation was more observed among patients with increased AST. These associations showed statistically significant p-values. Mutations in the N-terminal region of Large HDAg led to minor conformational changes. The C-terminal region indicates moderate structural differences caused by the mutations. The binding conformation of Large HDAg with Mutant2C exhibiting the most stable interaction, as suggested by its docking score. This study shows some evidence of the influence of HDAg mutations in relation to clinical significance, providing insights for further, longitudinal research.

Pentyl (2E)-3-(3-methoxyphenyl) prop-2-enoate attenuates acute respiratory syndrome induced by intestinal ischemia and reperfusion in rats - Viviane Leal Veloso; Wellington dos Santos Alves; Damião Pergentino de Sousa; João Marcelo de Castro e Sousa; Francisco das Chagas Alves Lima; Boris Timah Acha; Ana Flávia Seraine Custódio Viana; Gisele Alves Medeiros; Clailson da Silva Pinheiro; José Gabriel Fontenele Gomes; Maria Luísa Lima Barreto do Nascimento; João Pedro Alves Damaceno do Lago; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Structural abnormalities in erythrocytes and a potential denucleation process induced by metformin, compromising cell viability in specimens of Astyanax lacustris (Pisces, Characidae) - Luara Lupepsa; Pablo Américo Barbieri; Brennda Ribeiro Paupitz; Vanessa Oliveira Sales-Zampar; Helito Volpato; Fernanda Errero Porto Saparolli; Eliane Papa Ambrosio-Albuquerque; Carlos Alexandre Fernandes; Luciana Andreia Borin-Carvalho; Ana Luiza de Brito Portela-Castro (Environmental Science and Pollution Research, 2026)
Hematological studies in fish are sensitive indicators of physiological and pathological changes caused by aquatic pollution, including pharmaceutical contaminants. Among these pollutants, metformin is one of the most prevalent and has been associated with adverse effects on aquatic organisms. However, its impact on fish erythrocyte morphology remains poorly understood. This study evaluated the cyto- and genotoxic effects of metformin on erythrocytes of Astyanax lacustris through morphological analyses, membrane integrity assessment by flow cytometry, and DNA damage evaluation using comet assay. Fish were exposed to metformin concentrations of 50, 100, and 10,000 µg/L for 90 days. Exposure induced significant erythrocyte alterations, particularly at higher metformin concentrations, including membrane invaginations and ruptures, cytoplasmic vacuolization, nuclear abnormalities, DNA damage, peripheral nuclei, and formation of erythroplastids, suggesting denucleation process. Flow cytometry also revealed an increased proportion of non-viable cells. These findings suggest that metformin may significantly impair erythrocyte physiology and viability, potentially compromising the health of exposed fish.

Fisetin attenuates glutamate-induced excitotoxicity and modulates neural progenitor cell dynamics in vitro - Sergio Martínez-Ortega; Bruno I. Benincasa; Felipe G. Nishimura; Ana L. Fachin; Renata Dellalibera-Joviliano; Pedro Nunez-Abades; Carmen Castro; Rene O. Beleboni (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Neurodegenerative diseases (NDs) are characterized by progressive neuronal loss associated with excitotoxicity, oxidative stress, neuroinflammation, and impaired neuroplasticity. Fisetin, a naturally occurring flavonoid, has emerged as a potential neuroprotective compound due to its antioxidant and anti-inflammatory properties. In this study, we investigated the effects of fisetin in cellular models of glutamate-induced excitotoxicity and neural progenitor differentiation. Differentiated PC-12 cells were exposed to 13 mM glutamate and treated with fisetin. Cell viability was assessed using the MTT assay, reactive oxygen species (ROS) production by dihydroethidium assay, and TNF-α levels by ELISA. In parallel, subventricular zone (SVZ)-derived neurosphere cultures were used to evaluate proliferation and differentiation. Fisetin significantly attenuated glutamate-induced cytotoxicity, reduced ROS production, and decreased TNF-α levels. In neurosphere cultures, fisetin reduced neurosphere size without altering neurosphere number, suggesting modulation of progenitor cell dynamics without affecting neural stem cell self-renewal. Moreover, fisetin increased β-III-tubulin-positive neuroblasts without affecting GFAP-positive glial cells. These findings support the pharmacological potential of fisetin in modulating key pathological features of NDs and encourage further in vivo validation and molecular pathway analysis.

First records of spinturnicid mites (Mesostigmata: Spinturnicidae) in Tocantins State, Brazil - Luís Fernando da Cruz; Letícia de Biasi; Liege R. Siqueira; Ana Beatriz Pais Borsoi; Ingrid Benevides Machado; Ademar Ferreira da Silva; Marinete Amorim; Gilberto S. Gazêta; Fernando de Castro Jacinavicius; Darci Moraes Barros-Battesti; Ricardo Bassini-Silva (Biologia, 2026)

A Framework-Based Evaluation of Open Data Platforms in European Ports: A Comparative Study of Barcelona and Antwerp–Bruges - Lucas Freitas; Ana J. Mendes; Marcela Castro; Tiago Pinho (Journal of Marine Science and Engineering, 2026)
Open data platforms (ODPs) are emerging as strategic infrastructures for smart port development within the European Union, yet there is limited research offering integrated approaches to evaluate their performance across technical, operational, and regulatory dimensions. To address this gap, this study develops an analytical framework combining four complementary perspectives: open data platform design, FAIR (Findability, Accessibility, Interoperability, and Reusability) principles, smart port enablement, and EU regulatory alignment. The framework is applied through a qualitative comparative case study of the Ports of Barcelona and Antwerp–Bruges, based exclusively on secondary data sources, including the academic literature, policy documents, and publicly accessible platform data. The analysis is structured around three analytical dimensions—FAIR and interface features and accessibility, smart port enablement, and EU regulatory alignment—applied consistently across both cases. The findings reveal two distinct models: Barcelona adopts an open-by-default approach prioritising accessibility, transparency, and integration with public data ecosystems, while Antwerp–Bruges follows a controlled-access model focused on operational integration, system reliability, and business-to-business data exchange. Both approaches align with EU policy frameworks but involve different trade-offs between openness and operational control. The study contributes a structured, transferable framework for evaluating port ODPs and identifies practices for their design and governance in smart port and maritime logistics contexts.

First confirmation of Caribbean ciguatoxins in fish samples from the South Atlantic coast of Brazil - Rodrigo Hoff; David Castro; Jorge Giráldez; Jose Manuel Leão-Martins; Ana Gago-Martínez (Food Research International, 2026)

Using paradata to improve data quality: A case study on post-wildfire restoration - Ana Castro-Atanes; Maria L. Loureiro (Forest Policy and Economics, 2026)

Neuroprotective and antioxidant effects of fermented spent coffee ground fractions against Alzheimer's-related oxysterol 27-hydroxycholesterol in SH-SY5Y neuronal cells - Alejandra Arancibia-Díaz; Sofía Trujillo-Fernández; Carolina Astudillo-Castro; Mauricio Vergara-Castro; Carmen Soto-Maldonado; Andrés Córdova; María Elvira Zúñiga-Hansen; Ana María Vega-Letter; Paloma Fuentes; Claudia Altamirano (Food Chemistry, 2026)

Impact of measures to increase packaging recyclability in stability of plant-based burgers: A comparative study between multilayer and monolayer lidding films - Cristina Mena; Ricardo Pereira; Beatriz Nunes Silva; Rita Ventura; Ana Carneiro; Susana Teixeira; Fátima Silva; Joel Pereira; Inês Mota; João Ribeiro; Olga Castro; Maria João Monteiro; et al. (Food Packaging and Shelf Life, 2026)

Response of Portulaca oleracea biomass and its rhizospheric microbiome to the application of solid and liquid slumgum from beekeeping industry transformed with Penicillium chrysogenum - Ángel Carrascosa-Robles; José Antonio Pascual; Jessica Cuartero; Inmaculada García-Romera; Gloria Andrea Silva-Castro; Ana de Santiago; Margarita Ros; Spyridon A. Petropoulos; María del Mar Alguacil (Plant and Soil, 2026)
Background and aims Slumgum, a by-product of the beeswax-rendering process, is a nutrient-rich organic waste with potential as a sustainable fertiliser. Unlike chemical fertilisers, which can degrade soil health and contribute to environmental pollution, slumgum may improve soil structure, enhance microbial activity, and support long-term soil fertility. This study assessed, for the first time, the effects of both solid and liquid slumgum, either transformed with Penicillium chrysogenum and non-transformed, on purslane ( Portulaca oleracea ) biomass and soil rhizosphere microbial communities. Methods The experiment involved applying different slumgum treatments to purslane plants, followed by the analysis of shoot biomass and foliar phosphorous content. Soil enzymatic activities related to carbon, nitrogen, and phosphorus cycles were measured. Additionally, bacterial and fungal community composition, diversity, and functional guilds in the rhizosphere were described. Results Both transformed solid and liquid slumgum along with untransformed liquid slumgum treatments increased purslane shoot biomass (by 60–77%) and foliar phosphorous content (by 87–100%) compared to the control. Slumgum treatments modified the microbial community composition, increasing saprotrophic fungi and reducing plant pathogens. Transformed solid slumgum also enhanced enzymatic activities involved in nutrient cycling, whereas the untransformed solid slumgum treatment promoted bacterial genes associated with denitrification. Conclusion Our findings highlight the potential of slumgum, particularly in its transformed forms, as a sustainable alternative to chemical fertilisers. Its application may improve soil fertility and crop productivity while reducing environmental impact. Further studies should investigate its long-term effects under field conditions and evaluate its economic feasibility.

Synthesis and characterization of chitosan-functionalized nanostructured lipid carriers with temozolomide: cytotoxic effects and chromosomal instability in human glioblastoma cells - Helber Alves Negreiros; João Pedro Alves Damaceno do Lago; Victor Alves de Oliveira; Lia Raquel Alves Silva; Ana Carolina Lima de Melo; Igor Gabriel Barbosa de Sousa; Jefferson da Cruz Esteves; Sérgio Eduardo Matos Cazarotti Francisco; Samuel Lemos Paiva; João Pedro Crispim Guerra Rodrigues; Lucas Medeiros Martins Carvalho; Pedro Henricke Oliveira de Souza; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Multiform glioblastoma (GBM) is the most aggressive primary brain tumor, associated with high heterogeneity, treatment resistance, and poor survival. Temozolomide (TMZ), although the main chemotherapeutic agent used, shows limited efficacy due to low solubility, chemical instability, and acquired resistance. In this context, nanostructured systems can enhance their antitumor efficacy. This study aimed to develop and characterize chitosan-functionalized nanostructured lipid carriers loaded with Temozolomide (NLCTQ), as well as to assess their biological activity in human glioblastoma cells (U87-MG). Lipid nanoparticles functionalized with chitosan were prepared by hot emulsification and sonication. Physicochemical characterization included DLS, zeta potential, FTIR, and HPLC for drug quantification and encapsulation efficiency. Biological activity was evaluated in U87-MG cells using the cell viability assay MTT and trypan blue, the comet assay, the spheroid model, fluorescence cell death, and the CBMN assay. The formulation presented a homogeneous nanometric size and positive zeta potential, although with moderate encapsulation efficiency (39%). Biological assays demonstrated that NLCTQ significantly reduced cell viability, overcoming the U87-MG cell line’s resistance to TMZ by achieving cytotoxicity at doses up to 20 times lower than free TMZ. Additionally, NLCTQ promoted the formation of biomarkers of chromosomal instability, such as micronuclei, bridges, and nuclear buds, which may explain the observed cytotoxic effects. Together, the results indicate that TMZ nanoencapsulation in NLCTQ enhances its antitumor efficacy, representing a promising strategy to overcome the limitations of conventional chemotherapy in glioblastoma treatment.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Downscaling urban thermal signals with machine learning: A case study of Danish functional urban areas - Maria Castro; João Paixão; Inês Girão; Bruno Marques; Rune Magnus Koktvedgaard Zeitzen; Rita Cunha; Caio Fonteles; Peter Thejll; Hjalte Jomo Danielsen Sørup; Quentin Paletta; Ana Patrícia Oliveira (Urban Climate, 2026)

Emergence of Dirofilaria immitis in humid coastal zones: Epidemiological predictors and molecular characterization - Ana Clara M.P. Monteiro; Cássia M. Ribeiro; Hllytchaikra F. Fehlberg; Anaiá P. Sevá; Renata J.C. Cruz; Laura P.F. Louro; Maria Eduarda G.S. Castro; Tainara F. Barbosa; Luane E. Barreto; Fábio B. Scott; Ian K. Daniel; Guilherme G. Verocai; et al. (The Veterinary Journal, 2026)

Cystic endometrial hyperplasia in dairy goats: morphological changes and expressions of estrogen receptor-α and progesterone receptor - Agustín Avellaneda-Cáceres; Laura S. Aguirre; Gabriela V. Sandoval; Diego M. Medina; Ana L. Quintana; Francisco Acuña; Gimena Gomez Castro; Claudio G. Barbeito; Juan F. Micheloud (Research in Veterinary Science, 2026)

Influence of climate variability and shark interactions on artisanal deep-water fisheries in Spain's largest marine reserve - David Jiménez-Alvarado; Ana Espino-Ruano; Airam Guerra-Marrero; Julián Cabana-Gandiaga; Tomas Bañeras; José J. Castro-Hernández; Lorena Couce-Montero (Marine Environmental Research, 2026)

The first transcriptome of the diaphanous deep-sea hatchetfish Sternoptyx diaphana Hermann, 1781 (Teleostei: Sternoptychidae) - André Gomes-dos-Santos; Daniel Moita; David Barros-García; André M. Machado; Ana Matos; Nair Vilas-Arrondo; L. Filipe C. Castro; Elsa Froufe (Marine Genomics, 2026)

Assessment of installable offshore solar power capacity in Spain based on maritime spatial planning - Carla Fernández-Blanco; Almudena Filgueira-Vizoso; David Cordal-Iglesias; Ana Isabel García-Diez; Daniel Fernández-Mira; Laura Castro-Santos (Journal of Cleaner Production, 2026)

What drives cultural ecosystem services in mountain protected areas? An AI-assisted answer using social media data - José Carlos Pérez-Girón; Carlos Javier Navarro; Akram Elghouat; Rohaifa Khaldi; Domingo López-Pacheco; Salvador Arenas-Castro; Ana del Águila; Ricardo Moreno-Llorca; Nuria Pistón; Luis F. Romero; Ana Sofía Vaz; Siham Tabik; et al. (Ecosystem Services, 2026)

Do trophic guilds and habitat use influence microplastic ingestion in fishes from the Jaguariaíva River, upper Paraná River basin, Brazil? - Thiago Deruza Garcia; Katia Yofukuji; Rosemara Fugi; Rafael Block Samulewski; Lidiane Vizioli de Castro‑Hoshino; Dhiego Gomes Ferreira; Augusto Seawright Zanatta; Ana Paula Vidotto-Magnoni (Environmental Biology of Fishes, 2026)
Microplastics are emerging pollutants that have raised great concerns to the fish community and are present in most freshwater aquatic ecosystems. These pollutants can cause physical damage and accumulate in the gastrointestinal tract, leading to intestinal obstruction. Thus, the objective of this study was to evaluate the presence of microplastics in the gastrointestinal content of the fish community in the Jaguariaíva River, considered an important tributary of the Itararé River, upper Paraná River basin, Brazil. To this end, we tested whether (i) microplastic ingestion varies among fish from different trophic guilds (detritivores, omnivores, herbivores, insectivores, and piscivores) and (ii) whether ingestion is associated with habitat use (demersal, benthopelagic, and pelagic). The fishes were collected from March 2013 to December 2014 at seven points along the Jaguariaíva River and had their gastrointestinal tracts removed and analyzed in the laboratory. Microplastics were analyzed with a micro Fourier transform infrared spectrometer. In general, fibers and fragments were found in 13 fish species, with their composition being polyvinyl alcohol and polydimethylsiloxane. Furthermore, the consumption of these microplastics was not associated with trophic groups or the types of habitats used by the species analyzed. The presence of microplastics in fish provides insights into the current pollution in the Jaguariaíva River. These findings reinforce the need for mitigation measures to reduce plastic pollution and minimize its impact on aquatic biodiversity.

Histopathological alterations in the synganglion of female Rhipicephalus linnaei ticks treated with essential oils of Egletes viscosa and Lippia schaueriana - Melissa Carolina Pereira; Luis Adriano Anholeto; Marina Rodrigues de Abreu; Karina Neoob de Carvalho Castro; Kirley Marques Canuto; Ana Sheila Queiroz de Souza; Maria Izabel Camargo-Mathias (Arthropod-Plant Interactions, 2026)
The inappropriate use of synthetic chemical acaricides for tick management has contributed to the selection of acaricide-resistant tick strains, thereby stimulating the search for alternative and effective tick control strategies. Among these, the use of essential oils (EOs) derived from plants such as Egletes viscosa Less. (Asteraceae) and Lippia schaueriana Mart. (Verbenaceae) have shown promise in the control of insects and other arthropods. This study aimed to evaluate the effects of E. viscosa and L. schaueriana EOs on the morphohistology of the tick central nervous system (synganglion)—in Rhipicephalus linnaei semi - engorged females. The morphological alterations in the synganglion were assessed using histopathological and semi-quantitative analyses. The EOs, extracted via hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC–MS), revealed 27 constituents in E. viscosa and 18 in L. schaueriana , with cis-isopinocarveol acetate and piperitenone oxide identified as the predominant compounds, respectively. Histological and semi-quantitative analyses of the synganglion in EO-exposed females revealed dose-dependent alterations that were more severe than the mild vacuolization observed in the ethanol control group, primarily characterized by disruptions in the external membrane structures (neurilemma and perineurium), degeneration of the cortical region with hypertrophic, pyknotic, and fragmented neuronal nuclei, cytoplasmic vacuolization, and neuropil fiber disorganization. These findings suggest that the essential oils of E. viscosa and L. schaueriana induce histopathological damage in the synganglion, including neuronal cell damage and potentially impairing other central nervous system-mediated functions, such as feeding and reproduction. This supports the potential of these oils as candidates for the development of novel plant-based acaricides.

Himatanthus drasticus (Mart.) Plumel (APOCYNACEAE): phytochemical profile, evaluation of antibacterial and drug-potentiating activity, and toxicity of stem bark extracts - Maraiza Gregorio de Oliveira; Adrielle Rodrigues Costa; Jailson Renato de Lima Silva; Carlos Alonso leite dos Santos; Ana Raquel Pereira da Silva; Daniel Sampaio Alves; José Weverton Almeida-Bezerra; Ademar Maia Filho; José Walber Gonçalves Castro; Bárbara Fernandes Melo; Francisca de Fátima Silva de Sousa; Marcos Santos; et al. (Vegetos, 2026)

The haunting challenge of the trends and pathway assessments on newly introduced non-indigenous species in European seas - Okko Outinen; Peter A.U. Stæhr; Romeu S. Ribeiro; Aina Carbonell; Robert Comas-González; Lydia Png-Gonzalez; Maite Vázquez-Luis; Ann-Britt Florin; Rahmat Naddafi; Arjan Gittenberger; Hans Jakobsen; Ana C. Costa; et al. (Marine Pollution Bulletin, 2026)

Toxicological profiling of nutraceutical-grade curcumin-loaded solid lipid nanoparticles using Caco-2 cells and zebrafish (Danio rerio) embryo models - Raquel F.S. Gonçalves; Joana Ribeiro; Joana T. Martins; Marisa Sárria Pereira de Passos; Andreia Castro Gomes; António A. Vicente; Ana C. Pinheiro (Toxicology in Vitro, 2026)

Biochemical responses and ingestion of microplastics by native fishes in the Atlantic Forest, southern Brazil - Ananda Karla Alves Neundorf; Ana Paula Nascimento Corrêa; João Mateus Zepson-Capucho; Yara Tani Riuzim; Ubiratã de Assis Teixeira da Silva; Jean Ricardo Simões Vitule; Luís Fernando Fávaro; Ana Caroline Cabral; César de Castro Martins; André Andrian Padial; Lucélia Donatti (Science of The Total Environment, 2026)

Food use, behavioral and cultural significance of the wood-boring mollusc Turu (Teredo sp.) in the Brazilian Amazon - Danilo Vitor Vilhena Batista; Larissa Aparecida Moreira de Castro; Adriana Fernandes de Barros; Caio Francisco Santana Farias; Ana Paula de Souza; Alexandre Vaz da Silva; Carolina Cerqueira Lima Dittrich; Emilly Monteiro Lopes; Elenice Martins Brasil; Marco Shizuo Owatari; José Luiz Pedreira Mouriño; Maurício Laterça Martins (Food and Humanity, 2026)

Emerging trends in wastewater-grown microalgae: A techno-economic and environmental perspective - Ana Paula Maciel de Castro; Matheus Quintão Braga; Pietro Viana Araujo; Rafael Carvalho Nogueira da Gama; Alexia Saleme Aona de Paula Pereira; Thiago Abrantes Silva; Bruno Silva Henriques; Juliana Ferreira Lorentz; Nayara Vilela Avelar; Maria Lúcia Calijuri (Biomass and Bioenergy, 2026)

The reproductive biology of Dyckia scrutor (Bromeliaceae): an endangered species endemic to Campos Rupestres - Marsal Danrlei de Amorim; Luis Gustavo de Sousa Perugini; Ana Carolina Pereira Machado; Sabrina Aparecida Lopes; Rodrigo Santiago; Lucas Benício de Castro; Bárbara Aparecida Lopes Coelho; André Rodrigo Rech (Journal of Plant Research, 2026)
Pollinators are crucial for the conservation of endangered species, providing essential ecosystem services that support plant reproduction. Dyckia scrutor is an endangered species of bromeliad endemic to Campos Rupestres . The genus Dyckia presents species pollinated by both nocturnal and diurnal visitors, with bats and hummingbirds as the most important pollinators. However, the few existing studies about D. scrutor make it difficult to take action to preserve the species. This study aims to describe the floral biology of D. scrutor and identify the contribution of nocturnal and diurnal pollinators to the species’ reproductive success. We monitored reproductive phenology, floral longevity, nectar dynamics, floral visitors, pollinator dependence, pollen limitation, and the relative contribution of nocturnal and diurnal visitors. Although the plant produces seeds in the absence of pollinators, their presence increases production. D. scrutor showed some degree of pollen limitation, and the main floral visitors were the hummingbird Augastes scutatus and Strymon butterflies. Although we observed no nocturnal visits, the number of seeds in flowers open to nocturnal pollinators was higher than in those bagged, indicating that nocturnal pollination occurs. However, the contribution of daytime visitors to seed formation was greater. Our work highlights a case of doubly threatened interaction, in which an endangered plant species of restricted range appears to rely primarily on a hummingbird that is also endemic. These results suggest the need for special and cautious measures to preserve this interaction and consequently, the species involved.

Exploring new acaricidal compounds for environmental control of Amblyomma sculptum (Brazilian spotted fever agent): An in vitro and semi-field comparative study with Rhipicephalus microplus - Ana Carolina de Souza Chagas; Gustavo Avelar Sousa; Rafaela Tami Ikeda Kapritchkoff; Luís Adriano Anholeto; Leonardo Aparecido Lima dos Santos; Vera Lúcia de Castro; Waldomiro Barion-Júnior; Alessandro Pelegrine Minho (Veterinary Parasitology, 2026)

In vitro osteogenic potential of magnesium alloy without and with calcium phosphate coating - Mariana de Oliveira Viana Veras; Fátima Regina Nunes de Sousa; Conceição Silva Martins; Gildênio Estevam Freire; Ana Beatriz Graça Duarte; Thâmara Manoela Marinho Bezerra; Yves Ramos Costa Beviláqua; Stephany Ellen de Castro; Matheus Brandão dos Santos Lopes; Rosemayre Souza Freire; Pierre Basílio Almeida Fechine; Abrahão Cavalcante Gomes de Souza Carvalho; et al. (Tissue and Cell, 2026)

New findings of pseudotachylytes and their paleoseismic significance, Sierras Pampeanas of San Juan, Argentina - Gladis N. Palacio Balderramo; Brígida Castro de Machuca; Ana C. Mugas Lobos; Gustavo F. Ortíz; Gimena M. Bazán; Cristian E. Robledo (Journal of South American Earth Sciences, 2026)

Machine learning-assisted integration to evaluate the impact of fruit pre-washing, direct ozone treatment of coconut water, and storage temperature on physicochemical quality, enzymatic and microbiological inactivation - Eugénio da Piedade Edmundo Sitoe; Larissa Pereira Margalho; Patrícia Monteiro Evangelista; Max Suel Alves dos Santos; Wilma Custódio Fumo; Matheus da Silva Mourão; Alanna Vitória Rocha Eliziário; Ruann Janser Soares de Castro; Anderson S. Sant’Ana (Journal of Food Engineering, 2026)

Polysaccharide-mediated stabilization of bacterial nanocellulose dispersions: Experimental and molecular dynamics study - Ricardo Silva-Carvalho; Daniela Martins; Tarsila G. Castro; Ana Cristina Rodrigues; Bruna Costa; Paula Parreira; Artur Cavaco-Paulo; Fernando Dourado; M. Cristina L. Martins; Miguel Gama (Food Hydrocolloids, 2026)

Pretreatment–gasification coupling for agro-residue conversion: Insights from experimental and Aspen plus simulations - Diana Carolina Castro Mur; Carlos A. Díaz González; Diego Mauricio Yepes Maya; Rafael David Gómez Vásquez; Ana Ramos (Biomass and Bioenergy, 2026)

A survey of vector-borne bacteria in bat-associated mites (Mesostigmata: Macronyssidae and Spinturnicidae) from Brazil reveals the presence of Ehrlichia spp. - Luís Fernando da Cruz; Victor de Souza Mello-Oliveira; Maria Eduarda Moraes das Chagas; Gabriella Soares; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Leormando Fortunato Dornelas-Júnior; Érica Munhoz de Mello; Igor Massahiro de Souza Suguiura; Elizabete Captivo Lourenço; João Carlos Marocco; Letícia Dorigoni; et al. (Veterinary Research Communications, 2026)

Consistent topsoil carbon density and driving factors in urban greenspaces and natural ecosystems - Beatriz Jiménez-Prieto; Pablo García-Palacios; Carmen Lorenzo-Rodríguez; Elena Aguilar-Santana; Josu G. Alday; Camelia Algora; Cristian Carrillo-Guzmán; Cristina Armas; Felipe Bastida; Leonor Calvo; María D. Carmona-Yáñez; Axel Campos-Castro; et al. (Plant and Soil, 2026)
Background Urban greenspaces have the potential to mitigate urban carbon footprints by storing soil organic carbon (SOC). Different management and plant communities associated with different types of urban greenspaces may hold contrasting SOC, as well as different proportions of particulate (POC) and mineral-associated organic carbon (MAOC). In addition, management could outweigh the effects of climate or soil properties as drivers of urban SOC storage, in contrast with natural environments. Methods We analyzed SOC, POC and MAOC densities (kg m −2 ) in topsoil (0-10 cm) across 27 cities in the Iberian Peninsula with contrasting climatic and edaphic conditions. At each city, we compared four types of urban greenspaces (golf courses, roundabouts, urban farms, and parks) with a nearby natural ecosystem. Results Results revealed that, despite large differences in their typology, contrasting urban greenspaces stored comparable topsoil SOC and MAOC densities to natural ecosystems. Golf courses and urban farms also showed similar POC density to natural ecosystems, whereas parks and roundabouts had lower amounts of this carbon fraction. Consistent with global natural patterns, MAOC dominated over POC in the topsoil, and both carbon fractions showed an inverse correlation with mean annual temperature. While MAOC exhibited saturation at higher SOC levels, POC steadily increased. Conclusion Although urban greenspaces are usually neglected in global soil carbon assessments, our study shows that, compared to natural ecosystems (median: 2.42 kg m −2 ; interquartile range: 1.77), these areas store an equally important density of carbon in the topsoil (median: 2.26 kg m −2 ; interquartile range: 1.30), and this carbon exhibits similar fraction dominance, temperature influence, and saturation across large spatial gradients.

Peptide and osteological evidence for sex bias in megalithic tombs of La Lora region, Northern Iberia - Angélica Santa Cruz; Teresa Fernández-Crespo; Ana María Casas-Ferreira; Miguel del Nogal Sánchez; José Luis Pérez Pavón; Rodrigo Villalobos García; Miguel Moreno Gallo; Javier Basconcillos-Arce; Germán Delibes de Castro (Archaeological and Anthropological Sciences, 2026)
Burial patterns of ancient communities based on the analysis of human remains are difficult to define. In this regard, the existence of a sex bias in megalithic tombs of western Europe remains unclear. Sex estimation using standard osteological methodologies based on dimorphic features is a complex task in commingled and fragmentary human skeletal assemblages, as those found in megalithic burials usually are. Fortunately, advances in molecular archaeological research have made it possible to accurately estimate karyotypic sex. In this work, karyotypic sex is estimated from 85 individuals of all age groups from the megalithic burials of La Lora region (Burgos, Spain) through amelogenin peptides from dental enamel to compare with and extend osteological sex estimations and to calculate sex ratios in these assemblages. The results suggest an overall over-representation of males, in agreement with previous osteological data, despite inter-site variability. Some diachronic variations in the sex ratio have also been detected, which may nuance the trend. Specifically, an increase in the ratio of males at the end of the 4th millennium cal. BC, which may be linked to diachronic changes related to social organisation. The results also suggest that sex-related selective burial in non-adult groups would be less restrictive, as more juvenile females were identified, which could point towards patterns of adult female exogamy.

Chemical Induction of Metamorphosis in Ruditapes decussatus and Venerupis corrugata: Concentration and Time-Dependent Effects of Epinephrine and GABA - Beatriz Neves Gregório; Ana Rato; Sandra Joaquim; Marisa Castro; Eric Guévélou; Andreia Cruz; Domitília Matias (Fishes, 2026)
Metamorphosis is a critical bottleneck in the bivalve life cycle, usually associated with high mortality and asynchronous development under hatchery conditions. Synthetic chemical inducers are widely used to overcome these constraints. The neuroactive compounds epinephrine (EPI) and γ-aminobutyric acid (GABA) have been reported to be effective metamorphosis inducers in bivalve species. This study evaluated the inductive efficiency and toxicity of EPI and GABA in two economically important clam species, Venerupis corrugata and Ruditapes decussatus. Competent larvae were exposed to different concentrations (10−2, 10−4 and 10−6 M) for 24, 48 and 72 h. Metamorphic progression and mortality were assessed immediately after exposure and following a six-day post-exposure period. Both compounds induced metamorphosis following concentration–time and species-dependent responses, with narrow efficiency windows and pronounced delayed mortality at higher concentrations and/or longer exposure durations. In V. corrugata, the highest metamorphosis rates were obtained with both compounds at 10−6 M after 48 h. In contrast, R. decussatus required higher EPI concentrations (10−4 M for 48 h) for optimal induction, while GABA at 10−6 M was effective after 24 and 48 h. These findings highlight the need for post-exposure assessments and species-specific optimisation of chemical induction protocols to improve metamorphosis success and spat production in bivalve hatcheries.

Monitoring the reserve effect of a coastal no-take area in the northeast Atlantic along the first ten years of implementation - Ana Filipa Silva; José Lino Costa; Patrícia Teodoro; João J. Castro; Pedro Raposo de Almeida; Bernardo Ruivo Quintella (Ocean & Coastal Management, 2026)

Critical minerals and their conflicts: Dynamics of warnings about lithium exploration in the Vale do Jequitinhonha, Brazil - Paula Ferreira Ribeiro; Ana Beatriz Cabral Gomes Cardoso Lana Dias; Valderí de Castro Alcântara (The Extractive Industries and Society, 2026)

Application of nanoparticles to microalgae-based wastewater treatment: Mechanisms, bioremediation potential and technological frontiers - Matheus Quintão Braga; Juliana Ferreira Lorentz; Alexia Saleme Aona de Paula Pereira; Iara Barbosa Magalhães; Thiago Abrantes Silva; Nayara Vilela Avelar; Bruno Silva Henriques; Ana Paula Maciel de Castro; Paula Peixoto Assemany; Maria Lúcia Calijuri (Journal of Environmental Management, 2026)

Ecotrends: an R package for estimating habitat suitability trends over time - Neftalí Sillero; João Alírio; Nuno Garcia; Inês Freitas; João C. Campos; Lia Bárbara Duarte; Isabel Pôças; Ana Cláudia Teodoro; Salvador Arenas-Castro; A.Márcia Barbosa (Ecological Modelling, 2026)

Effect of high-roughage backgrounding duration on carcass traits and meat quality of young Nellore bulls - Adailton Camêlo Costa; Cris Luana de Castro Nunes; Ana Clara Franklin Santos; Thomas Joaquim Alvarenga Lessa; Guilherme Henrique de Freitas; Pauliane Pucetti; Luciano Saraiva Santos; Nathália Veloso Trópia; Sebastião de Campos Valadares Filho; Mario Luiz Chizzotti (Tropical Animal Health and Production, 2026)

Biostimulant Potential of Vitamins in Soybean Cultivation - Vitória Carolina Dantas Alves; Sebastião Ferreira de Lima; Eduardo Pradi Vendruscolo; Travis Wilson Witt; Arthur Renan Fernandes Nogueira; Laura Martins Ferreira; João Flávio Floriano Borges Gomides; Evelyn Rodrigues de Lacerda; Cassio de Castro Seron; Ana Paula Leite de Lima (International Journal of Plant Production, 2026)

Time-Series Niche Modelling Reveals Declining Tendencies of Habitat Suitability and Ecological Functions in a Mountainous Protected Area - Inês Freitas; João Alírio; Nuno Garcia; João C. Campos; Salvador Arenas-Castro; Isabel Pôças; Lia Duarte; Ana C. Teodoro; Neftalí Sillero (Environmental Management, 2026)
Monitoring biodiversity in protected areas is essential to mitigate biodiversity loss and evaluate the effectiveness of conservation policies. Integrating satellite remote sensing technologies, ecological niche models, and time-series analyses of biodiversity trends offers a fast and robust approach for assessing habitat suitability changes and species vulnerability over time. In this study, we implemented a framework combining these tools to monitor biodiversity in the Montesinho/Nogueira Special Conservation Area (Northeast Portugal). Using the MaxEnt algorithm, we generated ecological niche models for 342 species based on a time series (2001–2023) of remote sensing data from the Moderate-Resolution Imaging Spectroradiometer (MODIS) sensor. We analysed habitat suitability trends with the Mann-Kendall test to detect changes in habitat quality, as a metric of species vulnerability for individual species, five major taxonomic groups (vascular flora, amphibians, reptiles, birds, and mammals), functional groups (e.g. climate affinity, habitat type, diet, activity, reproduction), and conservation status (regional and European levels). Our study revealed a significant decline in habitat suitability over the past two decades, impacting all taxonomic groups and ecological functions. We observed a high variability in habitat suitability trends among species and taxonomic/functional groups, highlighting the complexity of biodiversity responses to environmental changes. Functional traits such as climatic affinity, trophic level or habitat specialisation were associated with variable rates of habitat decline, with species of Atlantic affinity, species associated with croplands and wetlands, and species specialised in insectivorous diets being at higher risk. Overall, these findings emphasise the need for comprehensive biodiversity monitoring programmes and demonstrate the utility of our approach to inform evidence-based conservation strategies in protected areas globally.

Antiarthritic property and toxicological evaluation of the tea prepared from Ximenia americana barks - Gabriela Fernandes Oliveira Marques; Francisco Glerison da Silva Nascimento; Mário Rogério Lima Mota; Ana Paula Negreiros Nunes Alves; Paulo Goberlânio Barros Silva; Maria Gonçalves Pereira; Rondinelle Ribeiro Castro; Ana Maria Sampaio Assreuy (Advances in Traditional Medicine, 2026)
Ximenia americana L. (Olacaceae), popularly known as wild plum, northern plum or Brazilian plum, is used in the folk medicine to treat several inflammatory conditions. This study evaluated the effect of the tea, containing total carbohydrates (44.8%), polyphenols (28 gallic acid equivalent - GAE) and proteins (1.3%), and the polysaccharide fraction (FII) of X. americana barks (Tea-Xa) on rat zymosan-induced arthritis, along with the acute toxicity of Tea-Xa given per oral . Female rats ( N = 36; 200–220 g) received Tea-Xa (30–300 mg/kg; p. o. ) or FII (1 mg/kg; i.v.) 2 h after zymosan-induced arthritis, being evaluated for hypernociception, edema and articular leukocyte influx, histopathological alterations (inflammatory signs, tissue necrosis and disorganization, edema). For toxicity (OECD-423) female rats ( N = 9; 170–200 g) received per oral Tea-Xa (300 or 2000 mg/kg) and were observed for behavioral (14 days) and hematological, biochemical and histopathological parameters (day 14). Tea-Xa and FII reduced joint hypernociception and edema (47%), articular cavity neutrophils (83%) and nitrite (55%). Joint histopathological analysis revealed that Tea-Xa (30–300 mg/kg) and FII reduce tissue disorganization, and Tea-Xa attenuates the inflammatory infiltrate, necrosis and tissue disorganization. Tea-Xa (LD50 greater than 2000 mg/kg/body weight) did not alter body weight, relative organ mass, liver and kidney function markers, or tissue structure. No alterations were observed of most animal behavioral parameters. The polysaccharides of X. americana possess anti-inflammatory and antinociceptive effects on zymosan-induced arthritis and Tea-Xa did not produce adverse effects or mortality.

Population dynamics and life history traits of the commercially important jaguar round crab Xantho poressa (Olivi, 1792) in Gran Canaria’s Intertidal Zones (Spain) - Airam Guerra-Marrero; Ana Espino-Ruano; David Jiménez-Alvarado; Lorena Couce-Montero; José J. Castro (Regional Studies in Marine Science, 2026)

High-dose neonatal riboflavin remodels energy metabolism and brain mitochondrial ultrastructure in rats exposed to maternal high-fat diet - Eulália Rebeca Silva-Araújo; Ana Elisa Toscano; Osmar Henrique dos Santos Júnior; Joaci Pereira dos Santos Júnior; Paula Brielle Pontes; Dyego Maia de Oliveira; Henrique José Cavalcanti Bezerra Gouveia; Maria Luísa Oliveira Buarque Silva; Eduardo Padrón-Hernández; Raul Manhães-de-Castro (Food Research International, 2026)

Extracellular vesicle microRNAs as an epigenetic biosignature of arsenic-associated diabetes in the Strong Heart Study - Christian K. Dye; Allison Kupsco; Gabriela L. Jackson; Ronald A. Glabonjat; Abbas Hakim; Anelizze Castro-Martinez; Louise C. Laurent; Jason G. Umans; Walter Goessler; Shelley A. Cole; Andrea A. Baccarelli; Ana Navas-Acien; et al. (Environmental Research, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

In Silico Analysis and Expression Profiling of Adhesin-Like Flocculins in Trichosporon asahii - Mateus Jorge Mendes dos Santos; Danielle de Castro Quinto; Guilherme de Souza Gagliano; Elaine Cristina Francisco; Ana Carolina Barbosa Padovan (Mycopathologia, 2026)
Background Trichosporon asahii is an opportunistic basidiomycetous yeast increasingly recognized as a cause of invasive infections in immunocompromised individuals, often associated with high morbidity and mortality. Its ability to adhere to host tissues and abiotic surfaces is considered a critical virulence factor, yet the molecular mechanisms underlying this adhesion remain poorly understood. Objective To characterize gene sequences in T. asahii belonging to the flocculin family with potential adhesive functions. Methods The homologous flocculin genes DHA1, DHA2, CPL1, and CFL1 , previously described in Cryptococcus neoformans as being involved in cell adhesion, were identified within the T. asahii predicted proteome. Four T. asahii strains were analyzed: two reference strains (CBS2479 and CBS7631) and two clinical strains (L2585 and L773). Cells were grown in planktonic morphology and biofilms in RPMI + MOPS medium with 2% glucose. The predominant morphology of the cells was observed using bright-field optical microscopy, and total RNA was extracted. The relative expression of the four flocculin genes was analyzed by qRT-PCR and normalized using the 2-ΔΔCt method and the actin gene. Results The flocculin proteins showed high similarity and common domains with C. neoformans flocculins and other adhesins. The strains exhibited a variety of morphologies, with the T. asahii CBS2479 strain predominantly displaying yeast forms, while the T. asahii L2585 strain presented a higher quantity of hyphae. All flocculins bound to human proteins in the PriaA/Cpl1_fungi domain and/or to the Cpl1-like domain. T. asahii flocculins were downregulated when compared to the reference strain CBS2479, while the clinical strain L2585 exhibited the highest expression of the flocculin CFL1 . During biofilm formation, DHA1 and CFL1 were highly expressed. Conclusion Flocculins were expressed according to specific yeast/hyphal morphology and were also more expressed in biofilms, indicating their association with biofilm maintenance and development.

Arabitol production: influence of acid and salt stress on glycerol fermentation by Komagataella pastoris, Scheffersomyces stipitis, and Pichia kluyveri in a batch system - Ana Karen Calderón-Ordaz; Ana Alejandra Vargas-Tah; Agustín Jaime Castro-Montoya; Juan Carlos González-Hernández; Ma. del Carmen Chávez-Parga (Biotechnology Letters, 2026)

Replacing natural savannas with eucalyptus and soybeans changes the matrix use and reduces bat taxonomic and functional diversity in the Amazonian savannas - Bruna S. Xavier; Karen Mustin; Tiago M. Marques; Marcelo M. Ferreira; Renato R. Hilário; José J. Toledo; Isaí J. Castro; Jorge M. Palmeirim; Ana M.C. Santos; Marcus V. Vieira; William D. Carvalho (Agriculture, Ecosystems & Environment, 2026)

Bioeconomic opportunities in restored tropical forests - Pedro Medrado Krainovic; João Paulo Romanelli; Angélica Faria de Resende; Laura Helena Porcari Simões; Ana Flávia Boeni; Lukas Rodrigues Souza; Cássio Augusto Patrocinio Toledo; Vinicius Castro Souza; Joannès Guillemot; Rens Brouwer; Frans Bongers; Paulo Guilherme Molin; et al. (Ambio, 2026)

Hematological and Biochemical Outcomes of Leishmania Infantum Infection in the South American Coati (Nasua nasua) in an Endemic Area of Visceral Leishmaniasis in Central Western Brazil - Gabriel Carvalho de Macedo; André Luiz Rodrigues Roque; Filipe Martins Santos; Wanessa Teixeira Gomes Barreto; Carina Elisei de Oliveira; William Oliveira de Assis; Grasiela Edith de Oliveira; Andreza Castro Rucco; Gisele Braziliano de Andrade; Alanderson Rodrigues da Silva; Nayara Yoshie Sano; Julia Gindri Bragato Pistori; et al. (Acta Parasitologica, 2026)

Ecotoxicological effects of low concentrations of multiple chemical stressors in a Brazilian subtropical estuary: An integrated assessment using green microalgae - Silvia Pedroso Melegari; Ana Claudia Oliveira de Almeida; Ana Caroline Cabral; Laís Ferreira dos Santos; Ítalo Martins Paladino; Marcelo Soeth; Renata Hanae Nagai; Cesar Castro Martins (Marine Pollution Bulletin, 2026)

Characterization of metal contaminants in the Critically Endangered angelshark (Squatina squatina): A first ecotoxicological insight - Tomas Bañeras; David Jiménez-Alvarado; Eva K.M. Meyers; Hector Toledo-Padilla; Arturo Hardisson; Dailos Gonzalez-Weller; Joanna Barker; Lucy R. Mead; Ana Espino-Ruano; Ayoze Castro-Alonso; María José-Caballero; Ángel Gutiérrez (Marine Pollution Bulletin, 2026)

Conservation of an endangered amazonian primate: priority areas for the pied tamarin (Saguinus bicolor) in Manaus, Brazil - Ana Luisa Albernaz; Marcelo Cordeiro Thalês; Marcelo Gordo; Diogo Lagroteria; Tainara V. Sobroza; William E. Magnusson; Philip M. Fearnside; Leandro Jerusalinsky; Renata Bocorny de Azevedo; Rodrigo Baia Castro; Dayse Campista; Wilson Roberto Spironello; et al. (Journal for Nature Conservation, 2026)

Drivers of seedling emergence and early growth of 12 European oak species: Results from a cross-continental experiment - Alexandro B. Leverkus; María Medina; Alba Lázaro-González; Laura Levy; Olivia Lorente-Casalini; Marino P. Reyes Martín; Enrique Andivia; Alessandro Bizzarri; Henrik Böhlenius; Vito E. Cambria; Claudia Cocozza; Branislav Cvjetković; et al. (Forest Ecology and Management, 2026)

Enantioselective toxicity of 3,4-methylenedioxypyrovalerone in Daphnia magna: Assessment of morphophysiological, behavioural, biochemical and reproductive responses - Ariana Pérez-Pereira; Ana R. Carvalho; Pedro A. Costa; Bruno B. Castro; João S. Carrola; Virgínia M.F. Gonçalves; Ana R.L. Ribeiro; Ana Sofia Almeida; Carla Fernandes; Maria E. Tiritan; Cláudia Ribeiro (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Comparison of benchtop and handheld near-infrared spectroscopy for predicting wood properties in fast-growing plantations for bioenergy applications - Caio Cesar Nemer Martins; Vinícius Resende de Castro; Paulo Ricardo Gherardi Hein; Angélica de Cássia Oliveira Carneiro; Adriano Reis Prazeres Mascarenhas; Lina Bufalino; Dayane Targino de Medeiros; Mário Vanoli Scatolino; Michael Douglas Roque Lima; Rafael Silveira Gomes Cardoso; Iara Fontes Demuner; Ana Márcia Macedo Ladeira Carvalho (Biomass and Bioenergy, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Zika Virus Reprograms Microglial Mitochondrial Metabolism to Support Immune Activation and Viral Replication: Omega-3 DHA Counteracts Neuroinflammation and Viral Persistence - Heloísa Antoniella Braz-de-Melo; Fernanda Gomes Lago; Rafael Corrêa; Igor de Oliveira Santos; Paula Maria Quaglio Bellozi; Raquel das Neves Almeida; Wagner Fontes; Mariana S. Castro; Aline Maria Araújo Martins; Raphaela Menezes de Oliveira; Nadia Martins Serpa Rossi; Gabriel Pasquarelli-do-Nascimento; et al. (Molecular Neurobiology, 2026)

Reduced volume in the amygdala of trigeminal neuralgia patients: a neuroimaging study with clinical correlates - Lucas Rego Ramos; Tamires Morett Gama; Ana Clara de Mendonça Maia; Luiza Helena da Fonseca Lima; Orlando Fernandes Jr; Paulo Henrique Rosado de Castro; Marcos Fabio DosSantos (Experimental Brain Research, 2026)

Dissociating the Role of Dorsolateral Prefrontal Cortex and Ventrolateral Prefrontal Cortex in Cognitive Control in Depression: A Combined HD-tDCS and fNIRS Study - Ana Hernández-Sauret; Gonzalo Garcia-Castro; Diego Emilia Redolar-Ripoll (Brain Topography, 2026)
Major depressive disorder (MDD) is marked by cognitive and affective dysfunctions associated with altered prefrontal cortical activity. While high-definition transcranial direct current stimulation (HD-tDCS) shows promise in modulating these deficits, little is known about the differential effects of targeting specific prefrontal subregions. This study investigated whether HD-tDCS over the dorsolateral (DLPFC) or ventrolateral (VLPFC) prefrontal cortex produces distinct behavioural and neurophysiological effects in patients with MDD, focusing on cognitive control, mood, and functional brain connectivity. Twenty-six patients with MDD received ten sessions of HD-tDCS over the left DLPFC, left VLPFC, or sham stimulation. Assessments were performed pre-intervention, post-intervention, and at one-month follow-up. Measures included the Beck Depression Inventory (BDI), World Health Organization Quality of Life – BREF (WHOQOL-BREF), and performance on cognitive tasks. A subset underwent resting-state functional near-infrared spectroscopy (fNIRS) to assess changes in prefrontal connectivity. DLPFC stimulation led to early and sustained improvements in depressive symptoms, executive function (e.g., Trail Making Test, Wisconsin Card Sorting Task), and quality of life domains. VLPFC stimulation produced delayed improvements, particularly in inhibitory control (e.g., Attention Network Test). fNIRS revealed no significant within-group changes in global connectivity, but at follow-up, the DLPFC group showed greater prefrontal connectivity than both VLPFC and sham, suggesting lasting functional reorganization. VLPFC stimulation did not alter global connectivity, possibly reflecting more localized or subcortical effects. HD-tDCS can differentially modulate cognitive and affective processes in MDD. DLPFC stimulation promotes broader, earlier, and more durable effects, while VLPFC stimulation may exert more specific, delayed influences. Functional connectivity measures enhance interpretation of neuromodulatory outcomes in clinical research.

Geostatistical Characterization of Climate Extremes Dynamics: The Drought Phenomenon - Miguel Gomes; Ana Castro; Rita Durão; Amílcar Soares (Mathematical Geosciences, 2025)

Cytotoxic and immunotoxic profile of HgCl2 involves alterations in purinergic signaling through the P2X7/NLRP3/CASP-1/IL-1β pathway: An in vitro study using human blood immune cells - Mairin Schott; Charles Elias Assmann; Bianca Vedoin Copês Rambo; Marcylene Vieira da Silveira; Milagros Fanny Vera Castro; Vitor Bastianello Mostardeiro; Adriel Antônio Schirmann; Robson Lourenço da Silva Santos; Pâmela de Almeida Milioni; Ana Barbosa Viana; Valderi Luiz Dressler; Daniel Lázaro Gallindo Borges; et al. (Toxicology in Vitro, 2025)

Intrafollicular immature oocyte transfer (IFIOT) for IN VIVO maturation of vitrified bovine oocytes - José Eduardo Vieira Chaves; Ana Caroline Chaves Vall Nicolás; Nayara Ribeiro Kussano; Laryssa Ketelyn Lima Pimenta; Venâncio Augusto Oliveira Silva; Alice Caroline Souza e Castro; Ana Cristina Menezes Mendes Gomes; Leonardo de França e Melo; Margot Alves Nunes Dode; José Felipe Warmling Sprícigo (Theriogenology, 2025)

Valorisation of slumgum through fungal biotransformation: Impacts on wheat growth and soil biological activity - Gloria Andrea Silva-Castro; María Camila Espinosa-Araque; César Arriagada-Escamilla; Mario Paniagua-López; Ángel Carrascosa-Robles; Ana De Santiago; María del Mar Alguacil; Inmaculada García-Romera (Bioresource Technology Reports, 2025)

Unveiling enantioselective mechanisms of toxicity of butylone in Daphnia magna - Renata Vidal; Ana R. Carvalho; Juliana Faria; Joana Barbosa; Virgínia M.F. Gonçalves; Maria E. Tiritan; Cristina Couto; João S. Carrola; Bruno B. Castro; Adrián M.T. Silva; Ana R.L. Ribeiro; Cláudia Ribeiro (Aquatic Toxicology, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Safety and efficacy of an intramuscular bivalent vaccine against influenza and Streptococcus pneumoniae infections in mice - Kimberly Freitas Cardoso; Lara Regina Alves de Souza; Débora Silva Martins; Beatriz Senra Álvares da Silva Santos; Ketyllen Reis Andrade de Carvalho; Sarah Giarola da Silva Messias; Ana Paula de Faria Gonçalves; Rayanne Rosa Do Nascimento Macário; Deyse Julia Ferreira de Jesus; Ana Luiza Pessoa De Mendonça Ângelo; Leonardo de Paula Pereira; Sâmick Layene Moreira Nascimento; et al. (Medical Microbiology and Immunology, 2025)

Hydrochars as Bio-based Fertilisers for Enhancing Biomass Growth: Insights into Phosphorus and Metals Dynamics - Hellen Luisa De Castro e Silva; Ana A. Robles-Aguilar; Çağrı Akyol; Hongzhen Luo; Nimisha Edayilam; Erik Meers (Journal of Soil Science and Plant Nutrition, 2025)

Beneficial Use of Marine Gypsum in Cantaloupe Culture and its Environmental Impact on Sandy Soil - Maria Valdete da Costa; José Francismar de Medeiros; Ana Kaline da Costa Ferreira; Paula Romyne de Morais Cavalcante Neitzke; Cíntia Raquel Duarte de Freitas; Fernando Henrique Alves da Silva; Eveline de Almeida Ferreira; Diana Ferreira de Freitas; Jessica Crhistie de Castro Granjeiro; Rita Oliveira Magally da Silva Marcelino; Luiz Fernando de Sousa Antunes; Rafael Oliveira Batista; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Characterization of anti-neutrophil extracellular traps (NET) antibodies according to systemic lupus erythematosus clinical phenotypes - Daniel Alberto Carrillo-Vázquez; Jennifer Tiaré Balderas-Miranda; Rosa Icela Arvizu Rivera; Alfredo Pérez-Fragoso; Beatriz Alcalá-Carmona; Miroslava Nuñez-Aguirre; Ana Sofía Vargas-Castro; Abdiel Absalón-Aguilar; Jaquelin Lira-Luna; Nancy R. Mejía-Domínguez; Guillermo Juárez-Vega; Karina Santana-de Anda; et al. (Immunologic Research, 2025)

Molecular epidemiology of Klebsiella pneumoniae causing bloodstream infections in a district hospital in Northern Portugal (2016–2018): clonal diversity and detection of hypervirulent strains - Michele Loiodice; Tatiana Ribeiro; Luís Marques Silva; Ana Paula Castro; Luísa Peixe; Ângela Novais (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Vermicompost, hydrogel, and beneficial soil microorganisms promote vetiver growth and microbial activity in Cu-impacted tailings - Sofia I. A. Pereira; Ana Faria; Ana S. S. Sousa; Nadine Sousa; Paula M. L. Castro; Helena Moreira (Environmental Sustainability, 2025)

VPS13D-Related Disorders: Description of New Variant and Phenotypic Spectrum Based on Age of Onset - Renata Silva de Mendonça; Ana Beatriz Arruda Santana; Andreia Braga Mota Azzoni; Ana Luiza Viegas de Almeida; Matheus Augusto Araujo Castro; Leandro Tavares Lucato; Fernando Kok; Claudio M. de Gusmao (The Cerebellum, 2025)

Valorization of wastewater-derived biopolymers for use as soil amendments in agriculture - Catarina Miranda; Sofia I. A. Pereira; Ana S. S. Sousa; Philipp Wilfert; Mark van Loosdrecht; António Martins; Paula M. L. Castro; Catarina L. Amorim (Environmental Science and Pollution Research, 2025)

Leaf anatomy of five epiphytic Bulbophyllum Thouars (Orchidaceae) species from the Cerrado of southeastern Brazil: adaptive strategies and taxonomic value - Paula Alves e Silva; Ana Carolina Couto da Silva; Hugo Humberto de Araújo; Reinaldo Alves de Castro; Silvana da Costa Ferreira; Luiz Menini Neto; Jaqueline Dias-Pereira (Flora, 2025)

Cordiaquinone B induces cytotoxicity and oxidative stress-mediated apoptosis in human colorectal cancer cells in vitro and in vivo - Stéphanie Aguiar de Negreiros Matos Silva; Fabrício dos Santos Machado; Luciano de Souza Santos; Maria Victoria Lima de Castro; Mateus Lima Nogueira; Milena Botelho Pereira Soares; Simone Alves Serafim Rocha; Renata Mendonça Araújo; Rosane Borges Dias; Daniel Pereira Bezerra; Ana Jérsia Araújo; José Delano Barreto Marinho Filho (Chemico-Biological Interactions, 2025)

Production of xylo-oligosaccharides from corn cobs using a xylanase-rich cocktail produced by Fusarium sp. E.A1.3.1 in free and alginate-immobilized forms, and in vitro fermentation with Lacticaseibacillus rhamnosus Lyofast LRB and Lactiplantibacillus plantarum LMG P-21021L - Irene Andressa; Glauce Kelly Silva do Nascimento; Tatiane Monteiro dos Santos; Daniela de Oliveira Teotônio; Ana Flávia Coelho Pacheco; Paulo Henrique Costa Paiva; Paulo de Souza Costa Sobrinho; Larissa de Oliveira Ferreira Rocha; Bruno Ricardo de Castro Leite Júnior; Vivian Machado Benassi; Marcio Schmiele (Biocatalysis and Agricultural Biotechnology, 2025)

Substituting grass hay and ground corn with forage cactus genotypes on mineral status of lambs - Luiz Carlos Leal Torres; Tomás Guilherme Pereira da Silva; Ricardo Alexandre Silva Pessoa; Roberto Germano Costa; Daurivane Rodrigues Sousa; Ângela Maria Vieira Batista; Diana Valadares Pessoa; Ihasmyn dos Santos Nunes; Ana Paula Silveira Paim; Dorgival Morais de Lima Júnior; Pierre Castro Soares; Francisco Fernando Ramos de Carvalho (Tropical Animal Health and Production, 2025)

Modulating inflammation and oxidative stress in rheumatoid arthritis: a systematic review of nutraceutical interventions - Camila Leiva-Castro; Ana M. Múnera-Rodríguez; Gádor Torres-Joya; Francisca Palomares-Jerez; Soledad López-Enríquez (Inflammopharmacology, 2025)
Rheumatoid arthritis is a chronic autoimmune disease characterized by persistent synovial inflammation and progressive joint destruction. The gut microbiome has emerged as a key factor in the regulation of the immune system, and its dysbiosis has been implicated in the pathogenesis of rheumatoid arthritis. Nutraceuticals, including probiotics, omega-3 fatty acids, coenzyme Q10, vitamin D, and polyphenols, have shown potential in modulating the gut microbiota and inflammatory pathways. This review explores the interplay between nutraceuticals, gut microbiota, and immune function in rheumatoid arthritis, with attention to pharmacokinetics and safety. We discuss recent clinical evidence, elucidate molecular mechanisms of action, and highlight future research directions for integrating nutraceuticals into therapeutic strategies for rheumatoid arthritis.

Feeding habits of the brown smooth-hound Mustelus henlei (Chondrichthyes: Triakidae) on the west coast of Baja California Sur, Mexico - Ana M. Moncada-Rosas; Alejandra Castro-Díaz; Arturo Tripp-Valdez; Felipe Galván-Magaña (Environmental Biology of Fishes, 2025)

Marine heatwaves and eutrophication jeopardize the seagrass Halodule wrightii and associated infauna - Carlos Eduardo Peixoto Dias; Dairana Misturini; Kalina Manabe Brauko; Guido De Gregório Grimaldi; Alessandro Mateus Sloty; Fernanda Dittmar Cardoso; Luis C.P. de Macedo-Soares; Victória Silvestre Corrêa; Sofia Assunção Castro; Eduardo Bastos; José Bonomi-Barufi; Ana Claudia Rodrigues; et al. (Marine Environmental Research, 2025)

Thermal tolerance and metabolic scope of Sphoeroides annulatus juveniles, a fish with aquaculture potential - Ruth Garcia-Villarreal; Ana Denise Re-Araujo; J. Pablo Sánchez-Ovando; Leonardo Ibarra-Castro; Melany Sánchez-González; Fernando Díaz (Journal of Thermal Biology, 2025)

Consumption of yogurts containing buriti pulp and fermented milks containing orange bagasse increases the response of the endogenous antioxidant system and the expression of heat shock proteins in healthy rats - Juliana S. Graça; Bruna G. Castro; Caroline Heckler; Patrícia B. Batista; Rafael L. Camargo; Marianna M. Furtado; Luísa Freire; Mayra F. Melo; Maria Paula M.B.B. Gonçalves; Amanda M.T.M. Moya; Cínthia B.B. Cazarin; Tatiana C. Pimentel; et al. (Food Research International, 2025)

Hotspots, trends and future prospects of salinization: a scientometric analysis of the effects of salinization on aquatic plants - Saimon Branco Bueno; Alice Pita-Barbosa; Ana Paula Roschildt; Muryllo Santos Castro; Junior Borella (Hydrobiologia, 2025)

Description and Patterns of Hyperostosis in Plata Pompano, Trachinotus marginatus Cuvier, 1832 - Alice Miranda Cardoso de Sá; Márcia Carolina Salomão; Helena Passeri Lavrado; Wilson Thadeu Valle Machado; Ana Paula de Castro Rodrigues; Fernando Augusto Pereira Tuna (Journal of Fish Diseases, 2025)
This study describes the occurrence of hyperostosis, to the best of our knowledge, for the first time in Trachinotus marginatus Cuvier 1832 and examines its patterns in 21 specimens from Rio de Janeiro, Brazil. Radiographic images revealed the presence of the condition in 76.2% of the individuals, affecting five distinct bone regions: supraoccipital (76.2%), dorsal‐fin pterygiophore (52.3%), anal‐fin pterygiophore (9.5%), rib (4.8%) and hemal spine (4.8%). Hyperostosis was consistently observed in the first dorsal pterygiophore and was not found in the other dorsal pterygiophores. A directional linearity was noted in the growth of the supraoccipital crest in the cranial region as the sexual maturation of individuals progressed, demonstrating a tendency for bone expansion. Although hyperostosis is a species‐specific condition, the studied species did not exhibit a clear relationship between specific bone region patterns and the total length of the individual, suggesting no progression in the same affected regions as the animal grows. Longitudinal histological sections of the supraoccipital and ribs revealed high bone porosity caused by hyperostosis, with the presence of several vascular channels. This study represents the first report of the condition of this species, which is an important resource for artisanal fishing in southern Brazilian waters.

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Sustainable control of Tetranychus neocaledonicus André (1933) (Acari: Tetranychidae) on lima bean through essential oils - Ana Caroline Santos de Sousa; Elizabeth Lorena Ramos Cabral; Giovana Lopes da Silva; Mariano Oscar Anibal Ibanez Rojas; Izaias Santos Marques; Angella Maria Alencar Viana; Gutierres Nelson Silva; Solange Maria de França; Paulo Roberto Ramalho Silva; Adriele de Castro Ferreira; Alexandra Lopes Carvalho; Kamilla de Andrade Dutra; et al. (Crop Protection, 2025)

Growth performance, phosphorus balance, gut function and bacteriome of juvenile Amazonian tambaqui (Colossoma macropomum) fed plant-based diets supplemented with phytase and/or xylanase-β-glucanase - Cristiana Leonor da Silva Carneiro; Bárbara Santos; Larissa Pacheco Cassemiro Monteiro; Felipe Rodrigues Saturnino; Mateus Magalhães Olegário; Alessandro Sebastião Gomes Quadros; Maria Goretti Oliveira de Almeida; Ronald Kennedy Luz; Tiago Antônio de Oliveira Mendes; Filipe Castro; Wilson Massamitu Furuya; Ana Lúcia Salaro (Aquaculture, 2025)

Arthrogryposis and axonopathy in the spinal cord in offspring of beef cattle grazing regrowth Sorghum spp. in Brazil - Ana Lívia Vasconcelos de Sousa; Davi Emanuel Ribeiro de Sousa; Cintia Regina Rêgo Queiroz-Machado; Isabeli Joaquim Contel; Alessandre Hataka; Müller Carrara Martins; Anderson Saravia; Edson Moleta Colodel; Aníbal G. Armién; Franklin Riet-Correa; Márcio Botelho de Castro; Mizael Machado (Toxicon, 2025)

Enhancing maize growth and reducing irrigation needs with extracellular polymeric substances and microbial inoculants - Alexandra Overall; Helena Moreira; Ana S.S. Sousa; Philipp Wilfert; Mark van Loosdrecht; Paula M.L. Castro; Sofia I.A. Pereira (Rhizosphere, 2025)

Oxidative foliar photo-necrosis, a mechanism of damage by phyto-pathogenic fungi - Roberto Hernández-Chacón; Lervin Hernández-Ramos; Laura Navarro de la Fuente; Manuel E. Medina; José J. Fernández; Ana R. Díaz-Marrero; Alejandro Salinas-Castro; Irene Lagunes; Ángel Trigos (Physiological and Molecular Plant Pathology, 2025)

Biological indicators of the effectiveness of using treated wastes from the olive industry as an amendment to recover contaminated soils - Cecilia Villareal-Reyes; Maria Ester GARCÍA-BERMÚDEZ; Gloria Andrea SILVA CASTRO; Manuel SIERRA-ARAGÓN; Jesus Dionisio FERNÁNDEZ BAYO; Ana ROMERO-FREIRE (Pedosphere, 2025)

Migration of oceanic fronts in the Pacific Southern Ocean during the Mid-Pleistocene transition - Maria Julia de Castro; Igor M. Venancio; Thiago P. Santos; Douglas V.O. Lessa; João M. Ballalai; Ana Luiza S. Albuquerque (Marine Micropaleontology, 2025)

Resistance of rice against infection by Bipolaris oryzae is differentially induced by β-aminobutyric and γ-aminobutyric acids - Leandro Castro Silva; Bruno Nascimento Silva; Verônica Vieira Brás; Marcela Uli Peixoto Araújo; Ana Claudia Ruschel Mochko; Luiz Felipe Castro Carmo Pinto; Fabrício Ávila Rodrigues (Plant and Soil, 2025)

Ontogenic, Immunological, and Behavioral Changes of Crack Cocaine Exposure During the Gestational Period - Yngrid Mickaelli Oliveira dos Santos; Igor Santana-Melo; Amanda Larissa Dias Pacheco; Milenna Maria Jatoba Hasten Reiter; Maisa de Araújo Costa; Keyla Silva Nobre Pires; Fernanda Maria Araújo de Souza; Jucilene Freitas-Santos; Mayara Rodrigues Barbosa; Jeferson Santana Ursulino; Marvin Paulo Lins; Rayssa Gabriely Duarte Torres; et al. (Molecular Neurobiology, 2025)

COMBINA: coastal ocean marine biosecurity international network of the Americas - Gregory M. Ruiz; Antonio Brante; James T. Carlton; Amy L. Freestone; Inti Keith; Brenda M. Soler-Figueroa; Mark E. Torchin; Alejandro Bortolus; Ricardo Coutinho; Maria Cecilia Trindade de Castro; Thomas Wayne Therriault; Sergio Andrés Benavides Avendaño; et al. (Biological Invasions, 2025)

Performance Improvement of Downdraft Biomass Gasification Using a Physical Barrier and Low-Cost Catalysts for Syngas Enhancement - Mateus Alves Magalhães; Angélica de Cássia Oliveira Carneiro; Tiago Guimarães; Márcio Aredes Martins; Gabriel Browne de Deus Ribeiro; Aylson Costa Oliveira; Barbara Corradi; Vinicius Resende de Castro; Solange de Oliveira Araújo; Paulo Fernando Trugilho; Iara Fontes Demuner; Ana Márcia Macedo Ladeira Carvalho (BioEnergy Research, 2025)

The design of the Brazilian Sub-Daily Rainfall dataset (BR-SDR): two decades of high-time-resolution data in Brazil - Cristiano Das Neves Almeida; Guillaume Francis Bertrand; Filipe Carvalho Lemos; Emerson da Silva Freitas; Abner Lins Silva; José Lindemberg Vidal Barbosa; Marcela Antunes Meira; Geraldo Moura Ramos Filho; Gilson Barbosa Athayde Junior; Flávio José D’Castro Filho; Saulo Aires de Souza; Andrew Thomas Fullhart; et al. (Hydrological Sciences Journal, 2025)

In Silico Development of a Multi-epitope Vaccine Targeting TFDP3: A Novel Approach for Cancer Immunotherapy - Genilda Castro de Omena Neta; Jose Wilson Batista da Silva Junior; Rodger Marcel Lima Rocha; Ana Kelly da Silva Fernandes Duarte; Emisael Stenio Batista Gomes; Fernando Berton Zanchi; Carolinne de Sales Marques; Carlos Alberto de Carvalho Fraga (Cell Biochemistry and Biophysics, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Intracerebral hemorrhage (hemorrhagic stroke) secondary to Bothrops spp. snakebite envenomation in a horse - Ana Lívia Vasconcelos de Sousa; Davi Emanuel Ribeiro de Sousa; Isabel Luana de Macêdo; Liz de Albuquerque Cerqueira; Yasmin Nunes Godoy da Fonseca; Andressa Barbosa Oliveira; Letícia Vilela Silva das Chagas; Geisiana Barbosa Gonçalves; Hennrique Caetano Veado; Kelly Moura Keller; Antônio Carlos Lopes Câmara; Mizael Machado; et al. (Toxicon, 2025)

Retrospective study based on clinical records of veterinary diseases in Goiás, Central-West region of Brazil - Laura Beatriz Gomes Cerqueira; Beatriz Oliveira Braga; Samuel Salvador Marques; Pedro Henrique de Castro Santos; Yasmim Marques da Silva; Juliana Dias Martins; Sergio Tosi Cardim; Ana Maria Duque de Araujo Munhoz; Thiago Souza Azeredo Bastos (Research in Veterinary Science, 2025)

Validating a landscape metric to map fire exposure to hazardous fuels in Portugal - Sidra Ijaz Khan; Maria Conceição Colaço; Ana Catarina Sequeira; Francisco Castro Rego; Jennifer L. Beverly (Natural Hazards, 2025)
Assessing wildfire hazard at the landscape level in Portugal with low-cost and time-saving methods is necessary to guide land and fire managers and protect communities at risk. This study applied a landscape metric developed in Canada to map wildfire exposure in Mainland Portugal between 1995 and 2018. The wildfire exposure metric was computed and validated by examining exposure within subsequently burned areas over five years: 1995, 2007, 2010, 2015, and 2018. Landscape fire exposure was computed by the proportion of neighborhood cells in a 100 m resolution grid that include hazardous fuel types. The resultant exposure metric analyzes the amount of land cover type in the area of a site that will either aid or prevent fire spread. The distribution of exposure levels remained relatively stable over time, decreasing just 0.5% from 1995 to 2018. Approximately 80% of burned areas occurred in sites with substantial exposure (i.e., ≥ 80%). This exposure metric, originally developed in Canada, aligned well with wildfires modulated by Portuguese climate and vegetation, leading to its successful validation. This study uses a simple, time-saving method to show high and low wildfire exposure areas, allowing managers to plan mitigation efforts at different scales, with potential applications for other countries facing large wildfire events.

Sorghum poisoning in ruminants and horses: a review - Ana Lívia Vasconcelos de Sousa; Franklin Riet-Correa; Márcio Botelho de Castro; Mizael Machado (Toxicon, 2025)

The multifaceted spectra of power − A participatory network analysis on power structures in diverse dryland regions - Veronica Olofsson; Maria Mancilla Garcia; Antonio J. Castro; Sofía Cortés Calderón; Amadou Hamath Diallo; Amanda Jiménez Aceituno; María D. López-Rodríguez; Taís Sonetti Gonzalez; Amanda Sousa Silvino; Ana Paula Aguiar (Global Environmental Change, 2025)

Nutritional evaluation of high-value alternative proteins extracted from legume defective seeds - Camila Jiménez-González; Laura Fernández-De-Castro; Ana María Torrado; Clara Fuciños; Elena Díaz-de-Apodaca; María Luisa Rúa (Food Chemistry, 2025)

Correction: The impact of genetics and spacing on productivity and energy stock: perspectives on the expansion of Eucalyptus as a biofuel in Brazil - Maria Kely Alves Gomes da Silva; Rosimeire Cavalcante dos Santos; Renato Vinícius Oliveira Castro; Gualter Guenther Costa da Silva; Rodrigo Eiji Hakamada; Daniela Minini; Laise de Jesus dos Santos; Ana Luiza da Silva Lopes-Nunes; Ananias Francisco Dias Júnior (New Forests, 2025)

Lower inoculum sizes of phosphorus-solubilizing bacteria benefit maize growth and soil enzyme activity in P-fertilized soils - Sofia I. A. Pereira; Ana S. S. Sousa; Aldo B. Felpeto; Andreia Miguel; João C. Pinto; Paula M. L. Castro; Helena Moreira (Symbiosis, 2025)

Soil quality changes in cashew orchard production in Brazilian semiarid areas: a comprehensive field survey across locations, seasons, tree types, and management practices - Arlene Santisteban Campos; Ederson da Conceição Jesus; Paulo Furtado Mendes Filho; Arthur Prudêncio de Araújo Pereira; Ana Cecília Ribeiro de Castro; Arthur Cesar Mina Albuquerque Coelho; Patricia do Nascimento Bordallo; Wardsson Lustrino Borges; Ana Cristina Portugal Pinto de Carvalho (Applied Soil Ecology, 2025)

First evidence of lead-induced impairment of intestinal digestive enzyme activity in birds - Ana C. Castro-Guijarro; Rodolfo J. Arias; Noelia C. Fernández; Juan G. Chediack; Fabricio D. Cid (Environmental Science and Pollution Research, 2025)

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

In vitro evaluation of Bacillus licheniformis protease on the nematodes Panagrellus sp., Meloidogyne incognita, Haemonchus spp. and Trichostrongylus spp - Ana Carolina Silva; Debora Castro de Souza; Adriane Toledo da Silva; Ruth Celestina Condori Mamani; Tiago Facury Moreira; Fabio Ribeiro Braga; Filippe Elias de Freitas Soares (Next Research, 2025)

Improving the effectiveness of safe cyanotoxin removal from drinking water using magnetic iron oxide nanoparticle-loaded carbon composites - Alejandro Cao; Natalia Vilariño; Lisandra de Castro Alves; Yolanda Piñeiro; Jose Rivas; Ana M. Botana; Cristina Carrera; María J. Sainz; Luis Rodríguez-Santos; M. Carmen Louzao; Luis M. Botana (Journal of Water Process Engineering, 2025)

Cytotoxic and metabolic effects of organic extracts from airborne fine particulate matter (PM2.5) in neuronal cells - Tatiana Silva; Célia Alves; Margarita G. Evtyugina; Ana S. Dias; Guilherme Martins Pereira; Pérola de Castro Vasconcellos; Maria de Fátima Andrade; Helena Oliveira; Iola F. Duarte (Environmental Toxicology and Pharmacology, 2025)

Storage increases soluble sugars and decreases bioactive compounds in wild passion fruit (Passiflora cincinnata) - Andréia de Oliveira Militão; Toshik Iarley da Silva; Ana Marinho do Nascimento; Franciscleudo Bezerra da Costa; Alinne Karen Gomes de Castro; Larissa Félix Macêdo; Charlene Maria Alcântara; Maria Ester Maia Evangelista; Giuliana Naiara Barros Sales; Kilson Pinheiro Lopes; Saint Clair Lira Santos (Horticulture, Environment, and Biotechnology, 2025)

Dietary inflammatory index (DII) and telomere length: a systematic review - Joice da Silva Castro; Carolynne Martins Teixeira; Daniela Mayumi Usuda Prado Rocha; Andréia Queiroz Ribeiro; Ana Claudia Pelissari Kravchychyn; Helen Hermana Miranda Hermsdorff (Biogerontology, 2025)

Status and biology of hawksbill turtles at Poilão Island, Guinea-Bissau: a key stronghold for the species in West Africa - Fernando Miguel Madeira; Paulo Catry; Rui Rebelo; Castro Barbosa; Aissa Regalla; Ana Rita Patrício (Biodiversity and Conservation, 2025)
This study provides the first detailed assessment of the hawksbill turtle ( Eretmochelys imbricata ) nesting population from Poilão island, in the Bijagós archipelago of Guinea-Bissau, the only documented regular nesting site for this species in West Africa. Over 17 years, from 2007 to 2024, 29 females were tagged, with one to six individuals nesting annually, some for more than 10 years. Nesting occurs from July to November, coinciding with the green turtle ( Chelonia mydas ) nesting season. Female hawksbills at Poilão are among the largest within the East Atlantic Regional Management Unit (EARMU), with average carapace length of 89.3 ± 4.3 cm. Satellite tracking revealed females remained year-round within the Bijagós archipelago, with small home ranges both during the inter-nesting (∼ 26.13 km 2 ) and foraging periods (∼ 38.41 km²). Genetic sequencing identified two haplotypes - EiBr5 and EiBr7 - linking this population to others from within the EARMU and across the Atlantic, highlighting this rookery’s broader regional significance. Poilão is the single known rookery of origin of the orphan haplotype EiBR5 (also known as EiA49). Despite its importance, the minute size of this population and the lack of evidence for recent recruitment pose challenges to its potential for recovery and effective conservation. This study underscores the need for archipelago-wide sustained conservation measures to ensure the future of the hawksbills from Poilão, and West Africa.

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Characterisation of bioactive compounds from leaves of Smilax fluminensis Steud. by gc-MS and LC-DAD-MS, and analysis of its antioxidant and ecotoxicological activities - Lucas Santos Azevedo; Juliana Costa Fonseca; Ana Hortência Fonsêca Castro; Katyuce de Souza Farias; Vanessa Samúdio Santos Zanuncio; Denise Brentan Silva; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2025)

Runs of homozygosity and selection signature in Santa Inês sheep: A genomic analysis - Tamires de Sousa Silva; Fábio Barros Britto; José Lindenberg Rocha Sarmento; Ana Paula Soares e Silva; Dayane Pereira de Castro; Fabiana Cristina Belchior de Sousa; Gislayne Souza do Nascimento; Gleyson Vieira dos Santos; Natanael Pereira da Silva Santos (Small Ruminant Research, 2025)

Effects of dietary supplementation with slow-release urea coated with carnauba wax on intake, ingestive behavior, selectivity, ruminal parameters, performance and carcass traits of lambs - Tainan da Silva Batista; Leilson R. Bezerra; Pedro H.S. Mazza; Analivia M. Barbosa; Beatriz S.C. de Castro; Melissa D. Ferrer; Ana Carolina Ferreira; Jasiel S. de Morais; Edson C. da Silva Filho; Ronaldo L. Oliveira (Small Ruminant Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Aerobic bioremediation of selenite in marine and freshwater environments via intracellular selenium nanoparticle formation by Pseudomonas frigusceleri MPC6 in glycerol-fed continuous bioreactors - Matias Orellana-Saez; Yeney Lauzurique; Pablo Donoso-Garcia; Manuel Carmona; Andrea Carvajal; Ana L. Riveros; Marcelo J. Kogan; Daniela F. Báez; Ignacio Poblete-Castro (Journal of Environmental Management, 2025)

Environmental and economic benefits of using microalgae grown in wastewater as biofertilizer for lettuce cultivation - Ana Álvarez-González; Iacy M.P. Castro; Antonio Ortiz; Rubén Díez-Montero; Fabiana Passos; Marianna Garfí; Enrica Uggetti (Bioresource Technology, 2025)

Efficacy of a formulation of chlorfenvinphos and dichlorvos on Rhipicephalus microplus in vivo test in Bahia, Brazil - Aline Kelly Araújo Costa Velame Ferreira; Wagner Carvalho e Silva Neto; Igor de Castro Oliveira; Maria Clara Bastos Rodrigues; Ângela Cristina de Oliveira Lima; Tiago Velame Ferreira; Carolina Carneiro de Matos; Ana Karina da Silva Cavalcante; Lorendane Millena de Carvalho; Wendell Marcelo de Souza Perinotto (Tropical Animal Health and Production, 2025)

The impact of genetics and spacing on productivity and energy stock: perspectives on the expansion of Eucalyptus as a biofuel in Brazil - Maria Kely Alves Gomes da Silva; Rosimeire Cavalcante dos Santos; Renato Vinícius Oliveira Castro; Gualter Guenther Costa da Silva; Rodrigo Eiji Hakamada; Daniela Minini; Laise de Jesus dos Santos; Ana Luíza da Silva Lopes-Nunes; Ananias Francisco Dias Júnior (New Forests, 2025)

Nutrient Input from Green Turtle Eggs and Hatchlings in a West Africa Island and Its Nearshore Environment - Cheila Raposo; Ana Rita Patrício; Paulo Catry; Castro Barbosa; Assana Camará; Aissa Regalla; Rui Rebelo (Estuaries and Coasts, 2025)
Sea turtle nesting brings marine-derived nutrients into sandy beach ecosystems, potentially influencing their dynamics. We investigated nutrient input from green turtle Chelonia mydas eggs and hatchlings into coastal habitats in Guinea-Bissau, West Africa. We assessed two islands within the João Vieira-Poilão Marine National Park (‘JVPMNP’), with contrasting sea turtle nesting density: very low (João Vieira) and very high (Poilão). On each island, we analyzed stable isotopes of carbon and nitrogen in one pair of plant species (coinvine Dalbergia ecastaphyllum bush/baobab Adansonia digitata tree) and two pairs of predator species (tufted ghost crab Ocypode cursor /African rainbow crab Cardisoma armatum and sea catfish Carlarius spp./crevalle jack Caranx hippos ). The first species in each pair is distributed closer to nesting sites, while the second is found further inland or offshore. Stomach content analysis was also conducted for fishes. Results supported nutrient input from turtle clutches benefiting the species living near nesting sites. Shoreline coinvines at Poilão had higher δ 15 N (5.1 ± 3.2‰) compared to João Vieira (≈0‰), suggesting assimilation of turtle-derived 15 N. Shoreline tufted ghost crabs at Poilão had enriched δ 15 N (15.2 ± 0.7‰ vs. João Vieira’s 12.2 ± 1.1‰) and δ 13 C (− 13.4 ± 0.7‰ vs. João Vieira’s − 18.7 ± 1.4‰), likely reflecting predation upon eggs and hatchlings. Sea catfishes at Poilão frequently consumed unhatched turtle eggs washed into the sea (17% frequency of occurrence) and hatchlings (up to 27%). This study suggests that nutrient availability from turtle nests influences and supports shoreline plants and consumers at JVPMNP.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Geostatistical Predictive Model of Drought Severity: A Case Study of Southern Portugal - Miguel Gomes; Ana Castro; Rita Durão; Amílcar Soares (Mathematical Geosciences, 2025)
Droughts represent one of the most significant natural hazards, with widespread implications for agriculture, ecosystems, and human livelihoods, particularly in regions like southern Portugal. In recent decades, severe drought events have become increasingly frequent and intense. Considering the potential impacts of droughts, particularly concerning water and river basin management—a critical factor in southern Portugal—the main motivation for this study was the creation of a short-term forecast alert system for drought severity. This study aims to assess the effectiveness of the random forest (RF) model in forecasting drought severity, using consecutive dry days (CDD) as a drought indicator. Daily precipitation data from 17 meteorological stations across southern Portugal were used to classify drought severity into three categories (classes A, B, and C). The RF models were applied to predict the likelihood of each drought severity class, using historical data to forecast future drought conditions. The model's performance results indicate that the RF model performs well in predicting moderate to severe drought classes, with particularly strong accuracy during the peak dry season in July and August. However, the model exhibited challenges in forecasting extreme drought classes, especially during the transitional months of June and September, likely due to the variability in precipitation patterns during these periods. The findings demonstrate the utility of the RF model as a reliable tool for early drought warning and water resource management in southern Portugal. Furthermore, the methodology presented in this study can be adapted to other regions, making it a versatile approach to addressing drought-related challenges worldwide.

Effects of estradiol on PGF2α synthesis and corpus luteum function during early pregnancy in beef heifers - Igor Garcia Motta; Amanda Guimarães da Silva; Isabella Rio Feltrin; Samuel Volpe Souza; Ana Clara Degan Mattos; Karine Galhego Morelli; Thadeu Castro; Thiago Kan Nishimura; Oliver Joseph Ginther; Guilherme Pugliesi (Theriogenology, 2025)

Integrating computational fluid dynamics for hydrodynamic analysis and experimental validation of an Upflow Anaerobic Hybrid (UAHB) system - Lucas Eduardo Ferreira da Silva; Ana Carolina Monteiro Landgraf; Thiago Morais de Castro; Flávia Aparecida Reitz Cardoso; Karina Querne de Carvalho; Eudes José Arantes (Journal of Environmental Chemical Engineering, 2025)

Assessing the efficacy of modified plant vaccine antigens in animal immunization: A systematic review - Tatyane Martins Cirilo; Ana Laura Grossi de Oliveira; Jordânia Costa Pinto; José Bryan da Rocha Rihs; Ana Cristina Loiola Ruas; Williane Fernanda Siqueira; Joseane Camilla de Castro; Nathalia Sernizon Guimarães; Ramayana Morais de Medeiros Brito; Lilian Lacerda Bueno; Thomas J. Cleij; Joni Esrom Lima; et al. (Food Bioscience, 2025)

Effects of digestate soil amendment on the fate of trace metals and on the soil microbial community - Veronica Baldasso; Maria Paola Tomasino; Stéphanie Sayen; Emmanuel Guillon; Luigi Frunzo; Carlos A.R. Gomes; Maria João Alves; Ricardo Castro; Ana Paula Mucha; C. Marisa R. Almeida (Environmental Pollution, 2025)

Influence of seasonality on the toxicity and metals bioavailability after the resuspension of sediments from a tropical estuary - Christiane do Nascimento Monte; Ana Paula de Castro Rodrigues; Bruno Galvão de Campos; Lucas Buruaem Moreira; Beatriz Grebbe; Guacira de Figueiredo Eufrasio Pauly; Ana Carolina Feitosa Cruz; Lílian Irene Dias da Silva; Renato Campello Cordeiro; Denis Moledo de Souza Abessa; Wilson Machado (Estuarine, Coastal and Shelf Science, 2025)

First record of Ixodes uriae White, 1852 (Parasitiformes: Ixodidae) on the great shearwater (Procellariiformes: Procellariidae) in Southern Brazil: a step toward understanding tick-host interactions - Ricardo Bassini-Silva; Fernando de Castro Jacinavicius; Gustavo Seron Sanches; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Carolina Feltes Alves; Eduardo Macagnan; Gabriela Cristini de Souza; Marcos Rogério André; Adriana Silva Albuquerque; Pedro Volkmer de Castilho; Darci Moraes Barros-Battesti; et al. (Veterinary Research Communications, 2025)

New records on autogenic behavior among populations of Ornithodoros fonsecai (Labruna and Venzal, 2009) (Ixodida: Argasidae) from northeastern Brazil - Ana Carolina Castro-Santiago; Leidiane Lima-Duarte; Jaqueline Valeria Camargo; Simone Michaela Simons; Ricardo Bassini-Silva; Ana Cláudia Calchi; Glauber Meneses Barboza de Oliveira; Maurício Cláudio Horta; Sebastián Muñoz-Leal; Marcelo Bahia Labruna; Marcos Rogério André; Rosangela Zacarias Machado; et al. (Veterinary Research Communications, 2025)

Population structure of Santa Inês sheep: the impact of genomic information - Tamires de Sousa Silva; Fábio Barros Britto; José Lindenberg Rocha Sarmento; Ana Paula Soares e Silva Matias; Dayane Pereira de Castro; Fabiana Cristina Belchior de Sousa; Francisca Kauanne Carvalho Silva; Natanael Pereira da Silva Santos (Tropical Animal Health and Production, 2025)

Unraveling the anti-biofilm properties of Laurinterol on pioneer biofouling bacteria from the red seaweed Laurencia johnstonii - Martha Patricia Agúndez-Salas; Ruth Noemí Aguila-Ramírez; Ana Laura González-Castro; Sara García-Davis; Mauricio Muñoz-Ochoa (Journal of Applied Phycology, 2025)

Molecular detection of Ehrlichia Sp. in bat-associated chigger mites (trombidiformes: leeuwenhoekiidae and trombiculidae S. s.) from Brazil - Ricardo Bassini-Silva; Victor de Souza Mello-Oliveira; Beatriz Rocha de Almeida; Isabella Pereira Pesenato; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Elizabete Captivo Lourenço; Katia Maria Famadas; Cal Welbourn; Ronald Ochoa; Marcos Rogério André; Marcelo Bahia Labruna; et al. (Experimental and Applied Acarology, 2025)

Epidemiology of Autosomal Dominant Spinocerebellar Ataxias in Latin America: A Systematic Review and Meta-Analysis - Milagros Galecio-Castillo; Jesus Gutierrez-Arratia; Alonso Abad-Murillo; Elison Sarapura-Castro; Ismael Araujo-Aliaga; Ana Saldarriaga-Mayo; Maryenela Illanes-Manrique; Mario Cornejo-Olivas (The Cerebellum, 2025)

Interaction of Programmed Obesity and Postnatal High Fat Diet but Not (-)-Epicatechin Treatment Modifies Muscle Atrophy Proteins Levels in Male Wistar Rats - Ana Luisa Alvarez-Chávez; Sergio De los Santos; Ramón Mauricio Coral-Vázquez; Luis Antonio Reyes-Castro; Elena Zambrano; Patricia Canto (Cell Biochemistry and Biophysics, 2025)
We determine whether the offspring of obese mothers and a postnatal high-fat diet (HFD) modify protein levels related to muscle synthesis (p70S6K-alpha) or atrophy (Murf and MAFbx), and if the administration of (-)-epicatechin (Epi) can modify these alterations. We hypothesized that the ubiquitin ligases Murf and MAFbx would be increased in the obesogenic context, either by in utero obesogenic environment or by a postnatal high-fat diet, while the p70S6K-alpha kinase and its activation might be decreased. Eight groups of six male Wistar offspring formed eight experimental groups: control (C), control fed with HFD (CHFD), maternal obesity (MO), maternal obesity fed with HFD (MOHFD), and the groups with Epi intervention: C+Epi long, CHFD+Epi long, MO+Epi long and MOHFD+Epi long. By Western blot, we evaluated the Epi effect on the Murf, MAFbx, and p70S6K-alpha proteins in gastrocnemius and soleus tissues. The Murf level increased 2.59-fold in CHFD vs C group and 2.62-fold for MOHFD vs C group ( p = 0.049 and p = 0.048, respectively) in gastrocnemius tissue. In soleus tissue, we observed an increase of MAFbx (1.52-fold) for the MOHFD group versus the C group ( p = 0.049). Epi treatment did not modify any protein expression. In conclusion, we found an increase in the Murf1 protein levels in gastrocnemius tissue of the direct model of obesity; as well, we observed an increase of the Murf1 in gastrocnemius and of the MAFbx in soleus muscles in the group of rats obese by programming and fed postnatally with a high-fat diet (doble stimulus). In addition, since obesity could cause muscle atrophy, which results in impaired muscle function, it would be relevant in future research to evaluate these signaling pathways in animals of different ages in order to search for markers of the progression of diseases such as sarcopenia obesity.

Temporal analysis of extracts from the leaves of Eugenia uniflora L.: chemistry and antifungal activity - Ana Cristina Rocha de Souza; Jeferson Santos Santana; Renan Canute Kamikawachi; Leonardo Dias Meireles; Marcelo José Pena Ferreira; Cristina de Castro Spadari; Kelly Ishida; Miriam Sannomiya (Brazilian Journal of Botany, 2025)

Epidemiological surveillance of myxoma virus in European hares (Lepus europaeus) in the Iberian Peninsula: First evidence of infection by the emerging ha-MYXV - Beatriz Cardoso; Sabrina Castro-Scholten; Roser Velarde; Salvador Rejón-Segura; Remigio Martínez; Ana M. Lopes; Lorena Pereira; Kevin P. Dalton; Andrea Menéndez-Manjón; Josep Estruch; Vanesa Alzaga; Jacinto Román; et al. (Veterinary Microbiology, 2025)

Dietary profiles of wild carnivores and Blastocystis occurrence: The case of the endangered Iberian lynx (Lynx pardinus) and systematic review - Javier Caballero-Gómez; Gabriel Ávalos; Pablo Matas-Méndez; Ana M. Figueiredo; Sabrina Castro-Scholten; Débora Jiménez-Martín; Pamela C. Köster; Mónica Santín; Begoña Bailo; David Cano-Terriza; Pedro Sarmento; Nuno Neves; et al. (Research in Veterinary Science, 2025)

Evaluating slow sand filtration for digestate post-treatment: A step toward safe agricultural reuse in rural communities in Colombia - Mirko Cucina; Liliana Castro; Humberto Escalante; Ivet Ferrer; Alexander Muñoz Muñoz; Jeimmy Lizeth Santamaría Bravo; Ana Fernanda Murcia Ordóñez; Elisabet Toro Vidiella; Marianna Garfí (Journal of Water Process Engineering, 2025)

Investigating the ability of standard tests to detect improvements in behavior after a 9-week training program in shelter dogs – A pilot study - Ana Catarina Vieira de Castro; Mariah Malone; Miriam Casaca; Urša Blenkuš; Lurdes Gomes; Parizad Baria-Unwalla; I.Anna S. Olsson (Journal of Veterinary Behavior, 2025)

How much biodiversity do yellow passionfruit (Passiflora edulis) croplands harbour? Insights from trap-nesting bees, wasps and their natural enemies - Léo Correia da Rocha-Filho; João Custódio Fernandes Cardoso; Aline Claro de Oliveira; Thayane Nogueira Araújo; Ana Luisa de Sousa e Castro-Melo; Solange Cristina Augusto (Journal for Nature Conservation, 2025)

Analysis of germination and vigor of cashew seeds for germplasm conservation by NMR and uPLC-qTOF-MS/MS based metabolomics - Elenilson Godoy Alves Filho; João Ravelly Alves de Queirós; Oriel Herrera Bonilla; Hilton César Rodrigues Magalhães; Edy Sousa de Brito; Paulo Riceli Vasconcelos Ribeiro; Kirley Marques Canuto; Lorena Mara Alexandre e Silva; Ana Cecília Ribeiro de Castro (Food Research International, 2025)

Chemical characterization and antioxidant potential of Arthrospira sp., Thalassiosira sp., and Raphidonema sp. - Vera Castro; Ana Teixeira; Luara Simões; Franklin Chamorro; Catarina Lourenço-Lopes; Celina Parreira; Sara M. Badenes; Luís Costa; Miguel A. Prieto; Rui Oliveira; Alberto C.P. Dias (Food Chemistry, 2025)

Agroecological vulnerability and climate resilience of Jatropha curcas under anthropogenic climate extremes in South America - Lucas Eduardo de Oliveira Aparecido; Guilherme Botega Torsoni; Ana Claudia Costa Baratti; Maíra Ferreira de Melo Rossi; João Antonio Lorençone; Pedro Antonio Lorençone; Rafael Peron Castro (Biomass and Bioenergy, 2025)

Bege Bahia: the Calcrete Known as Brazilian Travertine - Maria Heloisa Barros de Oliveira Frascá; Nuria Fernández Castro; Roberto Carlos Conceição Ribeiro; Ana Cristina Franco Magalhães; Fabiano Cabañas Navarro (Geoheritage, 2025)

Diel activity of insectivorous bats in response to land-use change in São Tomé Island, Gulf of Guinea - Ana Catarina Araújo-Fernandes; Ana Sofia Castro-Fernandes; Patrícia Guedes; José Cassari; Vanessa Alves Mata; Natalie Yoh; Ricardo Rocha; Ana Filipa Palmeirim (Biodiversity and Conservation, 2025)

Antiviral activity of terpenes isolated from marine brown seaweeds against herpes simplex virus type 2 - Lorena da Graça Pedrosa de Macena; Leonardo dos Santos Corrêa Amorim; Kauê Francisco Corrêa de Souza e Souza; Luíza Dantas Pereira; Claudio Cesar Cirne dos Santos; Caroline de Souza Barros; Carlos José Brito Ramos; Marcos Vinicius Santana; Helena Carla Castro; Valéria Laneuville Teixeira; Ana Maria Viana Pinto; Helena de Souza Pereira; et al. (Natural Product Research, 2025)

Thraupis sayaca (Passeriforme: Thraupidae) nesting in an abandoned nest of a social wasp - Lucas Camargos da Silva Araújo; Ana Flávia Silveira Santos; Maria Luiza Simões Silva; Gabriel de Castro Jacques; Marcos Magalhães de Souza (Ornithology Research, 2025)

Novel Intermediate ATXN10 Alleles in the Healthy Peruvian Population: A Matter of Indigenous American Ethnic Origin - Karina Milla-Neyra; Ismael Araujo-Aliaga; Carla Manrique-Enciso; Elison Sarapura-Castro; Maryenela Illanes-Manrique; Diego Veliz-Otani; Ana Saldarriaga-Mayo; Angel Medina-Colque; Julia Rios-Pinto; Ivan Cornejo-Herrera; Andrea Rivera-Valdivia; Ignacio F. Mata; et al. (The Cerebellum, 2025)

Geochemical mapping of modern sedimentary organic matter deposited in a World Heritage subtropical estuary affected by human activities: stable isotopes and molecular approaches - Marines Maria Wilhelm; Ana Caroline Cabral; Felipe Rodrigues dos Santos; Ana Lúcia Lindroth Dauner; Márcia Caruso Bícego; Renata Hanae Nagai; Rubens Cesar Lopes Figueira; Michel Michaelovitch de Mahiques; César de Castro Martins (Environmental Science and Pollution Research, 2025)

Phosphorus acquisition by plants: Challenges and promising strategies for sustainable agriculture in the 21st century - Tamara GÓMEZ-GALLEGO; Iván SÁNCHEZ-CASTRO; Lázaro MOLINA; Carmen TRASAR-CEPEDA; Carlos GARCÍA-IZQUIERDO; Juan L. RAMOS; Ana SEGURA (Pedosphere, 2025)

Impact of ultrasonic pretreatment on pumpkin seed protein: Effect on protease activities, protein structure, hydrolysis kinetics and functional properties - Ana Flávia Coelho Pacheco; Flaviana Coelho Pacheco; Gabriela Aparecida Nalon; Jeferson Silva Cunha; Irene Andressa; Paulo Henrique Costa Paiva; Alline Artigiani Lima Tribst; Bruno Ricardo de Castro Leite Júnior (Food Research International, 2025)

Responses of insectivorous bats to different types of land-use in an endemic-rich island in Central West Africa - Ana Sofia Castro-Fernandes; Ana Catarina Araújo-Fernandes; Patrícia Guedes; José Cassari; Vanessa A. Mata; Natalie Yoh; Ricardo Rocha; Ana Filipa Palmeirim (Biological Conservation, 2025)

Influence of Smilax fluminensis extract and fractions on seed germination and seedling development of mono and eudicotyledonous species - Lucas Santos Azevedo; Ana Hortência Fonsêca Castro; Katyuce de Souza Farias; Vanessa Samúdio Santos Zanuncio; Denise Brentan Silva; Luciana Alves Rodrigues dos Santos Lima (Biocatalysis and Agricultural Biotechnology, 2025)

Molecular evidence of Wolbachia in bat-associated mite Periglischrus Iheringi Oudemans, 1902 (Mesostigmata: Spinturnicidae) from Brazil - Ricardo Bassini-Silva; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; João Carlos Marocco; Letícia Dorigoni; Rosiléia Marinho de Quadros; Marcos Rogério André; Darci Moraes Barros-Battesti; Ashley P. G. Dowling; Marcelo Bahia Labruna; Fernando de Castro Jacinavicius (Veterinary Research Communications, 2025)

Laboratory and physiological aspects of substitute metazoan models for in vivo pharmacotoxicological analysis - Paulo Michel Pinheiro Ferreira; Carla Lorena Silva Ramos; José Ivo Araújo Beserra Filho; Micaely Lorrana Pereira Conceição; Mateus Lima Almeida; Débora Caroline do Nascimento Rodrigues; Jhonatas Cley Santos Porto; João Marcelo de Castro e Sousa; Ana Paula Peron (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Distinct management units for the Critically Endangered angelshark (Squatina squatina) revealed in the Canary Islands - Eva K.M. Meyers; Nadia Faure; David Jiménez-Alvarado; Joanna Barker; Hector Toledo-Padilla; Fernando Tuya; Charlotte Pike; Lucy R. Mead; Michael J. Sealey; Maria Belén Caro; David M.P. Jacoby; Felipe Ravina Olivares; et al. (Conservation Genetics, 2025)
The angelshark, Squatina squatina , is listed as Critically Endangered on the IUCN Red List of Threatened Species, and remaining populations are highly fragmented throughout its historical distribution. The Canary Islands archipelago in the North East Atlantic has been identified as a uniquely large stronghold for the species. In the present study, we compared the population genetic structure of S. squatina across different islands of the Canary Island archipelago using both microsatellite and single nucleotide polymorphism (SNP) markers. Both markers revealed significant differentiation of angelsharks between islands in the archipelago, with three main genetic units at: (1) Tenerife, (2) Gran Canaria and (3) the island group consisting of La Graciosa, Lanzarote and Fuerteventura. Our results imply a connectivity barrier between some adjacent islands, most likely driven by abyssal depths, and varying geological history and formation of each island and oceanographic patterns (i.e. seasonal coastal upwellings off the African coast). Therefore, we suggest that in the Canary Islands, S. squatina populations should be managed locally, with conservation and research priorities designed and implemented specifically for each of the three genetic units.

Assessing spatial and temporal trends over time in potential species richness using satellite time-series and ecological niche models - Nuno Garcia; João C. Campos; João Alírio; Lia B. Duarte; Salvador Arenas-Castro; Isabel Pôças; Ana C. Teodoro; Neftalí Sillero (Biodiversity and Conservation, 2025)
Assessing biodiversity in protected areas is essential for effective conservation management. However, conventional methods for estimating species richness can lead to inaccurate assessments of biodiversity in these regions. To address this, we present a complementary approach to assess potential species richness at a 1 km resolution in the special conservation area of Montesinho/Nogueira (SAC-MN; Portugal), based on a spatial and temporal estimates of species richness trends over time (2001–2021). We compiled 10,190 species occurrence records from four taxonomic groups: amphibians, reptiles, birds, and mammals. We created correlative ecological niche models (MaxEnt) with a time series of satellite-remote sensing variables (SRS-ENMs) using Google Earth Engine (GEE). We calculated annual potential species richness (PSR) maps by stacking the SRS-ENMs and identified positive and negative trends with the Mann–Kendall test. Each species’ ecological niche model revealed unique patterns of habitat suitability within SAC-MN over time. The eastern and western boundaries of SAC-MN revealed an increase in PSR, while the central area indicated PSR declines. Each group displayed different trends in PSR: birds and mammals were more similar between them than amphibians and reptiles. This approach provides ecologists and conservationists with valuable tools to evaluate PSR and trends over time, offering crucial insights for decision-makers and stakeholders to support local biodiversity conservation efforts.

Trypanosoma cruzi has Two Peptidyl-tRNA Hydrolases Showing Different Localization and Function - María Elizabeth Reséndiz-Juárez; Ana Laura Rosas-Soto; Armando Pérez-Rangel; José Tapia-Ramírez; Emmanuel Ríos-Castro; Fanny Rodríguez-Cruz; Ricardo Alejandre-Aguilar; Rebeca Manning-Cela; Gloria León-Avila; José Manuel Hernández-Hernández (Acta Parasitologica, 2025)

A rare case of renal eventration in a domestic cat - Yury Carantino Costa Andrade; Cicera Paloma de Sousa; Lara Vilela Soares; Ana Paula Prueza de Almeida Luna Alves; Anne Karoline Mendes da Silva; Ana Beatriz de Castro Lima; Thamara Barrozo Sampaio; Ana Luiza Teixeira Amado Jorge; André Eduardo Schlemper; Natani Silva Reis; Sofia Borin-Crivellenti; Leandro Zuccolotto Crivellenti (Topics in Companion Animal Medicine, 2025)

Evaluation of dried blood spots for serological surveys of myxoma and rabbit hemorrhagic disease viruses in their wild reservoir - Joana Ferreira-e-Silva; Saúl Jiménez-Ruiz; Marisa Rodrigues; Emídio Santos; Sabrina Castro-Scholten; Vitor Lizana; Alba Martí-Marco; Tereza Almeida; Ana M. Lopes; Joana Abrantes; Juan Bárcena; Esther Blanco; et al. (Preventive Veterinary Medicine, 2025)

SARS-CoV-2 and distemper co-infection in a domestic ferret. Case report - Ana Estephanía Castro-Martínez; Ximena Rosas-Plaza; Andrea Pérez; Erick Martínez-Fuentes; Karla Mollinedo-Beltrán; Adriana Méndez-Bernal; Daniel Alejandro Gómez Pizano; Laura Cobos-Marín (Journal of Exotic Pet Medicine, 2025)

Beyond the threshold - Different accumulation of organochlorine compounds in common dolphins (Delphinus delphis) inhabiting continental and insular ecosystems in the Northeast Atlantic - Raul Valente; Nara de Oliveira-Ferreira; Rita Ferreira; Ana M. Correia; Bárbara M.R. Manhães; Ágatha Gil; Annalisa Sambolino; Elitieri B. Santos-Neto; L. Filipe C. Castro; Haydée A. Cunha; Alexandre F. Azevedo; Ana Dinis; et al. (Environmental Pollution, 2025)

Application of a hybrid fuzzy inference system to map the susceptibility to fires - Miqueias Lima Duarte; Tatiana Acácio da Silva; Jocy Ana Paixão de Sousa; Amazonino Lemos de Castro; Roberto Wagner Lourenço (Natural Hazards, 2025)

Effect of maternal heat stress at different stages of pregnancy on the reproductive performance and antral follicle count of the progeny of Holstein cows - Eduardo Alves Lima; Laís Reis Carvalho; Raphael Evangelista Orlandi; Luiz Manoel Souza Simões; Miguel Pizzolante Bottino; Ana Paula Castro Santos; Fernando de Oliveira Scarpa; Jose Nelio de Sousa Sales (Animal Reproduction Science, 2025)

Optical immunosensor panel using quantum dot-antibody conjugates for highly sensitive detection of carbohydrate antigen 19–9 (CA19-9) - Daniela Oliveira; Pedro Oliveira; Ana Xu; Eduarda Rodrigues; Susana G. Guerreiro; Rafael C. Castro; David S.M. Ribeiro; João L.M. Santos; Ana Margarida L. Piloto (Analytica Chimica Acta, 2025)

Distance From Nest and Climate Explain Geographical Trends of Harvester Ant's Food Resource Use: A Multi‐Species Approach - Diego Anjos; Pedro Luna; Kleber Del‐Claro; Rodrigo G. Pol; Javier Lopez de Casenave; Helena Maura Torezan‐Silingardi; Martha L. Baena; Florencia Baudino; Judie Bronstein; Melissa Burt; Eduardo Calixto; Ana Laura Cao; et al. (Journal of Biogeography, 2025)
Main Animals not only forage for abundant and nearby resources, but their diets can also be influenced by abiotic and geographic factors. This often results in non‐random interactions among species. We investigate how seed density, distance from nest, abiotic (e.g., climate stability, temperature, precipitation) and geographic factors (e.g., latitude, elevation and continental hemisphere) influence the removal of food items (i.e., seeds and dead arthropods) by Pogonomyrmex species. Location South and North America, from Patagonia to the Rocky Mountains. Taxon Genus Pogonomyrmex (Formicidae: Hymenoptera). Methods Conducting standardised experiments, we performed a seed removal experiment and an assessment of the items retrieved by ant workers of 160 nests from eight Pogonomyrmex spp. at 16 sites extending the American continent. Results Pogonomyrmex ants native to North America removed more seeds than their South American counterpart. In general, results align with optimal foraging theory, indicating a higher probability of seed removal near ant nests. High climate stability correlated with lower seed predation rates, emphasising seed consumption's significance in historically arid environments. Increased precipitation and temperature led to reduced removal of food resources, suggesting reduced water availability and lower mean temperatures increases the consumption of seeds by harvester ants. Conclusions Overall, Pogonomyrmex ants' food resource use is influenced by a combination of factors such as region, distance from the nest and climate. This study underscores harvester ants' potential impact on plant distribution over large spatial scales consuming seeds from the immediate proximity of their nest and preventing establishment.

A Probabilistic View of Forbidden Links: Their Prevalence and Their Consequences for the Robustness of Plant–Hummingbird Communities - François Duchenne; Elisa Barreto; Esteban A. Guevara; Holger Beck; Carolina Bello; Rafaela Bobato; Daniela Bôlla; Emanuel Brenes; Nicole Büttner; Ana P. Caron; Nelson Chaves‐Elizondo; María J. Gavilanes; et al. (Ecology Letters, 2025)
The presence in ecological communities of unfeasible species interactions, termed forbidden links, due to physiological or morphological exploitation barriers has been long debated, but little direct evidence has been found. Forbidden links are likely to make ecological communities less robust to species extinctions, stressing the need to assess their prevalence. Here, we used a dataset of plant–hummingbird interactions, coupled with a Bayesian hierarchical model, to assess the importance of exploitation barriers in determining species interactions. We found evidence for exploitation barriers between flowers and hummingbirds across the 32 studied communities; however, the proportion of forbidden links changed drastically among communities because of changes in trait distributions. The higher the proportion of forbidden links, the more they decreased network robustness because of constraints on interaction rewiring. Our results suggest that exploitation barriers are not rare in plant–hummingbird communities and have the potential to limit the rescue of species experiencing partner extinction.

Hg, Cd, As, and Pb in surface sediments from the tropical coastal lagoon Estero Salado, Gulf of Guayaquil-Ecuador - Franklin I. Ormaza-González; Rubén D. Castro-Rendón; Ana Maridueña-Bravo; Nayiva Bobadilla-Cordova; Ivanna Ramos-Castañeda; Peter J. Statham (Frontiers in Marine Science, 2024)
The Gulf of Guayaquil (GG) is the most important tropical estuarine system of the eastern coast of South America, receiving an average water flow of about 1 650 m 3 s -1 from a river basin of approximately 33 700 km 2 . The city of Guayaquil surrounds the inner coastal lagoon of the Estero Salado (ES) that empties into the GG. This coastal lagoon is of high social, food production, and environmental importance for the city and the GG. However, there is limited high quality data on metal pollution in this zone, no recent information on Hg, and the extent to which sediment metal pollution extends into the GG is presently unknown. As, Cd, Pb, and Hg were analysed in surface sediments from the urban zone and gave average concentrations of 32.3, 2.08, 41.9, and 0.12 mg kg -1 (dry weight), respectively. Additionally, data were obtained for the first time for the El Morro Channel, south of the ES in the GG, which is expected to be a relatively pristine zone; average As, Cd, Pb and Hg concentrations were 6.6, 0.22, 7.9 and 0.02 mg kg -1 (dry weight), well below concentrations seen in the urban ES zone. Estimates of the geo-accumulation index for metal pollution, using the El Morro data as background values, were 1.7 (As), 2.7 (Cd), 1.8 (Pb) and 2.0 (Hg), making the ES class II and a moderately polluted estuary for As, Hg and Pb, but class III and “moderately to heavily polluted” for Cd. If the lowest concentrations of the EM samples are taken the ES is class III for As, IV for Hg and Pb, and V for Cd; id est, the ES would classify as a heavily to extremely polluted estuary regarding these metals. These data show the metal concentrations increase significantly as the main conurbation of Guayaquil is approached from offshore, indicating a strong anthropogenic source of metals from the city, with anticipated negative environmental impacts.

Coupled Hydrodynamic and Biogeochemical Modeling in the Galician Rías Baixas (NW Iberian Peninsula) Using Delft3D: Model Validation and Performance - Adrián Castro-Olivares; Marisela Des; Maite deCastro; Humberto Pereira; Ana Picado; João Miguel Días; Moncho Gómez-Gesteira (Journal of Marine Science and Engineering, 2024)
Estuaries are dynamic and resource-rich ecosystems renowned for their high productivity and ecological significance. The Rías Baixas, located in the northwest of the Iberian Peninsula, consist of four highly productive estuaries that support the region’s economy through key fisheries and aquaculture activities. Numerical modeling of biogeochemical processes in the rias is essential to address environmental and anthropogenic pressures, particularly in areas facing intense human development. This study presents a high-resolution water quality model developed using Delft3D 4 software, integrating the hydrodynamic (Delft3D-FLOW) and water quality (Delft3D-WAQ) modules. Calibration and validation demonstrate the robust performance and reliability of the model in simulating critical biogeochemical processes, such as nutrient cycling and phytoplankton dynamics. The model effectively captures seasonal and spatial variations in water quality parameters, including water temperature, salinity, inorganic nutrients, dissolved oxygen, and chlorophyll-a. Of the variables studied, the model performed best for dissolved oxygen, followed by nitrates, phosphates, ammonium, silicate, and chlorophyll-a. While some discrepancies were observed in the inner zones and deeper layers of the rias, the overall performance metrics aligned closely with the observed data, enhancing confidence in the model’s utility for future research and resource management. These results highlight the model’s value as a tool for research and managing water and marine resources in the Rías Baixas.

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Applying the Three Horizons approach in local and regional scenarios to support policy coherence in SDG implementation: Insights from arid Spain - María D. López-Rodríguez; Amanda Jiménez-Aceituno; Cristina Quintas-Soriano; Juan Miguel Requena-Mullor; Enrica Garau; Daniela Alba-Patiño; Irene Otamendi-Urroz; Ana Paula D. Aguiar; Sofía Cortés-Calderón; Antonio J. Castro (Global Environmental Change, 2024)

Environmental surveillance of Cryptosporidium and Giardia in surface supply water and treated sewage intended for reuse from an urban area in Brazil - Ronalda Silva de Araújo; Mikaela Renata Funada Barbosa; Milena Dropa; Vanessa Cristina Araujo de Castro; Ana Tereza Galvani; José Antônio Padula; Antônio de Castro Bruni; Carlos Jesus Brandão; Maria Anete Lallo; Maria Inês Zanoli Sato (Environmental Pollution, 2024)

Flavonoids: the use in mental health and related diseases - Camilla Nicolucci; Milena Padovani; Fernanda de Castro Rodrigues; Laura Nagy Fritsch; Ana Cristina Santos; Denise Gonçalves Priolli; Juliana M. Sciani (Natural Product Research, 2024)

Potential urinary biomarkers in preeclampsia: a narrative review - Renata Araujo Avendanha; Guilherme Figueiredo Coelho Campos; Beatriz Castello Branco; Nicolle Coimbra Ishii; Luiz Henrique Nacife Gomes; Ailton José de Castro; Caio Ribeiro Vieira Leal; Ana Cristina Simões e Silva (Molecular Biology Reports, 2024)

Unravelling epigenetic mechanisms in Cerastoderma edule genome: a comparison of healthy and neoplastic cockles - Alejandro Viña-Feás; Javier Temes-Rodríguez; André Vidal-Capón; Samuel Novas; Jorge Rodríguez-Castro; Ana Pequeño-Valtierra; Juan José Pasantes; Jose M. C. Tubío; Daniel Garcia-Souto (Molecular Genetics and Genomics, 2024)
Cancer is a multifaceted genetic disease characterized by the acquisition of several essential hallmarks. Notably, certain cancers exhibit horizontal transmissibility, observed across mammalian species and diverse bivalves, the latter referred to as hemic neoplasia. Within this complex landscape, epigenetic mechanisms such as histone modifications and cytosine methylation emerge as fundamental contributors to the pathogenesis of these transmissible cancers. Our study delves into the epigenetic landscape of Cerastoderma edule , focusing on whole-genome methylation and hydroxymethylation profiles in heathy specimens and transmissible neoplasias by means of Nanopore long-read sequencing. Our results unveiled a global hypomethylation in the neoplastic specimens compared to their healthy counterparts, emphasizing the role of DNA methylation in these tumorigenic processes. Furthermore, we verified that intragenic CpG methylation positively correlated with gene expression, emphasizing its role in modulating transcription in healthy and neoplastic cockles, as also highlighted by some up-methylated oncogenic genes. Hydroxymethylation levels were significantly more elevated in the neoplastic samples, particularly within satellites and complex repeats, likely related to structural functions. Additionally, our analysis also revealed distinct methylation and activity patterns in retrotransposons, providing additional insights into bivalve neoplastic processes. Altogether, these findings contribute to understanding the epigenetic dynamics of bivalve neoplasias and shed light on the roles of DNA methylation and hydroxymethylation in tumorigenesis. Understanding these epigenetic alterations holds promise for advancing our broader understanding of cancer epigenetics.

Prevalence and molecular characterization of carbapenem-resistant Enterobacterales in patients from a public referral hospital in a non-metropolitan region of Brazil during and post the SARS-CoV-2 pandemic - Romário Costa Fochat; Ana Clara de Lelis Araújo; Olavo dos Santos Pereira Júnior; Marcelo Silva Silvério; Alessandra Figueiredo de Castro Nassar; Maria de Lourdes Junqueira; Marcio Roberto Silva; Patrícia Guedes Garcia (Brazilian Journal of Microbiology, 2024)

Correction: Performance assessment of a new serological diagnostic test for COVID-19 with candidate peptides from spike and nucleocapsid viral proteins - Vanessa de Melo Cavalcanti-Dantas; Alan Frazão da Silva; Andrei Félix Mendes; Waldecir Oliveira de Araújo Júnior; Lucas Coêlho Bernardo-Menezes; Cristiane Campello Bresani-Salvi; Lúcio Roberto Cançado Castellano; Ana Isabel Vieira Fernandes; Sherlan Guimarães Lemos; Jurandy Júnior Ferraz de Magalhães; Renato Antônio dos Santos Oliveira; Priscilla Anne Castro de Assis; et al. (Brazilian Journal of Microbiology, 2024)

In Vivo Test to Evaluate the Cytotoxicity and Genotoxicity of Natural Zeolite (NZ) Functionalized with Silver Nanoparticles (NZ-AgNPs) on Erythrocytes of Yellowtail Tetra Fish Astyanax lacustris - Josiane Rodrigues Rocha da Silva; Camila Oliveira de Andrade; Anna Carla Ribeiro; Paula Derksen Macruz; Elizabeth da Costa Neves FernandesAlmeida Dua; Rosângela Bergamasco; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Biological Trace Element Research, 2024)

The use of water in wineries: A review - Cristina Matos; Manuela Castro; José Baptista; António Valente; Ana Briga-Sá (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Novel PCR assay for the identification of two transmissible cancers in Cerastoderma edule - Martín Santamarina; Alicia L. Bruzos; Ana Pequeño-Valtierra; Jorge Rodríguez-Castro; Seila Díaz; Jose M.C. Tubio (Journal of Invertebrate Pathology, 2024)

Assessment of endogenous and exogenous silver nanoparticles effects on the microalgae Chlorella vulgaris - Natalí Romero; Adrianne Brito; Horacio E. Troiani; Iseli L. Nantes; Guillermo R. Castro; Ana M. Gagneten (World Journal of Microbiology and Biotechnology, 2024)

Paleo-ecological quality status induced by natural and anthropogenic impacts in the last 2000 years: a multidisciplinary approach in the outer region of Sepetiba Bay (SE Brazil) - Murilo Barros Saibro; Maria Virgínia Alves Martins; Rubens Figueira; Egberto Pereira; Heitor Evangelista; Marcus Vinícius Licínio; Josefa Varela Guerra; Felipe de Castro Figueiredo Simões; Vincent Marcel Pierre Bouchet; Fabio Francescangeli; Fabrizo Fontalini; Paulo Alves de Lima Ferreira; et al. (Journal of Soils and Sediments, 2024)
Purpose Some marine organisms can be used as Biological Quality Elements to estimate the degree of environmental impact and to monitor the health of benthic habitats. Organisms with mineralized protections, such as benthic foraminifera, can provide helpful information on the evolution of the coastal system over a long period and determine the Paleo-Ecological Quality Status (Paleo-EcoQS). This work aims at reconstructing the Paleo-EcoQS in the heavily anthropized Sepetiba Bay (SB; Rio de Janeiro State, SE Brazil). Materials and methods This work is based on a multiproxy approach, including textural, geochemical, and foraminiferal data along the core SP11 retrieved near the Pico da Marambaia (a mountain on the tip of the Marambaia Barrier Island). Geochemical analyses encompassing total organic carbon (TOC), total sulfur (S), total nitrogen (N), calcium carbonate (CaCO 3 ), stable isotopes in organic matter ( OM δ 13 C, and OM δ 15 N) and elemental concentrations as well as 201 Pb, 137 Cs, and radiocarbon dating were performed to characterize the Paleo-EcoQS in the bay. Results The values of the Paleo-EcoQS.st (standardized Paleo-EcoQS) index in core SP11 indicate that the paleoenvironmental quality varied from moderate to good between ≈50 AD and ≈1500 AD and from good to high between the ~ 1920s and ~ 1990s. Since the 1990s, the Paleo-EcoQS.st has deteriorated considerably, probably due to the deposition of contaminated dredging material in nearby areas. Ballast water discharge may have introduced alien species, such as Ammonia buzasi , into the SB. Conclusions The results obtained in core SP11, compared to those of another core (i.e., SP8) from a nearby area, suggest that the reference level of maximum environmental quality is not always reached in a period before industrialization in coastal ecosystems with significant interaction with the ocean; natural factors, related, for example, to sedimentary dynamic processes or geomorphological changes, can lead to unexpected results.

Quantification of relevant metabolites in apoptotic bodies from HK-2 cells by targeted metabolomics based on liquid chromatography-tandem mass spectrometry - Samuel Bernardo-Bermejo; Ana B. Fernández-Martínez; Francisco Javier Lucio-Cazaña; María Castro-Puyana; María Luisa Marina (Analytica Chimica Acta, 2024)

Influence of Dolphin-Watching Tourism Vessels on the Whistle Emission Pattern of Common Dolphins and Bottlenose Dolphins - Ana A. Silva; Joana Castro; André Cid; Sérgio M. Jesus; Fábio L. Matos (Oceans, 2024)
Recent years have seen a notable rise in dolphin-watching boat activities along the Algarve coast in Portugal, potentially affecting the common dolphin (Delphinus delphis) and bottlenose dolphin (Tursiops truncatus) local populations. This study examines the impact of increasing underwater noise levels from these boats on dolphin vocalizations. Field recordings were conducted from June to September 2022, analyzing dolphin whistles in various boat presence scenarios. The results indicate significant changes in whistle-frequency characteristics with boat presence, including increased start, low, and high frequencies, alongside a decrease in the number of inflection points in modulated whistles. The changes might negatively impact dolphin populations viability, underscoring the need for further research. Additionally, improved mitigation strategies may be necessary to reduce the potential negative effects of dolphin watching on cetacean communication and behavior in the Algarve region.

Integrating waste valorization and symbiotic microorganisms for sustainable bioremediation of metal(loid)-polluted soils - Mario Paniagua-López; Gloria Andrea Silva-Castro; Ana Romero-Freire; Francisco José Martín-Peinado; Manuel Sierra-Aragón; Inmaculada García-Romera (Science of The Total Environment, 2024)

Germination as a strategy to improve the characteristics of flour and water-soluble extracts obtained from sunflower seed - Irene Andressa; Maria José do Amaral e Paiva; Flaviana Coelho Pacheco; Fábio Ribeiro Santos; Jeferson Silva Cunha; Ana Flávia Coelho Pacheco; Nathalia de Andrade Neves; Raquel Guidetti Vendruscolo; Marcio Schmiele; Alline Artigiani Lima Tribst; Érica Nascif Rufino Vieira; Bruno Ricardo de Castro Leite Júnior (Food Bioscience, 2024)

Corrigendum to “Potential availability of metals in anaerobic mono- and co-digestion of pig manure and maize” [Bioresour. Technol. 402 (2024) 130818] - Hellen Luisa de Castro e Silva; Ana A. Robles-Aguilar; Çağrı Akyol; Bernard Willems; Erik Meers (Bioresource Technology, 2024)

Oral administration of Lactobacillus delbrueckii UFV-H2b20 protects mice against Aspergillus fumigatus lung infection - Ana Clara Matoso Montuori de Andrade; Nathalia Luisa Oliveira; Ana Elisa Nolasco e Silva; Leonardo Gomes Vaz; Flávia Rayssa Braga Martins; Mateus Eustáquio de Moura Lopes; Lícia Torres; Celso Martins Queiroz; Remo Castro Russo; Liliane Martins dos Santos; Leda Quercia Vieira; Frederico Marianetti Soriani (Inflammation Research, 2024)

XylR regulates genes at xyl cluster, involved in D-xylose catabolism in Herbaspirillum seropedicae Z69 - Ana Karen Malán; Juan José Marizcurrenaa; Manuela Oribe; Susana Castro-Sowinski; Silvia Batista (Archives of Microbiology, 2024)

Generating insights to improve the performance of communities supported agriculture: an analysis focused on female participation, governance structure and volume of food distributed - Gustavo Alves de Melo; Maria Gabriela Mendonça Peixoto; Samuel Borges Barbosa; Ana Júlia Silva Alves; Anna Clara Lasso Souza; Maria Cristina Angélico Mendonça; Luiz Gonzaga de Castro Júnior; Patrícia Guarnieri dos Santos; André Luiz Marques Serrano; Clóvis Neumann (Environment, Development and Sustainability, 2024)

Short preconditioning with TGFβ of equine adipose tissue-derived mesenchymal stem cells predisposes towards an anti-fibrotic secretory phenotype: A possible tool for treatment of endometrosis in mares - Yat Sen Wong; Ana Carolina Mançanares; Felipe Navarrete; Pamela Poblete; Lidice Mendez-Pérez; Lleretny Rodriguez-Alvarez; Fidel Ovidio Castro (Theriogenology, 2024)

Minor loss or huge threat? Assessment of potential infrastructure projects reveals drastic landscape degradation in the Atlantic forest - Jéssica Stéfane Alves Cunha; Nathan Castro Fonsêca; Cinthia Renata Vieira de Lima; Jhonathan Gomes dos Santos; Herbert de Tejo Pereira; Bruna Martins Bezerra; Ana Carolina Borges Lins-e-Silva (Journal for Nature Conservation, 2024)

Use of ultrasound to improve the activity of cyclodextrin glycosyltransferase in the producing of β-cyclodextrins: Impact on enzyme activity, stability and insights into changes on enzyme macrostructure - Jeferson Silva Cunha; Flaviana Coelho Pacheco; Caio Cesar Nemer Martins; Ana Flávia Coelho Pacheco; Alline Artigiani Lima Tribst; Bruno Ricardo de Castro Leite Júnior (Food Research International, 2024)

Digitalising BIPV energy simulation: A cross tool investigation - Rebecca Jing Yang; Yusen Zhao; Sujan Dev Sureshkumar Jayakumari; Astrid Schneider; S. Prithivi Rajan; Jonathan Leloux; Philippe Alamy; Gavin Prasetyo Raharjo; Fedele Rende; Tharushi Samarasinghalage; Ana Marcos Castro; Nuria Martin Chivelet; et al. (Energy and Buildings, 2024)

Hydrothermal carbonisation of manure-derived digestates: Chemical properties and heavy metals distribution in end-products - Hellen Luisa de Castro e Silva; Stef Ghysels; Ana A. Robles-Aguilar; Çağrı Akyol; Frederik Ronsse; Erik Meers (Chemical Engineering Journal, 2024)

Antimicrobial resistance, virulence genes, and ESBL (Extended Spectrum Beta-Lactamase) production analysis in E. coli strains from the Rio Grande/Rio Bravo River in Tamaulipas, Mexico - Rocío Requena-Castro; María Guadalupe Aguilera-Arreola; Ana Verónica Martínez-Vázquez; Wendy Lizeth Cruz-Pulido; Gildardo Rivera; Virgilio Bocanegra-García (Brazilian Journal of Microbiology, 2024)

Effect of solid-state fermentation of Brewer's spent grain on digestibility and digestive function of european seabass (Dicentrarchus labrax) juveniles - Tássia Estevão-Rodrigues; Helena Fernandes; Sara Moutinho; Diogo Filipe; Filipa Fontinha; Rui Magalhães; Ana Couto; Marta Ferreira; Margarida Gamboa; Carolina Castro; Isabel Belo; José Salgado; et al. (Animal Feed Science and Technology, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Biochemical profile and oocyte quality of primiparous Bos indicus cows submitted to a timed artificial insemination protocol - Miguel Pizzolante Bottino; Laís Reis Carvalho; Raphael Evangelista Orlandi; Ana Paula Castro Santos; Luiz Manoel Souza Simões; Felipe Perecin; Gabriella Mamede Andrade; Guilherme de Paula Nogueira; Marcos Antônio Maioli; José Nélio de Sousa Sales (Theriogenology, 2024)

ESR chronology of the endokarstic deposits of Galería complex (Sierra de Atapuerca, Spain) - Isabel Hernando-Alonso; Davinia Moreno; Ana Isabel Ortega; Alfonso Benito-Calvo; María Jesús Alonso; Isidoro Campaña; Josep María Parés; Isabel Cáceres; Paula García-Medrano; Eudald Carbonell; José María Bermúdez de Castro (Quaternary Geochronology, 2024)

Dynamic shifts of functional diversity through climate-resilient strategies and farmland restoration in a mountain protected area - João C. Campos; João Alírio; Salvador Arenas-Castro; Lia Duarte; Nuno Garcia; Adrián Regos; Isabel Pôças; Ana C. Teodoro; Neftalí Sillero (Journal of Environmental Management, 2024)

Sulfonamide-chalcone hybrid compound suppresses cellular adhesion and migration: Experimental and computational insight - Gisele Santos de Araújo; Andrea Felinto Moura; Ayslan Batista Barros; Manoel Odorico Moraes; Claudia Pessoa; Caridad Noda Perez; Mirian Rita Carrilho de Castro; Fábio de Oliveira Silva Ribeiro; Durcilene Alves da Silva; Paulo Sérgio de Araújo Sousa; Jefferson Almeida Rocha; José Delano Barreto Marinho Filho; et al. (Chemico-Biological Interactions, 2024)

Molecular detection of Bartonella spp. in bat-associated macronyssid mites (Acari: Macronyssidae) from Southern and Southeastern Brazil - Maria Eduarda Moraes das Chagas; Victor Souza de Mello-Oliveira; Mariane Guerro-de-Souza; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Érica Munhoz de Mello; Igor Massahiro Souza de Suguiura; Elizabete Captivo Lourenço; Katia Maria Famadas; Ashley P. G. Dowling; Marcos Rogério André; Darci Moraes Barros-Battesti; et al. (Veterinary Research Communications, 2024)

Long-term administration of omeprazole in mice: a study of behavior, inflammatory, and oxidative stress alterations with focus on central nervous system - Dulce Maria Nascimento Coelho; Dilailson Carlos Costa Júnior; Daniel Moreira Alves da Silva; Ana Carolina Benício Alves; Raquell de Castro Chaves; Manoela de Oliveira Rebouças; José Tiago Valentim; Andressa Alexandre de Oliveira; Iardja Stefane Lopes Sales; Lucas Antonio Duarte Nicolau; Francisca Cléa Florenço de Sousa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Regulation of growth and stress metabolism in rice plants through foliar and root application of seaweed extract from Kappaphycus alvarezii (Rhodophyta) - Tadeu Augusto van Tol de Castro; Orlando Carlos Huertas Tavares; Danielle França de Oliveira Torchia; Erinaldo Gomes Pereira; Natalia Fernandez Rodrigues; Leandro Azevedo Santos; Ana Lúcia do Amaral Vendramini; Mauricio Roque da Mata; Carolina Vieira Viêgas; Ricardo Luiz Louro Berbara; Andrés Calderín García (Journal of Applied Phycology, 2024)

Performance assessment of a new serological diagnostic test for COVID-19 with candidate peptides from spike and nucleocapsid viral proteins - Vanessa de Melo Cavalcanti-Dantas; Alan Frazão da Silva; Andrei Félix Mendes; Waldecir Oliveira de Araújo Júnior; Lucas Coêlho Bernardo-Menezes; Cristiane Campello Bresani-Salvi; Lúcio Roberto Cançado Castellano; Ana Isabel Vieira Fernandes; Sherlan Guimarães Lemos; Jurandy Júnior Ferraz de Magalhães; Renato Antônio dos Santos Oliveira; Priscilla Anne Castro de Assis; et al. (Brazilian Journal of Microbiology, 2024)

Use of otolith microchemistry signatures to assess the habitat use of Centropomus undecimalis in lagoon systems of the southwest Atlantic - Paulo Roberto Camponez de Almeida; Marcus Rodrigues da Costa; Rebeca Dias de Souza Coutinho; Ana Méndez-Vicente; Jorge Pisonero Castro; Cassiano Monteiro-Neto; Rafael de Almeida Tubino; Alberto Teodorico Correia (Regional Studies in Marine Science, 2024)

The effect of acute exposure of yellowtail tetra fish Astyanax lacustris (Lütken, 1875) to the glyphosate-based herbicide Templo® - Camila Oliveira de Andrade; Josiane Rodrigues Rocha da Silva; Pablo Americo Barbieri; Luciana Andrea Borin-Carvalho; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Laetia procera (Poepp.) Eichler can be included in polycyclic management programs for timber production, replacing species intensively harvested in the Amazon forest - Ana Paula Souza Ferreira; João Olegário Pereira de Carvalho; Cassio Rafael Costa dos Santos; Washington Duarte Silva da Silva; Tatiana da Cunha Castro; Afonso Figueiredo Filho; Ademir Roberto Ruschel (Forest Ecology and Management, 2024)

Inter-island nesting dynamics and clutch survival of green turtles Chelonia mydas within a marine protected area in the Bijagós Archipelago, West Africa - Cheila Raposo; Rui Rebelo; Paulo Catry; Maria Betânia Ferreira-Airaud; Castro Barbosa; Tumbulo Bamba Garcia; Aissa Regalla; Manuel Sá Sampaio; Ana Rita Patrício (Marine Biology, 2024)
Understanding spatial heterogeneity in reproductive success among at-risk populations facing localised threats is key for conservation. Sea turtle populations often concentrate at one nesting site, diverting conservation efforts from adjacent smaller rookeries. Poilão Island, Bijagós Archipelago, Guinea-Bissau, is a notable rookery for green turtles Chelonia mydas within the João Vieira-Poilão Marine National Park, surrounded by three islands (Cavalos, Meio and João Vieira), with lower nesting activity. Poilão’s nesting suitability may decrease due to turtle population growth and sea level rise, exacerbating already high nest density. As the potential usage of secondary sites may arise, we assessed green turtle clutch survival and related threats in Poilão and its neighbouring islands. High nest density on Poilão leads to high clutch destruction by later turtles, resulting in surplus eggs on the beach surface and consequently low clutch predation (4.0%, n = 69, 2000). Here, the overall mean hatching success estimated was 67.9 ± 36.7% ( n = 631, 2015–2022), contrasting with a significantly lower value on Meio in 2019 (11.9 ± 23.6%, n = 21), where clutch predation was high (83.7%, n = 98). Moderate to high clutch predation was also observed on Cavalos (36.0%, n = 64) and João Vieira (76.0%, n = 175). Cavalos and Meio likely face higher clutch flooding compared to Poilão. These findings, alongside observations of turtle exchanges between islands, may suggest a source-sink dynamic, where low reproductive output sink habitats (neighbouring islands) are utilized by migrants from Poilão (source), which currently offers the best conditions for clutch survival.

Histological biomarkers and microbiological parameters of an estuarine fish from the Brazilian Amazon coast as potential indicators of risk to human health - Gustavo Henrique Rodrigues Vale de Macedo; Jonatas da Silva Castro; Wanda Batista de Jesus; Ana Laíssa Pereira Costa; Rafael do Carmo Silva Ribeiro; Samanda de Jesus Roland Pires; Rita de Cássia Mendonça Miranda; Wellyson da Cunha Araújo Firmo; Luís Cláudio Nascimento da Silva; Raimundo Nonato Diniz Costa Filho; Raimunda Nonata Fortes Carvalho Neta; Débora Batista Pinheiro Pinheiro Sousa (Environmental Monitoring and Assessment, 2024)

Polycyclic aromatic hydrocarbons in seawater after the mysterious oil spill of 2019 on the Pernambuco coast, northeast Brazil - Thayane Cristina da S. Moreira; Ana Flávia B. de Oliveira; Pedro Gabriel C. de Lucena; Estefani S. do Nascimento; Leonardo M.F. de Almeida; Cristiane Maria V. de Araújo-Castro; Lino Angel V. Rojas; Gilvan T. Yogui; Eliete Zanardi-Lamardo; Jandyson M. Santos (Marine Pollution Bulletin, 2024)

Energy efficiency in winemaking industry: Challenges and opportunities - Manuela de Castro; José Baptista; Cristina Matos; António Valente; Ana Briga-Sá (Science of The Total Environment, 2024)

Bibliometric analysis of pumpkin seed proteins: A review of the multifunctional properties of their hydrolysates and future perspectives - Ana Flávia Coelho Pacheco; Flaviana Coelho Pacheco; Jeferson Silva Cunha; Fabio Ribeiro dos Santos; Jean Carlos Coelho Pacheco; Kely de Paula Correa; Wilson de Almeida Orlando Junior; Paulo Henrique Costa Paiva; Bruno Ricardo de Castro Leite Junior (Food Bioscience, 2024)

Blown film of PLA for packaging with green tea and fish industrial residues: An insight on their properties - Pedro V. Rodrigues; Ana B. Cunha; Mariana A. Andrade; Fernanda Vilarinho; Ana Vera Machado; M. Cidália R. Castro (Food Packaging and Shelf Life, 2024)

Potential availability of metals in anaerobic mono- and co-digestion of pig manure and maize - Hellen Luisa de Castro e Silva; Ana A. Robles-Aguilar; Çağrı Akyol; Bernard Willems; Erik Meers (Bioresource Technology, 2024)

Toxicity of butylone and its enantiomers to Daphnia magna and its degradation/toxicity potential using advanced oxidation technologies - Ana R. Carvalho; Ana M. Morão; Virgínia M.F. Gonçalves; Maria Elizabeth Tiritan; Ana M. Gorito; M.Fernando Pereira; Adrián M.T. Silva; Bruno B Castro; João S. Carrola; Maria M. Amorim; Ana R.L. Ribeiro; Cláudia Ribeiro (Aquatic Toxicology, 2024)

Resveratrol Reduces Neuroinflammation and Hippocampal Microglia Activation and Protects Against Impairment of Memory and Anxiety-Like Behavior in Experimental Cerebral Palsy - Caio Matheus Santos da Silva Calado; Raul Manhães-de-Castro; Sabrina da Conceição Pereira; Vanessa da Silva Souza; Leticia Nicoly Ferreira Barbosa; Osmar Henrique dos Santos Junior; Claudia Jacques Lagranha; Pedro Alberto Romero Juárez; Luz Torner; Omar Guzmán-Quevedo; Ana Elisa Toscano (Molecular Neurobiology, 2024)

Larvicidal and oviposition deterrent activity of sesquiterpenes from the red seaweed Laurencia johnstonii against Aedes aegypti - Ana Laura González-Castro; José Luis Torres-Estrada; Mauricio Muñoz-Ochoa (Journal of Applied Phycology, 2024)

Laboratory Test for Efficient and Cost-Effective Design of CPR Grouting to Improve Soft Soils - Guilherme Faria Souza Mussi de Andrade; Cid Almeida Dieguez; Alessandro Cirone; Bruno Teixeira Lima; Ana Cristina Castro Fontenla Sieira (Geotechnical and Geological Engineering, 2024)

Description of Corynebacterium hiratae sp. nov. isolated from a human tissue bone a novel member of Corynebacterium Genus - Lincoln de Oliveira Sant’Anna; Louisy Sanches dos Santos; Julianna Giordano Botelho Olivella; Mariana da Cruz Mota; Juliana Nunes Ramos; Paulo Victor Pereira Baio; Danilo Jobim Passos Gil da Rocha; Verônica Viana Vieira; Marisa Almuzara; Carlos Vay; Claudia Barberis; Thiago Luiz de Paula Castro; et al. (Brazilian Journal of Microbiology, 2024)

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

Coexisting in the Surf Zone: Age and Feeding Habits of the Spotted Seabass (Dicentrarchus punctatus) and European Seabass (Dicentrarchus labrax) on the Gulf of Cádiz Beaches (Southwest Iberian Peninsula) - Carlos Rodríguez-García; Ana Toro-Podadera; Jesica Sarmiento-Carbajal; Remedios Cabrera-Castro (Fishes, 2024)
Various commercial fish species utilize different coastal habitats as nurseries in their juvenile stages, with surf zones being particularly crucial due to the protection and abundant food resources they offer. Among the species that rely on these areas are the spotted seabass (Dicentrarchus punctatus) and the European seabass (Dicentrarchus labrax). This study aimed to investigate the age and feeding habits of surf zone specimens of these species and explore their environmental adaptations. The average size for D. punctatus was 16.94 ± 4.05 cm, and for D. labrax, it was 23.23 ± 6.30 cm. The length–weight relationship for D. punctatus was TW = 0.013*TL2.885 (parameter a: 95% CI: 0.012–0.014; parameter b: 95% CI: 2.854–2.917), and for D. labrax, it was TW = 0.008*TL3.095 (parameter a: 95% CI: 0.006–0.009; parameter b: 95% CI: 3.040–3.151). In both D. punctatus (79.20%) and D. labrax (75.92%), the predominant age classes were 1+ and 2+. Significant variations in age class abundance were observed in D. punctatus based on the time of day, lunar phase, and season, while D. labrax showed variations only by season. A diet analysis revealed that both species primarily consume mysids and fish, with D. punctatus showing dietary variations related to the time of day, lunar phase, and season, and D. labrax showing variations with the time of day and season.

Pharmacological hyperprolactinemia: a retrospective analysis of 501 hyperprolactinemia cases in primary care setting - Ana M. García Cano; Marta Rosillo; Ana Gómez Lozano; Lucía Jiménez Mendiguchía; Marta Marchán Pinedo; Argeme Rodríguez Torres; Marta Araujo-Castro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Differentiating Bagasse and Straw as Feedstocks for Sugarcane Cellulosic Ethanol: Insights from Pilot-Scale Pretreatments - Viviane M. Nascimento; Simone C. Nakanishi; Carlos Alberto de Oliveira Filho; Absai da Conceição Gomes; Aline Machado de Castro; Ana Paula Rodrigues Torres; Christian Alejandro Queipo; Danuza Nogueira Moyses; Felipe de Oliveira Brito; Luiz Fernando Martins Bandeira; Carlos Driemeier (BioEnergy Research, 2024)

Acaricidal activity of synthetic spilanthol derivative against ticks of medical and veterinary importance - Luis Adriano Anholeto; Guilherme Andrade Brancaglion; Danilo Martins dos Santos; Rafaela Tami Ikeda Kapritchkoff; Karina Neoob de Carvalho Castro; Kirley Marques Canuto; Rodney Alexandre Ferreira Rodrigues; Daniel Souza Correa; Ana Carolina de Souza Chagas; Julio Cezar Pastre (Veterinary Parasitology, 2024)

Bio-based superabsorbent hydrogels for nutrient release - Alessandra B. Ribeiro; Helena Moreira; Sofia I.A. Pereira; Mariana Godinho; Ana Sofia da Silva Sousa; Paula Castro; Carla F. Pereira; Francisca Casanova; Ricardo Freixo; Manuela E. Pintado; Óscar L. Ramos (Journal of Environmental Chemical Engineering, 2024)

Current trends and mismatches on fungicide use and assessment of the ecological effects in freshwater ecosystems - Ana Rita Pimentão; Ana Patrícia Cuco; Cláudia Pascoal; Fernanda Cássio; Bruno B. Castro (Environmental Pollution, 2024)

Local and NON-LOCAL source apportionment of black carbon and combustion generated PM2.5 - Jessika Rodríguez; Ana María Villalobos; Julio Castro-Molinare; Héctor Jorquera (Environmental Pollution, 2024)

Metataxonomy of acid mine drainage microbiomes from the Santa Catarina Carboniferous Basin (Southern Brazil) - Estácio Jussie Odisi; Robert Cardoso de Freitas; Diego Serrasol do Amaral; Saulo Britto da Silva; Marcus Adonai Castro da Silva; William de Oliveira Sant Ana; André Oliveira de Souza Lima; Leonardo Rubi Rörig (Extremophiles, 2024)

Database of immature stage traits of Ephemeroptera, Plecoptera, and Trichoptera (EPT) genera for the Amazon - Natália Beatriz Barros Santos; Gabriel Martins Cruz; Josinete Sampaio Monteles; Ana Paula Justino de Faria; Viviane Caetano Firmino; Yulie Shimano; Victor Rennan Santos Ferreira; Ana Luiza-Andrade; Frederico Falcão Salles; Diego M. P. Castro; Fábio B. Quinteiro; Lucas R. C. Lima; et al. (Aquatic Sciences, 2024)

Genetic implications of vein texture and mineralogy at the Au-bearing El Morado mining district, Sierras Pampeanas, San Juan, Argentina - Ana Cecilia Mugas Lobos; Gladis Noemí Palacio Balderramo; Brígida Castro de Machuca (Journal of South American Earth Sciences, 2024)

Iron and aluminum ore mining pollution induce oxidative and tissue damage on fruit-eating bats from the Atlantic Forest - Ana Luiza Fonseca Destro; Deborah Cardoso Gonçalves; Thaís da Silva Alves; Kemilli Pio Gregório; Vinicius Melo da Silva; Victor Rodrigues Santos; Olagide Wagner de Castro; Hernando Baggio Filho; Guilherme Siniciato Terra Garbino; Reggiani Vilela Gonçalves; Jerusa Maria de Oliveira; Mariella Bontempo Freitas (Journal of Hazardous Materials, 2024)

Pressurized liquid extraction of bioactive compounds from grape peel and application in pH-sensing carboxymethyl cellulose films: A promising material to monitor the freshness of pork and milk - Ana Paula Francisco; William Gustavo Sganzerla; Luiz Eduardo Nochi Castro; Tiago Linhares Cruz Tabosa Barroso; Aline Priscilla Gomes da Silva; Cleonice Gonçalves da Rosa; Michael Ramos Nunes; Tânia Forster-Carneiro; Mauricio A. Rostagno (Food Research International, 2024)

Structural changes induced by ultrasound in proteases and their consequences on the hydrolysis of pumpkin seed proteins and the multifunctional properties of hydrolysates - Ana Flávia Coelho Pacheco; Flaviana Coelho Pacheco; Gabriela Zinato Pereira; Paulo Henrique Costa Paiva; Carini Aparecida Lelis; Alline Artigiani Lima Tribst; Bruno Ricardo de Castro Leite Júnior (Food and Bioproducts Processing, 2024)

Erythrocyte alterations in specimens of Danio rerio caused by exposure to metformin - Pablo Americo Barbieri; Luara Lupepsa; Brennda Ribeiro Paupitz; Camila Oliveira de Andrade; Adriana Aparecida Sinópolis Gigliolli; Ana Luiza de Brito Portela-Castro; Ricardo Pereira Ribeiro; Carlos Alexandre Fernandes; Luciana Andreia Borin-Carvalho (Environmental Toxicology and Pharmacology, 2024)

Toxicity Assessment of the Biogenic Amines Cadaverine and Putrescine in Aquatic Organisms - Ana Paula Andrade Braga; José Henrique Vallim; Rodrigo Fernandes Castanha; Vera Lucia Scherholz Salgado de Castro; Maria Aparecida Marin-Morales (Water, Air, & Soil Pollution, 2024)

Environmental surface surveillance during a COVID-19 outbreak in a school community: implications for controlling indirect transmission - José Cherem; Ingrid Marciano Alvarenga; Ana Laura Ramos Mendes Coelho; Karla Silva Teixeira Souza; Denise Alvarenga Rocha; Pedro Henryque de Castro; Victor Satler Pylro; Joziana Muniz de Paiva Barçante (Brazilian Journal of Microbiology, 2024)

Phylogenetic evidence reshapes the taxonomy of Cacao and its allies (Theobroma and Herrania; Malvaceae, Byttnerioideae) - Matheus Colli-Silva; James Edward Richardson; Ana M. Bossa-Castro; José Rubens Pirani (Brittonia, 2024)
Theobroma (Malvaceae, Byttnerioideae), the cacao genus, has a taxonomic history spanning over two centuries. Currently, it comprises 23 species of trees from lowland forests from the Tropical Americas. Herrania , a closely related genus described later, includes 17 additional species commonly referred to as “wild cacaos.” Phylogenetic relationships and morphological circumscriptions between Theobroma and Herrania have been the subject of debate. While Herrania has traditionally been treated as a separate genus based on evident morphological differences in leaf and petal features, it shares similarities with Theobroma in terms of habit, inflorescence, and fruit types. Recent phylogenetic evidence, incorporating a broader taxonomic sampling and a total-evidence analysis, suggested that Theobroma is paraphyletic, with Herrania nested within it. This finding supports the restoration of a classical circumscription of Theobroma wherein Herrania is considered a section of the former genus. Here, we provide a detailed account of the taxonomic history at infrageneric levels and propose one new subsection, two names at new ranks (to better allocate the diversity within T. sect. Herrania ), and nine new combinations encompassing this expanded circumscription of Theobroma . In our study, we delimit Theobroma with forty species divided into six sections: T. sect. Glossopetalum (14 spp.), T. sect. Herrania (17 spp.), T. sect. Oreanthes (5 spp.), T. sect. Rhytidocarpus (1 sp.), T. sect. Telmatocarpus (2 spp.), and T. sect. Theobroma (1 sp.). Furthermore, we recognize three subsections within T. sect. Herrania . Alongside these newly proposed changes, we present a section-level identification key and provide diagnostic characters for each taxon.

Chemical characterization, antioxidant activity, and cytotoxicity of fatty acids methyl esters from Handroanthus impetiginosus (Mart. ex DC.) Mattos (Bignoniaceae) seeds - Luana Cristina Diniz Santos; Lucas Santos Azevedo; Ezequias Pessoa de Siqueira; Ana Hortência Fonsêca Castro; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2024)

On the role of system integration in plastic waste management - Rafael Castro-Amoedo; Julia Granacher; Ivan Kantor; Alina Dahmen; Ana Barbosa-Povoa; François Maréchal (Resources, Conservation and Recycling, 2024)

Co-fermentation of lactic acid bacteria and S. cerevisiae for the production of a probiotic beer: Survival and sensory and analytical characterization - Antonio Domínguez-Tornay; Ana Belén Díaz; Cristina Lasanta; Enrique Durán-Guerrero; Remedios Castro (Food Bioscience, 2024)

Microplastic Ingestion by Fish in a Neotropical Reservoir: Effects of Reservoir Dynamics and Fish Traits - Kátia Yasuko Yofukuji; Ana Lúcia Paz Cardozo; Lidiane Vizioli de Castro-Hoshino; Rosemara Fugi (Water, Air, & Soil Pollution, 2024)

Assessing toxicity mechanism of silver nanoparticles by using brine shrimp (Artemia salina) as model - Sergimar Kennedy de Paiva Pinheiro; Ana Kamila Medeiros Lima; Thaiz Batista Azevedo Rangel Miguel; Antonio Gomes Souza Filho; Odair Pastor Ferreira; Montcharles da Silva Pontes; Renato Grillo; Emilio de Castro Miguel (Chemosphere, 2024)

Feeding ecology of the African cuttlefish Sepia bertheloti (Cephalopoda: Sepiidae) in western Africa - Airam Guerra-Marrero; Ana Espino-Ruano; Lorena Couce-Montero; David Jiménez-Alvarado; José J. Castro (Fisheries Research, 2024)

Congruence between microsatellite loci, SNPs, and COI gene reveals a phylogeographic break in the southern Caribbean Sea: The case of West Indian top shell Cittarium pica (Gastropoda: Tegulidae) - Juan Carlos Narváez Barandica; Julian F. Quintero-Galvis; Ana Caruso Vargas; Germán Blanco Cervantes; Juan Carlos Aguirre Pabón; Lyda Castro García; Ricardo Betancur-R.; Arturo Acero P. (Fisheries Research, 2024)

Correction to: Household Salt Storage and Seasoning Consumption Are Predictors of Insufcient Iodine Status Among Pregnant Women in Southeastern Brazil - Ana Carolina Momentti; Mariana de Souza Macedo; Ana Flávia de Sousa Silva; Vanessa Cristina de Oliveira Souza; Fernando Barbosa Júnior; Sylvia do Carmo Castro Franceschini; Anderson Marliere Navarro (Biological Trace Element Research, 2024)

How complex is the hidden species diversity of the teleost Plotosus genus? - Elsa Froufe; André Gomes-dos-Santos; Ana Matos; Jonathan Wilson; Salman Malakpourkolbadinezhad; Daniel D. Pereira; Randal Singer; L. Filipe C. Castro (Ichthyological Research, 2024)
The striped eel catfish, Plotosus lineatus was first described by Thunberg in 1787 from the Indo-Pacific region in the East Indian Ocean. Since then, the species has been recorded in various marine and brackish habitats in Japan, southern Korea, the Ogasawara Islands, Australia, Lord Howe Island, Palau and Yap in Micronesia, East Africa to Samoa, Madagascar, Red Sea and the Persian Gulf. Occurrences of this species have also been registered in the Mediterranean Sea, a non-native location, indicating a possible biological invasion event. Despite its long history, the taxonomic status of the P. lineatus species complex remains puzzling and uncertain. Here, we analysed all the available mitochondrial cytochrome c oxidase subunit 1 sequences (NCBI and BOLD) from specimens covering the current known distribution range, in an attempt to clarify the evolutionary relationships of different lineages within this species. We deduce nine monophyletic Lineages - I–IX , of P. lineatus with Kimura-2P distances ranging from 2% to 16%, with a mean intraspecific distance of 6%. Strikingly, Lineage V is composed uniquely of Mediterranean-captured individuals, with an unknown evolutionary origin. These findings strongly suggest the need for a careful species taxonomic reassessment. Some Lineages are composed of individuals from specific geographic locations (e.g., Australia and Indonesia), while others include specimens from broader geographic areas (e.g., almost all Indo-Pacific coastline). Additionally, several deposited sequences are most likely the result of morphology-based misidentifications. Due to the biological invasive potential, as well as the use of the species as a valuable physiology model, the P. lineatus species complex requires further attention. Overall our study offers a clear framework for future comparative studies of striped eel catfish individuals captured from different ecosystems.

Assessment of the photoprotective potential and structural characterization of secondary metabolites of Antarctic fungus Arthrinium sp. - Ana Carolina Jordão; Gustavo Souza dos Santos; Thaiz Rodrigues Teixeira; Ana Júlia Pasuch Gluzezak; Clarissa Bechuate de Souza Azevedo; Karina de Castro Pereira; Ludmilla Tonani; Lorena Rigo Gaspar; Márcia Regina von Zeska Kress; Pio Colepicolo; Hosana Maria Debonsi (Archives of Microbiology, 2024)

Macromineral status, water balance and kidney function of goats fed two cactus cladodes species - Tomás Guilherme Pereira da Silva; Joana Albino Munhame; Ângela Maria Vieira Batista; Ihasmyn dos Santos Nunes; Ana Paula Silveira Paim; Pierre Castro Soares; Carlos Henrique da Silva Mendes; Adriana Guim; Dorgival Morais de Lima Júnior; Francisco Fernando Ramos de Carvalho (Small Ruminant Research, 2023)

The effect of a mining dam failure on the genetic diversity and population resilience of marine fishes along the eastern Brazilian coast - Juliana Beltramin De Biasi; Ricardo Marques Dias; Vinicius Castro Santos; Aline Meira Bonfim Mantellato; Ana Paula Cazerta Farro; Mauricio Hostim-Silva; Carlos Werner Hackradt; Fabiana Cézar Félix-Hackradt (Regional Studies in Marine Science, 2023)

Derivative of 7-hydroxycoumarin has antifungal potential against Candida species and low cytotoxicity against human cells: In silico studies and biological evaluation - Paula Lima Nogueira; Danielle da Nóbrega Alves; Palloma Christine Queiroga Gomes da Costa; Gleycyelly Rodrigues Araujo; Alana Rodrigues Ferreira; Ana Paula Gomes Moura Farias; Natália Ferreira de Sousa; Marianna Vieira Sobral; Damião Pergentino de Sousa; Marcus Tullius Scotti; Luciana Scotti; Ricardo Dias de Castro (Fungal Biology, 2023)

A ketogenic diet pattern during lactation increases visceral fat, glucose, and cholesterol levels and reduces beneficial fecal bacteria in dams and offspring - Jakssuel Sebastion Dantas Alves; Raul Manhães de-Castro; Henrique José Cavalcanti Bezerra; Bárbara Joacy Rodrigues Costa de-Santana; Elizabeth do Nascimento; Yohanna de Oliveira; Jade Morais Alves; José Luiz de Brito Alves; Marciane Magnani; Ana Elisa Toscano; Gisélia de Santana Muniz (Food Bioscience, 2023)

Metamodel to predict annual cooling thermal load for commercial, services and public buildings: A country-level approach to support energy efficiency regulation - Rayner Maurício e Silva Machado; Matheus Soares Geraldi; Mateus Bavaresco; Marcelo Salles Olinger; Larissa Pereira de Souza; Artur Martins Kamimura; Natasha Hansen Gapski; Tiago de Castro Quevedo; Liége Garlet; Ana Paula Melo; Roberto Lamberts (Energy and Buildings, 2023)

Household Salt Storage and Seasoning Consumption Are Predictors of Insufficient Iodine Status Among Pregnant Women in Southeastern Brazil - Ana Carolina Momentti; Mariana de Souza Macedo; Ana Flávia de Sousa Silva; Vanessa Cristina de Oliveira Souza; Fernando Barbosa Júnior; Sylvia do Carmo Castro Franceschini; Anderson Marliere Navarro (Biological Trace Element Research, 2023)

Report on the first two confirmed autochthonous cases of West Nile virus encephalitis in Catalonia, Spain - Carles García-Cervera; Simona Mihaela Iftimie; Miguel J. Martínez; Ana Vázquez González; Sandra Parra-Pérez; Laia Revuelta-López-Cordón; Joan Gil-Toral; Rosa Mercè Vileu Vallverdu; Ana Martínez Mateo; Ana Felisa López-Azcona; Isabel Pujol-Bajador; Frederic Ballester-Bastardie; et al. (Infectious Diseases, 2023)

Dietary oleic acid supplementation improves feed efficiency and modulates fatty acid profile and cell signaling pathway in European sea bass (Dicentrarchus labrax) juveniles fed high-lipid diets - Nicole Martins; Rui Magalhães; Lúcia Vieria; Ana Couto; Cláudia R. Serra; Margarida R.G. Maia; António J.M. Fonseca; Ana R.J. Cabrita; Pedro Pousão-Ferreira; Carolina Castro; Helena Peres; Aires Oliva-Teles (Aquaculture, 2023)

Understanding socioecological interaction networks in Marine Protected Areas to inform management - Silvia de Juan; Andres Ospina-Alvarez; Antonio J. Castro; Emilio Fernández; Gonzalo Méndez-Martínez; Jone Molina; Pablo Pita; Ana Ruiz-Frau; Gabriela de Abreu; Sebastian Villasante (Ocean & Coastal Management, 2023)

Contribution of the nursery areas to the major fishing grounds of the Brazilian sardine (Sardinella brasiliensis) in Southeastern Brazilian Bight inferred from otolith fingerprints - Rafael Schroeder; Paulo R. Schwingel; Richard Schwarz; Felippe A. Daros; Taynara P. Franco; Natasha T. Hoff; Ana Méndez Vicente; Jorge P. Castro; André M. Vaz-dos-Santos; Alberto T. Correia (Fisheries Research, 2023)

Brown Skua and south polar Skua (Aves: Stercorariidae) a hybridization case or same species? - Ana Carolina Marinho Mota; Erli Schneider Costa; João Paulo Machado Torres; Jansen de Araujo; Larissa Castro Tormena; Gisele Pires de Mendonça Dantas (Polar Biology, 2023)

Trophic ecology of common bottlenose dolphins in a pelagic insular environment inferred by stable isotopes - Ester Dias; Morgane Dromby; Rita Ferreira; Ágatha Gil; Raquel Tejerina; L. Filipe C. Castro; Massimiliano Rosso; Isabel Sousa-Pinto; Joel C. Hoffman; Maria A. Teodósio; Ana Dinis; Filipe Alves (Hydrobiologia, 2023)
The common bottlenose dolphin ( Tursiops truncatus ) is a top marine predator widely dispersed in coastal and pelagic habitats and with a generalist feeding behavior. Yet, information on the trophic ecology of animals inhabiting pelagic environments is still scarce. Using carbon (δ 13 C: 13 C/ 12 C) and nitrogen (δ 15 N: 15 N/ 14 N) stable isotope ratios, we identified and quantified the main groups of prey assimilated by bottlenose dolphins inhabiting an oceanic habitat (Madeira Island, East Atlantic). Bottlenose dolphins assimilated pelagic, schooling fish (such as blue jack mackerel, Trachurus picturatus ) and mesopelagic and demersal squids, which reinforces the pelagic dietary composition of insular/oceanic dolphins. Also, intra-seasonal differences were found in their stable isotope ratios, which suggest intraspecific variability in the feeding behavior among individuals living in the same area. Sex was not the main factor contributing to these differences, suggesting the lack of trophic niche segregation between adult males and females in this offshore environment. Nonetheless, further studies including different life stages and information on the ecophysiological requirements are necessary to disclose the factors responsible for the observed variability. This study showed that insular dolphins fed primarily on economically important pelagic prey, highlighting the need of developing management strategies that integrate conservation in fisheries plans.

Compatibility study of Duddingtonia flagrans conidia and its crude proteolytic extract - Debora Castro de Souza; Ana Carolina da Silva; Adriane Toledo da Silva; Clara Resende de Souza Castro; Laisa Bastos Albuquerque; Tiago Facury Moreira; Jackson Victor de Araújo; Fabio Ribeiro Braga; Filippe Elias de Freitas Soares (Veterinary Parasitology, 2023)

Seroprevalence and risk factors associated with caprine toxoplasmosis in the State of Goiás, Brazilian Savanna - Uilcimar Martins Arantes; Catarina Elízia Bernardino Rates de Moura; Maria Cristina de Oliveira; Caio Márcio de Oliveira Monteiro; Marcos Barcelos Café; Welber Daniel Zanetti Lopes; Valéria de Sá Jayme; Ana Maria de Castro; Jéssica Yonara de Souza; Geovana Batista de Campos; Vando Edésio Soares; Vanessa Silvestre Ferreira de Oliveira; et al. (Small Ruminant Research, 2023)

Effects of dietary xylanase plus β-glucanase levels on total-tract nutrient and energy digestibility and N balance of growing pigs fed diets containing corn distillers dried grains - Bryan Francisco Castro Dereck; Elias Giacomel; Caroline de Souza; Leonardo Willian de Freitas; Igor Willian Wrobel Straub; Anderson Corassa; Ana Paula Silva Ton; Franz Dias Gois; Jhunior Abrahan Marcía Fuentes; Maicon Sbardella (Tropical Animal Health and Production, 2023)

Age, growth, and population structure of the African cuttlefish Sepia bertheloti based on beak microstructure - Airam Guerra-Marrero; Aurora Bartolomé; Lorena Couce-Montero; Ana Espino-Ruano; David Jiménez-Alvarado; José J. Castro; Catalina Perales-Raya (Marine Biology, 2023)
In this study, we explored the feasibility of using the beaks of the African cuttlefish Sepia bertheloti for age estimation and growth analysis. The rostrum sagittal section (RSS) of the lower beak was the most suitable region in the species. It was applied in samples caught off Morocco and Guinea-Bissau between June 2018 and January 2020. A maximum life expectancy of around 14 months was observed (specifically 419 days for cuttlefishes from Morocco and 433 from Guinea-Bissau). The males presented greater longevity, as the maximum age of the females was between 9 and 11 months. Sepia bertheloti showed a negative allometric growth; however, the exponential model better describes each population growth. By sexes, the males of both locations followed an asymptotic growth model while the females exhibited a non-asymptotic growth. The growth rates were different between locations, with the highest values in Guinea-Bissau. The males, in turn, grew faster for both study locations. In Guinea-Bissau, these growth differences were influenced by the hatching season since individuals born between autumn and winter were the fastest-growing. Samples from Morocco did not show growth differences between the hatching season and other seasons. These results indicate that the RSS of lower beaks are suitable for estimating the age, growth pattern, and population structure of Sepia bertheloti .

In vitro anti-inflammatory activity and ameliorative effects on gastric ulcers of Licania rigida benth seed extract - Joanna de Freitas Rocha; Letícia de Castro Viana; Luiz Carlos Pereira Almeida Filho; Thiago Silva de Almeida; José Joaquim Lopes Neto; Veríssimo Vieira Neto; Pedro Matheus Sousa Tabosa; Diana Célia Sousa Nunes-Pinheiro; Virgínia Cláudia Carneiro Girão-Carmona; Ana Fontenele Urano Carvalho; Erika Freitas Mota (Inflammopharmacology, 2023)

Unintended consequences of valuing the contributions of non-native species: misguided conservation initiatives in a megadiverse region - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Carlos Bernardo Mascarenhas Alves; Marlene Sofia Arcifa; Valter M. Azevedo-Santos; Marcelo Fulgêncio Guedes Brito; Pâmella Silva de Brito; Paula Maria Gênova de Castro Campanha; Fernando Rogério Carvalho; Gabriel Costa da Costa; Mario Alberto Cozzuol; Almir Manoel Cunico; et al. (Biodiversity and Conservation, 2023)

Mobile terrestrial laser scanner vs. UAV photogrammetry to estimate woody crop canopy parameters – Part 1: Methodology and comparison in vineyards - Alexandre Escolà; José M. Peña; Francisca López-Granados; Joan R. Rosell-Polo; Ana I. de Castro; Eduard Gregorio; Francisco M. Jiménez-Brenes; Ricardo Sanz; Francesc Sebé; Jordi Llorens; Jorge Torres-Sánchez (Computers and Electronics in Agriculture, 2023)

Mobile terrestrial laser scanner vs. UAV photogrammetry to estimate woody crop canopy parameters – Part 2: Comparison for different crops and training systems - Jorge Torres-Sánchez; Alexandre Escolà; Ana Isabel de Castro; Francisca López-Granados; Joan R. Rosell-Polo; Francesc Sebé; Francisco Manuel Jiménez-Brenes; Ricardo Sanz; Eduard Gregorio; José M. Peña (Computers and Electronics in Agriculture, 2023)

Early Neolithic human remains from Galería del Sílex in Sierra de Atapuerca, Burgos, Spain - Antonio Molina-Almansa; Mercedes Conde-Valverde; Ana Isabel Ortega; Rebeca García-González; Laura Rodríguez; Alfonso Alday; Eneko Iriarte; Salvador Domingo; Juan Luis Arsuaga; José María Bermúdez de Castro; Eudald Carbonell; José Miguel Carretero; et al. (Quaternary Science Reviews, 2023)

Sustainable bioethanol production from first- and second-generation sugar-based feedstocks: Advanced bibliometric analysis - Cláudia Elisa César Guimarães; Francisco Simão Neto; Viviane de Castro Bizerra; Jean Gleison Andrade do Nascimento; Roberta Bussons Rodrigues Valério; Paulo Gonçalves de Sousa Junior; Ana Kátia de Sousa Braz; Rafael Leandro Fernandes Melo; Juliana de França Serpa; Rita Karolinny Chaves de Lima; Artemis Pessoa Guimarães; Maria Cristiane Martins de Souza; et al. (Bioresource Technology Reports, 2023)

The Landscape of Neutralizing Monoclonal Antibodies (nAbs) for Treatment and Prevention of COVID-19 - Aline de Almeida Oliveira; Diana Praia Borges Freire; Ana Rodrigues de Andrade; Amanda de Miranda Marques; Luciana da Silva Madeira; José Procópio Moreno Senna; Ivna Alana Freitas Brasileiro da Silveira; Beatriz de Castro Fialho (Journal of Pharmaceutical Innovation, 2023)
Purpose After nearly 3 years of the COVID-19 pandemic, even though a vast body of knowledge and products (including vaccines and treatments) have been developed and disseminated, the virus is still evolving and new variants arising. Consequently, thousands of lives continue to be lost. Neutralizing monoclonal antibodies (nAbs) are promising drugs that emerged to treat SARS-CoV-2. In the uncertainty of the current situation, there is the question of whether organizations should continue to invest in this technology. To help decision-making in scientifical and pharmaceutical organizations, it is of major importance to monitor the development of products and technologies. Therefore, the aim of this study is analyze the landscape of nAbs for COVID-19. Methods The scenario of 473 biotherapeutics focusing on nAbs was evaluated using foresight techniques and a review of literature. Data were obtained from structured and semi-structured databases and processed for treatment, cleaning, consistency, validation, and enrichment. Results We identified 227 nAbs and performed an extensive literature review of 16 nAbs in late clinical development, including development technologies, responses to variants of concern (VOCs), manufacturing, and clinical aspects. Conclusions Even though the emergence of new VOCs is a threat to the effectiveness of this treatment, demanding constant genomic surveillance, the use of nAbs to treat and prevent COVID-19 will probably continue to be relevant due to excellent safety profiles and the possibility of immediate immunity transfer, especially in patients showing inadequate immunological response to vaccination. Therefore, we suggest that organizations should keep investing in improvements in this technology.

In Silico Simulations and Functional Cell Studies Evidence Similar Potency and Distinct Binding of Pacific and Caribbean Ciguatoxins - Sandra Raposo-García; David Castro; Emilio Lence; Pablo Estévez; José Manuel Leão; Concepción González-Bello; Ana Gago-Martínez; M. Carmen Louzao; Carmen Vale; Luis M. Botana (Exposure and Health, 2023)
Ciguatoxins (CTX) cause ciguatera poisoning, which is the most common reported human food poisoning related to natural marine toxins. Pacific ciguatoxins are the most abundant and studied CTX analogues; however, the growing distribution of Caribbean analogues and the limited data available on their biological effects make necessary to re-evaluate their relative potency. For decades, the guidelines established by regulatory agencies have assumed that the potency of the Caribbean CTXs were tenfold lower than the Pacific CTXs. We present here an integrated study involving Neuro-2a cells (the method used worldwide to test ciguatoxins), electrophysiological assays, and in silico simulations that evidence the similar cytotoxicity of Caribbean and Pacific ciguatoxins and their asymmetry binding within sodium channels. The binding mode of the toxins was first explored by molecular docking using the GOLD program and the resulting binary complexes were further studied by Molecular Dynamics simulation studies using the molecular mechanics force field AMBER. The simulation studies explain their distinct impact on the activation potential of the channel as experimentally observed and provide a detailed picture of the effects caused by these toxins on an atomic scale. Graphical Abstract

A general overview of the multifactorial adaptation to cold: biochemical mechanisms and strategies - Ana Ramón; Adriana Esteves; Carolina Villadóniga; Cora Chalar; Susana Castro-Sowinski (Brazilian Journal of Microbiology, 2023)

Characteristics of Streptococcus agalactiae belonging to CC103 clone circulating among dairy herds and pregnant women in Brazil - Leandro Corrêa Simões; Flávio Gimenis Fernandes; Ivi Cristina Menezes de Oliveira; Ana Beatriz de Almeida Corrêa; Natália Silva Costa; Laura Maria Andrade Oliveira; Ana Caroline Nunes Botelho; Sergio Eduardo Longo Fracalanzza; Lucia Martins Teixeira; Tatiana Castro Abreu Pinto (Brazilian Journal of Microbiology, 2023)

Influence of seasonal variation to the population growth and ecophysiology of Typha domingensis (Typhaceae) - Yasmini da Cunha Cruz; Ana Lívia Martins Scarpa; Alejandro Sandria Díaz; Marcio Paulo Pereira; Evaristo Mauro de Castro; Fabricio José Pereira (Journal of Plant Research, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Development of conversion factors to estimate the concentrations of heavy metals in manure-derived digestates - Hellen Luisa de Castro e Silva; Ivona Sigurnjak; Ana Robles-Aguilar; Anne Adriaens; Erik Meers (Waste Management, 2023)

Long-term e-cigarette aerosol exposure causes pulmonary emphysema in adult female and male mice - Andrea Jazel Rodriguez-Herrera; Ana Beatriz Farias de Souza; Thalles de Freitas Castro; Pedro Alves Machado-Junior; Elena Cecilia Marcano-Gomez; Tatiana Prata Menezes; Maria Laura da Cruz Castro; André Talvani; Daniela Caldeira Costa; Sílvia Dantas Cangussú; Frank Silva Bezerra (Regulatory Toxicology and Pharmacology, 2023)

Antibiotics reduce Pocillopora coral‐associated bacteria diversity, decrease holobiont oxygen consumption and activate immune gene expression - Michael T. Connelly; Grace Snyder; Ana M. Palacio‐Castro; Phillip R. Gillette; Andrew C. Baker; Nikki Traylor‐Knowles (Molecular Ecology, 2023)
Corals are important models for understanding invertebrate host–microbe interactions; however, to fully discern mechanisms involved in these relationships, experimental approaches for manipulating coral–bacteria associations are needed. Coral‐associated bacteria affect holobiont health via nutrient cycling, metabolic exchanges and pathogen exclusion, yet it is not fully understood how bacterial community shifts affect holobiont health and physiology. In this study, a combination of antibiotics (ampicillin, streptomycin and ciprofloxacin) was used to disrupt the bacterial communities of 14 colonies of the reef framework‐building corals Pocillopora meandrina and P . verrucosa, originally collected from Panama and hosting diverse algal symbionts (family Symbiodiniaceae ). Symbiodiniaceae photochemical efficiencies and holobiont oxygen consumption (as proxies for coral health) were measured throughout a 5‐day exposure. Antibiotics altered bacterial community composition and reduced alpha and beta diversity, however, several bacteria persisted, leading to the hypothesis that these bacteria are either antibiotics resistant or occupy internal niches that are shielded from antibiotics. While antibiotics did not affect Symbiodiniaceae photochemical efficiency, antibiotics‐treated corals had lower oxygen consumption rates. RNAseq revealed that antibiotics increased expression of Pocillopora immunity and stress response genes at the expense of cellular maintenance and metabolism functions. Together, these results reveal that antibiotic disruption of corals' native bacteria negatively impacts holobiont health by decreasing oxygen consumption and activating host immunity without directly impairing Symbiodiniaceae photosynthesis, underscoring the critical role of coral‐associated bacteria in holobiont health. They also provide a baseline for future experiments that manipulate Pocillopora corals' symbioses by first reducing the diversity and complexity of coral‐associated bacteria.

First record of partial albinism in the critically endangered Angelshark ( Squatina squatina ) (Linnaeus, 1758) - David Jimenez‐Alvarado; Eva Meyers; Airam Guerra‐Marrero; Ana Espino‐Ruano; Lorena Couce‐Montero; Joanna Barker; Michael Sealey; Héctor Toledo; Belén Caro; Charlotte Pike; David M.P. Jacoby; Lucy Mead; et al. (Journal of Fish Biology, 2023)
We report the first case of partial albinism in the Critically Endangered angelshark, Squatina squatina . The encounter with this specimen took place while SCUBA diving on the beach of Tufia, located on the east coast of the island of Gran Canaria on 2 April 2021. This is also the first confirmed finding of an albino elasmobranch specimen in the Canary Island archipelago.

Effect of kombucha intake on the gut microbiota and obesity-related comorbidities: A systematic review - Mirian Aparecida de Campos Costa; Darlene Larissa de Souza Vilela; Gabriela Macedo Fraiz; Isabelle Lima Lopes; Ana Iris Mendes Coelho; Luiza Carla Vidigal Castro; José Guilherme Prado Martin (Critical Reviews in Food Science and Nutrition, 2023)

Testing differences of marine non-indigenous species diversity across Macaronesia using a standardised approach - Nuno Castro; Ignacio Gestoso; Patrício Ramalhosa; Evandro Lopes; Corrine Almeida; Ana Costa; Manuela Parente; Eva Cacabelos; Rogélio Herrera; José L. Costa; João Canning-Clode (Marine Pollution Bulletin, 2023)

Revegetation through seeding or planting: A worldwide systematic map - Alba Lázaro-González; Enrique Andivia; Arndt Hampe; Shun Hasegawa; Raffaella Marzano; Ana M.C. Santos; Jorge Castro; Alexandro B. Leverkus (Journal of Environmental Management, 2023)

Assessment of drying conditions for storage of a yeast-based decolorization solution for application in textile industrial wastewater treatment plants - Marta Mendes; Ana C. Cassoni; Soraia Alves; Patrícia Moreira; Paula ML. Castro; Manuela E. Pintado (Fungal Biology, 2023)

Prevalence of latent Mycobacterium tuberculosis infection in hematopoietic stem cell transplantation comparing tuberculin skin test and interferon-gamma release assay - Victor A C Castro-Lima; Ana Paula T Santos; Priscila T Musqueira; Natalya Z Maluf; Jéssica F Ramos; Lívia Mariano; Vanderson Rocha; Silvia F Costa (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Combining biosolid and mineral sources of phosphorus and potassium in organomineral fertilizers influences the dynamics and efficiency of nutrient release - Julia Barra Netto-Ferreira; Fernanda Palmeira Gabetto; Ana Carolina Muniz de Araujo; Ricardo de Castro Dias; Nelson Moura Brasil do Amaral Sobrinho; Everaldo Zonta (Environmental Geochemistry and Health, 2023)

Anticancer effects of phytol against Sarcoma (S-180) and Human Leukemic (HL-60) cancer cells - Marcus Vinícius Oliveira Barros de Alencar; Muhammad Torequl Islam; Ana Maria Oliveira Ferreira da Mata; Antonielly Campinho dos Reis; Rosália Maria Torres de Lima; José Roberto de Oliveira Ferreira; João Marcelo de Castro e Sousa; Paulo Michel Pinheiro Ferreira; Ana Amélia de Carvalho Melo-Cavalcante; Abdur Rauf; Hassan A. Hemeg; Khalaf F. Alsharif; et al. (Environmental Science and Pollution Research, 2023)

Occurrence of bean-associated cytorhabdovirus and cowpea mild mottle virus infecting cultivated and wild Passiflora spp. in Brazil - Andreza Henrique Vidal; Gustavo Pereira Felix; Emanuel Felipe Medeiros Abreu; Bruna Pinheiro-Lima; Monique Jacob Xavier Vianna; Isadora Nogueira; Ana Clara Rodrigues Abreu; Marcio Martinello Sanches; José Leonardo Santos-Jiménez; Raul Castro Carriello Rosa; Maitê Freitas Silva Vaslin; Fábio Gelape Faleiro; et al. (Crop Protection, 2023)

Rajids ovipositing on marine litter: A potential threat to their survival - Miguel Valderrama-Herrera; Sara Amada Cardenas; Carlos Calvo-Mac; Renzo Gustavo Celi-Vértiz; Valeria Liz Chumpitaz-Levano; Walter Eduardo Flores-Miranda; Zoila M.T. Lopez-Tirado; Mariana Molina-Alvarez; Diana N. Rubio-Cheon; Maryalejandra Trucios-Castro; Melisa D. Fernández Severini; Ana D. Forero López; et al. (Marine Pollution Bulletin, 2023)

Genome-wide comparative analysis of Glycolate oxidase (GOX) gene family in plants - Érica Monik Silva Roque; Felipe de Castro Teixeira; Alex Martins de Aguiar; Victor Breno Faustino Bezerra; Ana Carolina Moreira da Costa; Sâmia Alves Silva; Ana Luiza Sobral Paiva; Humberto Henrique de Carvalho; Murilo Siqueira Alves (Plant Gene, 2023)

Epigenetic regulation of collagen in the mare's placenta: putative relationship with maternal age - Manuel A. Vasconcelos; Yat Wong; Joana Alpoim-Moreira; Maria R. Rebordão; Maria J. Fradinho; Ana L. Costa; Miguel Bliebernicht; Fidel O. Castro; Elisabete Silva; Graça M. Ferreira-Dias (Journal of Equine Veterinary Science, 2023)

Contribution of TGFß and of a cocktail of TGFß and the pro-inflammatory cytokines IL-1, IL- 6 and TNFα to the establishment of a fibrotic phenotype in endometrial fibroblasts of mares - Yat S. Wong; Pamela Poblete; Lidice Mendez; Ana C. Mancanares; Lleretny Rodriguez-Alvarez; Fernando E. Saravia; Fidel O. Castro (Journal of Equine Veterinary Science, 2023)

Efficacy of fungoid chitosans from Aspergillus niger and Agaricus bisporus in controlling the oxidative browning of model white wines - Federico Baris; Antonio Castro Marín; Ana Cristina De Aguiar Saldanha Pinheiro; Silvia Tappi; Fabio Chinnici (Innovative Food Science & Emerging Technologies, 2023)

Chemical profile, antioxidant potential and toxicity of Smilax brasiliensis Sprengel (Smilacaceae) stems - Izabela Caputo Assis Silva; Lucas Santos Azevedo; Ana Hortência Fonsêca Castro; Katyuce de Souza Farias; Vanessa Samúdio Santos Zanuncio; Denise Brentan Silva; Luciana Alves Rodrigues dos Santos Lima (Food Research International, 2023)

Selection of Brucella abortus mimetic epitopes for fast diagnostic purposes in cattle - Fabiana de Almeida Araújo Santos; Patrícia Tiemi Fujimura; Emília Rezende Vaz; Ana Cristina Honorato de Castro; Ana Graci Brito-Madurro; Vivian Alonso-Goulart; Luciana Machado Bastos; Belchiolina Beatriz Fonseca; Anna Monteiro Correia Lima; Luiz Ricardo Goulart (Veterinary Research Communications, 2023)

Thermoregulatory capacity of goat kids from birth to weaning in a dry hot climate - Mateus Alves Gonçalves; Robson Mateus Freitas Silveira; Maria Samires Martins Castro; Ana Paula Araújo do Nascimento; Francisca Méssia Pereira Martins; Ana Sancha Malveira Batista; Josiel Ferreira; Débora Andreia Evangelista Façanha; Carlos Tadeu dos Santos Dias; Angela Maria de Vasconcelos (Tropical Animal Health and Production, 2023)

Bifidobacterium lactis CCT 7858 Improves Gastrointestinal Symptoms by Antibiotics Treatment: a Double-Blind, Randomized, Placebo-Controlled Trial - Monique Michels; Emily Córneo; Luana Cucker; Carla Sasso Simon; Gabriel Fernandes Alves de Jesus; Carolina Michels; Kristian Madeira; Ana Paula Voytena; Marina Rossetto; Fernanda Ramlov; Danusa de Castro Damásio; Felipe Dal-Pizzol (Probiotics and Antimicrobial Proteins, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Effect of TiO2 Microparticles in Lettuce (Lactuca sativa L.) Seeds and Seedlings - Ana Kamila Medeiros Lima; Alexya Vitória Felix Carvalho; Sergimar Kennedy de Paiva Pinheiro; Yan Torres; Thaiz Batista Azevedo Rangel Miguel; Saulo Fernandes Pireda; Pierre Basílio Almeida Fechine; Laís Gomes Fregolente; Emilio de Castro Miguel (Bulletin of Environmental Contamination and Toxicology, 2023)

Cryopreservation modifies the distribution of the prostate-derived lectin SL15 on the llama (Lama glama) sperm - Renato Zampini; Ximena A. Castro-González; Micaela Scandura; Luciana M. Sari; Ana V. Diaz; Alfredo Martin; Martin E. Argañaraz; Silvana A. Apichela (Theriogenology, 2023)

Critical Pronociceptive Role of Family 2 Voltage-Gated Calcium Channels in a Novel Mouse Model of HIV-Associated Sensory Neuropathy - Debora Denardin Lückemeyer; Arthur Silveira Prudente; Marcella de Amorim Ferreira; Ana Merian da Silva; Raquel Tonello; Sérgio José Macedo Junior; Camila Sant’ Helena do Prado; Célio José de Castro Júnior; Marcus Vinicius Gomez; João Batista Calixto; Juliano Ferreira (Molecular Neurobiology, 2023)

Addition of iron ore tailings to increase the efficiency of anaerobic digestion of swine manure: ecotoxicological and elemental analyses in digestates - Hellen Luisa de Castro e Silva; Regina Mambeli Barros; Ivan Felipe Silva dos Santos; Marco Aurélio Kondracki de Alcântara; Electo Eduardo Silva Lora; Hélcio José Izário Filho; Vanessa Bezerra de Menezes Oliveira; Ana Lucia Fonseca; Dayane de Oliveira; Maria Carolina Triques; Gabriel Caracciolo Koenigkam de Oliveira (Environment, Development and Sustainability, 2023)

Oral formulation of Wnt inhibitor complex reduces inflammation and fibrosis in intraperitoneal implants in vivo - Ana Luíza de Castro Santos; Natália Jordana Alves da Silva; Celso Tarso Rodrigues Viana; Letícia Cristine Cardoso dos Santos; Gabriel Henrique Costa da Silva; Sérgio Ricardo Aluotto Scalzo Júnior; Pedro Augusto Carvalho Costa; Walison Nunes da Silva; Itamar Couto Guedes de Jesus; Alexander Birbrair; Mariana T. Q. de Magalhães; Frédéric Frézard; et al. (Drug Delivery and Translational Research, 2023)

Assessment of eutrophication from phosphorus remobilization after resuspension of coastal sediments from an urban tropical estuary - Christiane do N. Monte; Ana Paula de Castro Rodrigues; Matheus Cavalcante Silva; Luana J. S. Ferreira; Gustavo Monte; Carla Semiramis Silveira; Renato Campello Cordeiro; Wilson Machado (Environmental Science and Pollution Research, 2023)

Novel clinical and immunological features associated with persistent post-acute sequelae of COVID-19 after six months of follow-up: a pilot study - Jiram Torres-Ruiz; Julieta Lomelín-Gascón; Jaquelin Lira Luna; Ana Sofia Vargas- Castro; Alfredo Pérez-Fragoso; Miroslava Nuñez-Aguirre; Beatriz Alcalá-Carmona; Abdiel Absalón-Aguilar; Jennifer T. Balderas-Miranda; José Luis Maravillas-Montero; Nancy R. Mejía-Domínguez; Carlos Núñez-Álvarez; et al. (Infectious Diseases, 2023)

Bioremediation of coastal aquaculture effluents spiked with florfenicol using microalgae-based granular sludge – a promising solution for recirculating aquaculture systems - Ana S. Oliveira; Marta Alves; Frederico Leitão; Marta Tacão; Isabel Henriques; Paula M.L. Castro; Catarina L. Amorim (Water Research, 2023)

Effect of diets containing cactus cladodes on physical and histomorphometric parameters, and bone mineral content of feedlot lambs and goats - Tomás Guilherme Pereira da Silva; Levi Auto Lopes; Joana Albino Munhame; Ângela Maria Vieira Batista; Francisco de Assis Leite Souza; Maria Edna Gomes de Barros; Ihasmyn dos Santos Nunes; Ana Paula Silveira Paim; Pierre Castro Soares; Francisco Fernando Ramos de Carvalho (Small Ruminant Research, 2023)

Evaluating different levels of papain as texture modifying agent in bovine meat loaf containing transglutaminase - Wanessa Oliveira Ribeiro; Maristela Midori Ozaki; Mirian dos Santos; Ruann Janser Soares de Castro; Helia Harumi Sato; Ana Karoline Ferreira Ignácio Câmara; Andrea Paola Rodríguez; Paulo Cezar Bastianello Campagnol; Marise Aparecida Rodrigues Pollonio (Meat Science, 2023)

Over-expression of the barley Phytoglobin 1 (HvPgb1) evokes leaf-specific transcriptional responses during root waterlogging - Robert D. Hill; James de Castro; Mohammed M. Mira; Abir U. Igamberdiev; Kim H. Hebelstrup; Sylvie Renault; Wayne Xu; Ana Badea; Claudio Stasolla (Journal of Plant Physiology, 2023)

Organic fragments of k-carrageenan, lipids and peptides plus K-rich inorganic fraction in Kappaphycus alvarezii biomass are responsible for growth stimulus in rice plant when applied both foliar and root pathway - Tadeu Augusto van Tol de Castro; Orlando Carlos Huertas Tavares; Danielle França de Oliveira Torchia; Hellen Fernanda Oliveira da Silva; Octávio Vioratti Telles de Moura; Raphaella Esterque Cantarino; Samuel de Abreu Lopes; Carolina Vieira Viêgas; Ana Lucia do Amaral Vendramini; Leandro Azevedo Santos; Ricardo Luiz Louro Berbara; Andrés Calderín García (Algal Research, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Evaluation of lead exposition length on the liver and intestinal histoarchitecture of eared dove (Zenaida auriculata) - Verónica P. Filippa; Emilce L. Tabares; Ana C. Castro-Guijarro; Juan G. Chediack; Fabricio D. Cid (Environmental Science and Pollution Research, 2023)

Contribution to the knowledge of genome size variation in Calendula L. (Asteraceae) with special focus on the SW Mediterranean region - Ana Carla Gonçalves; Helena Oliveira; João Loureiro; Sílvia Castro; Maria Eduarda Fidalgo; Teresa Ribeiro; Ahmed Ouhammoud; Rachid Amirouche; Leonor Morais-Cecílio; Conceição Santos; Paulo Silveira (Plant Biosystems, 2023)

Toxic plants from the perspective of a “Quilombola” community in the Cerrado region of Brazil - Ricardo de Castro Santos Paim; Luiza Gabriella Ferreira de Paula; Débora Moreira Soares; Tarik Fernandes Gonçalves Rocha; Amanda Lopes Ribeiro; Natália Barros; Fabrício Carrião dos Santos; Heleno Dias Ferreira; Vera Lúcia Gomes-Klein; Benito Soto-Blanco; José Paes de Oliveira-Filho; Paulo Henrique Jorge da Cunha; et al. (Toxicon, 2023)

Impact of gastrointestinal digestion simulation on brewer’s spent grain green extracts and their prebiotic activity - Teresa Bonifácio-Lopes; Luís M. G. Castro; Ana Vilas-Boas; Débora Campos; José A. Teixeira; Manuela Pintado (Food Research International, 2023)

Effect of anthropic disturbances on the activity pattern of two generalist mesocarnivores inhabiting Mediterranean forestry plantations - Daniela F. Teixeira; Guilherme Ares-Pereira; Cláudia Camarinha; Cátia Lima; Ana Magalhães; Guilherme Castro; Carlos Fonseca; Luís Miguel Rosalino (Biodiversity and Conservation, 2023)
Humans have been altering the Mediterranean landscapes for millennia. To diminish the probability of encounters with domestic animals, humans and their activities, many species adjust their behavior to become more nocturnal. Even habitat-generalist species, such as red fox and stone marten that are somehow tolerant to environmental changes, might be affected by anthropic disturbances. Nevertheless, only a small number of studies were implemented in Iberia targeting these mesocarnivores’ activity patterns, and fewer have assessed the temporal ecology of these species in Eucalyptus plantations, the current main forest cover in Portugal. Based on camera traps, we aimed to analyze: 1) the temporal and spatio-temporal activity patterns of red fox and stone marten; and 2) how they are affected by distinct human disturbances (i.e., humans, livestock, dogs, plantations, and hunting). Foxes presented a higher crepuscular activity, while martens were entirely nocturnal, suggesting some avoidance behavior. Both mesocarnivores showed a higher overlap with dogs’ activity than with humans or livestock. Foxes’ activity patterns vary between seasons and habitats but were not influenced by the hunting period. Results suggest that both mesocarnivores, besides setting apart their activity from humans related disturbances, also show a tendency to temporally avoid each other. While the increase of nocturnality may indicate an anthropic disturbance impact, a reduction of activity overlap between mesocarnivores may be a strategy to reduce competition. These results may help support the sustainable management of landscapes by highlighting critical periods where activity overlaps may occur, and thus the anthropic impacts on wildlife are higher.

Oxidative stress mediated cytogenotoxicological effects of phytol in wistar albino rats - Marcus Vinícius Oliveira Barros de Alencar; Muhammad Torequl Islam; Antonielly Campinho dos Reis; José Victor de Oliveira Santos; Adriana Maria Viana Nunes; Felipe Cavalcante Carneiro da Silva; Keylla da Conceição Machado; João Marcelo de Castro e Sousa; Željko Reiner; Miquel Martorell; Sharmila Fagoonee; Javad Sharifi-Rad; et al. (Advances in Traditional Medicine, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Vegetative reproduction in Pinguicula heterophylla (Lentibulariaceae): differential role of aboveground and belowground biomass - Ana Luz Mendoza-Pérez; Dulce María Figueroa-Castro (Brazilian Journal of Botany, 2023)

In vitro effect of the iron chelator deferiprone on the antimicrobial susceptibility and biofilms of Burkholderia pseudomallei - Glaucia Morgana de Melo Guedes; Késia Veras Costa Ribeiro; Emanuela Silva de Araújo; Vinícius Carvalho Pereira; Ana Carla de Castro Freitas Soares; Alyne Soares Freitas; Rossana de Aguiar Cordeiro; José Júlio Costa Sidrim; Marcos Fábio Gadelha Rocha; Débora de Souza Collares Maia Castelo-Branco (Biofouling, 2023)

Genotoxicity and cytotoxicity of textile production effluents, before and after Bacillus subitilis bioremediation, in Astyanax lacustris (Pisces, Characidae) - Josiane Rodrigues Rocha da Silva; Angelivia Gregorio; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

A social study of the technicians dealing with refrigerant gases: Diagnosis of the behaviours, knowledge and importance attributed to the F-gases - Graça Martinho; Paulo J. Castro; Pedro Santos; Ana Alves; João M.M. Araújo; Ana B. Pereiro (International Journal of Refrigeration, 2023)

Age validation in early stages of Sepia officinalis from beak microstructure - Airam Guerra-Marrero; Catalina Perales-Raya; Fedor Lishchenko; Ana Espino-Ruano; David Jiménez-Alvarado; Lorena Couce-Montero; José J. Castro (Marine Biology, 2023)
This is the first study addressing validation of the early growth stages (including the first increment) in the beaks of juvenile cuttlefishes. The age validation in juveniles of Sepia officinalis was performed by comparison of the number of increments observed in the rostrum surface of lower jaws with their true age. A total of 159 individuals were reared at 18 ºC and 21 ºC, with ages up to 31 days from hatching. The number of growth increments in the beak was counted and contrasted with the days of life after hatching, validating the hypothesis of one increment of growth corresponding to one day of life. The mean coefficient of variation between readings (measuring precision) was 2.95 ± 5.98%. The growth of the reading area (rostrum surface) and the periodicity of increment deposition showed no difference between the two culture temperatures and therefore daily deposition was confirmed at these temperatures.

Structural parameters of biofilm and bacterioplankton are better indicators of urbanization than photosynthetic functional parameters in low-order streams - Rocío Gorbarán; Carolina Vilches; María Carolina Rodríguez Castro; Adonis Giorgi; Ana Torremorell (Hydrobiologia, 2023)

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Plastic ingestion by carnivore fish in a neotropical floodplain: seasonal and interspecific variations - Ana Lúcia Paz Cardozo; Kátia Yasuko Yofukuji; Ranulfo Combuca da Silva Júnior; Lidiane Vizioli de Castro-Hoshino; Rosemara Fugi (Environmental Science and Pollution Research, 2023)

Assessment of the environmental acceptability of potential artificial reef materials using two ecotoxicity tests: Luminescent bacteria and sea urchin embryogenesis - Jorge Santos; Eva Cifrian; Araceli Rodriguez-Romero; Adrian I. Yoris-Nobile; Elena Blanco-Fernandez; Daniel Castro-Fresno; Ana Andres (Chemosphere, 2023)

Particulate matter fingerprints in biofuel impacted tunnels in South America's largest metropolitan area - Guilherme Martins Pereira; Thiago Nogueira; Leonardo Yoshiaki Kamigauti; Djacinto Monteiro dos Santos; Emerson Queiroz Mota Nascimento; José Vinicius Martins; Ana Vicente; Paulo Artaxo; Célia Alves; Pérola de Castro Vasconcellos; Maria de Fatima Andrade (Science of The Total Environment, 2023)

Corrigendum to “Relationship between thermal environment, thermoregulatory responses and energy metabolism in goats: A comprehensive review” Journal of Thermal Biology 109 (2022) 103324] - Ana Rebeca Castro Lima; Robson Mateus Freitas Silveira; Maria Samires Martins Castro; Laura Bertolaso De Vecchi; Angélica Santos Rabelo de Souza Bahia; Thaise Pinto de Melo; Márcia Helena Machado da Rocha Fernandes; Kléber Tomás Resende (Journal of Thermal Biology, 2023)

Bioaccessibility of phenolic compounds in L. varieties and Nied. after gastrointestinal digestion - Alba C. Durán-Castañeda; Alicia P. Cardenas-Castro; Jara Pérez-Jiménez; Ana M. Pérez-Carvajal; Jorge A. Sánchez-Burgos; Raquel Mateos; Sonia G. Sáyago-Ayerdi (Food Chemistry, 2023)

Elevation drives taxonomic, functional and phylogenetic β‐diversity of phyllostomid bats in the Amazon biome - William Douglas Carvalho; Isadora E. Fluck; Isaí Jorge de Castro; Renato Richard Hilário; Ana Carolina Moreira Martins; José Júlio de Toledo; Bruna da Silva Xavier; Cristian Dambros; Paulo E. D. Bobrowiec (Journal of Biogeography, 2023)
Aim We evaluated the relative importance of geographical and environment variables for taxonomic, phylogenetic and functional β‐diversity of phyllostomid bats along the entire Amazon biome and specifically in the lowlands. Location Amazon biome. Taxon Chiroptera. Methods We carried out a bibliographic review and compiled a wide and unprecedented database of 106 phyllostomid bat species at 102 sites throughout the Amazon biome. For all possible pairs of sites in both datasets, we estimated the Jaccard pairwise dissimilarity, that is, β‐diversity, considering its three dimensions—taxonomic, phylogenetic and functional—for its two components—turnover (substitution of species) and differences in species richness. The association between dissimilarity measurements and geographical and environment variables was assessed using multiple regressions on distance matrices (MRM). Results We found that turnover and differences in species richness had similar contributions to the taxonomic β‐diversity. However, for phylogenetic and functional β‐diversity, lineages and functions richness differences contribute slightly more than turnover for total β‐diversity. In the lowlands, species, lineages and functions richness differences were slightly higher than turnover for all diversity dimensions. When accounting for all the sites, elevation was the main predictor of phyllostomid bats' taxonomic, phylogenetic and functional turnover. For lowland sites, ecoregions was the main (but relatively weak) predictor associated with all β‐diversity dimensions. Main conclusions Analysis of filtering sites according to elevation revealed that species in the Amazonian lowlands are taxonomically and phylogenetically different from species in the Andes, and present taxonomic, phylogenetic and functional redundancy between assemblages. When accounting for the whole range of distribution of bats, results showed the predominant effect of elevation over other geographical and environmental predictors. This indicates that the diversity of good dispersers such as bats is more affected by specialisation along environment and climatic gradients than by geographical barriers throughout the Amazon biome.

Neuroprotective Effect of Exogenous Galectin-1 in Status Epilepticus - Amanda Larissa Dias Pacheco; Igor Santana de Melo; Maisa de Araujo Costa; Mariah Morais Celestino Amaral; Nívea Karla de Gusmão Taveiros Silva; Yngrid Mickaelli Oliveira Santos; Daniel Leite Góes Gitaí; Marcelo Duzzioni; Alexandre Urban Borbely; Robinson Sabino Silva; Ana Luiza Ferreira Donatti; Luisa Mestriner; et al. (Molecular Neurobiology, 2022)

Dietary exposure to low-calorie sweeteners in a sample of Brazilian pregnant women - Larissa Marinho Duarte; Sila Mary Rodrigues Ferreira; Claudia Choma Bettega Almeida; Ana Clara da Fonseca Leitão Duran; Mariana Fagundes Grilo; Mariana de Souza Macedo; Sylvia do Carmo Castro Franceschini; Sandra Patricia Crispim (Food Additives & Contaminants: Part A, 2022)

Fecundity and reproductive patterns of the fiddler crab Uca maracoani Latreille 1802-1803 in an Amazonian estuary in northern Brazil - Daiane Aviz; Priscila Amorim Carmona; Ana Caroline de Castro Barbosa; Cléverson Rannieri Meira dos Santos (Invertebrate Reproduction & Development, 2022)

Combination of synthetic acaricides with (E)-cinnamaldehyde to control Rhipicephalus microplus - Bruno César Ferreira Gonzaga; Nélio Roberto de Moraes; Gabriel Webert Gomes; Ana Lúcia Coutinho; Francisca Letícia Vale; Lainny Jordana Martins Pereira e Sousa; Laís Marreto; Daniel de Castro Rodrigues; Márcia Cristina de Azevedo Prata; Paula Marchesini; Welber Daniel Zanetti Lopes; Caio Monteiro (Experimental and Applied Acarology, 2022)

Metformin-induced alterations in gills of the freshwater fish Astyanax lacustris (Lütken, 1875) detected by histological and scanning electron microscopy - Pablo Americo Barbieri; Isabelle Pereira Mari-Ribeiro; Luara Lupepsa; Adriana Aparecida Sinópolis Gigliolli; Brennda Ribeiro Paupitz; Rafael Fernando de Melo; Eneri Vieira de Souza Leite Mello; Ana Luiza de Brito Portela-Castro; Luciana Andreia Borin-Carvalho (Ecotoxicology, 2022)

Microbiome signatures in Acropora cervicornis are associated with genotypic resistance to elevated nutrients and heat stress - Ana M. Palacio-Castro; Stephanie M. Rosales; Caroline E. Dennison; Andrew C. Baker (Coral Reefs, 2022)

The Technical and Economic Feasibility of the CENTEC Floating Offshore Wind Platform - Almudena Filgueira-Vizoso; Laura Castro-Santos; David Cordal Iglesias; Félix Puime-Guillén; Isabel Lamas-Galdo; Ana Isabel García-Diez; Emre Uzunoglu; Hugo Díaz; C. Guedes Soares (Journal of Marine Science and Engineering, 2022)
This paper defines a methodology for the economic feasibility analysis of a floating offshore wind farm composed of tensioned leg platforms, which are part of the EU ARCWIND research project. In this context, the phases and subphases of its life-cycle process are considered to deal with aspects such as bathymetry, characteristics of the platforms, distance from the farm to shore, distance from the farm to port and offshore wind speed. All the costs and other external parameters such as capital cost, electric tariff, interest rate, percentage of financing and corporate tax have been analysed to calculate the internal rate of return, net present value, discounted pay-back period and levelized cost of energy of the farm. This work studies a farm composed of TLP offshore wind platforms designed by CENTEC and located at Ribadeo in Spain. Results indicate the costs and the economic feasibility of this platform for deep waters. They indicate that the platform is economically feasible for the location selected.

Genetic diversity and verbascoside content in natural populations of Pyrostegia venusta (Ker Gawl.) Miers - Natália Helena Gavilan; Lucas Junqueira de Freitas Morel; Juliana da Silva Coppede; Silvia Helena Taleb-Contini; Suzelei de Castro França; Bianca Waléria Bertoni; Ana Maria Soares Pereira (Molecular Biology Reports, 2022)

Growth Response, Gas Exchange, and Leaf Anatomy of Handroanthus spp. Seedlings in Mine Tailings Enriched with Nutrient Solution - Ana Lívia Martins Scarpa; Yasmini da Cunha Cruz; Vinícius Politi Duarte; Evaristo Mauro de Castro; Moacir Pasqual; Jean Paulo Vitor de Oliveira; Fabricio José Pereira (Journal of Soil Science and Plant Nutrition, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Fine-scale foraging segregation in a green turtle (Chelonia mydas) feeding ground in the Bijagós archipelago, Guinea Bissau - Fernando Miguel Madeira; Rui Rebelo; Paulo Catry; João Neiva; Castro Barbosa; Aissa Regalla; Ana Rita Patrício (Frontiers in Marine Science, 2022)
Green turtles ( Chelonia mydas ) are highly dependent on neritic foraging areas throughout much of their life. Still, knowledge of recruitment dynamics, foraging habits, and habitat use in these areas is limited. Here, we evaluated how the distribution and food preferences of green sea turtles from different life stages varied within a foraging aggregation. We focused on two islands in Guinea-Bissau, Unhocomo and Unhocomozinho, using water captures and survey dives to record habitat use and characteristics, and stable isotopes to infer diet. Additionally, we used stable isotopes to infer their diet. Two habitat types were sampled: deeper (2.26 ± 0.4 m) rocky sites fringed by mangrove with macroalgae, and sandy shallows (1.37 ± 0.12 m) surrounded by rocky reefs with macroalgae and seagrass. The two benthic communities were similar isotopically and in terms of species composition, except for the presence or absence of seagrass, which had unique signatures. We captured 89 turtles ranging from 35 cm to 97 cm in curved carapace length (i.e., juvenile to adult stages). Size distribution was habitat-dependent, with most smaller turtles present in sandy shallows and larger turtles favoring slightly deeper rocky sites. Turtle isotopic signatures differed between the habitat of capture, regardless of size, revealing a marked dichotomy in foraging preference. All turtles fed primarily on macroalgae, mostly rhodophytes. However, individuals captured in sandy habitats had evident seagrass skewed isotopic signatures. Larger turtles may be unable to use the more diverse shallower foraging sites due to increased vulnerability to predation. Despite the proximity of the sampled foraging sites (2.7 km apart), the two foraging subgroups seem to maintain consistently different feeding habits. Our study highlights how heterogeneous green turtle foraging habits can be within populations, even at small geographic scales.

Late Pleistocene to Holocene variations in marine productivity and terrestrial material delivery to the western South Atlantic - Ana Lúcia Lindroth Dauner; Gesine Mollenhauer; Jens Hefter; Márcia Caruso Bícego; Michel Michaelovitch de Mahiques; César de Castro Martins (Frontiers in Marine Science, 2022)
Despite the increased number of paleoceanographic studies in the SW Atlantic in recent years, the mechanisms controlling marine productivity and terrestrial material delivery to the South Brazil Bight remain unresolved. Because of its wide continental shelf and abrupt change in coastline orientation, this region is under the influence of several environmental forcings, causing the region to have large variability in primary production. This study investigated terrestrial organic matter (OM) sources and marine OM sources in the South Brazil Bight, as well as the main controls on marine productivity and terrestrial OM export. We analyzed OM geochemical (bulk and molecular) proxies in sediment samples from a core (NAP 63-1) retrieved from the SW Atlantic slope (24.8°S, 44.3°W, 840-m water depth). The organic proxies were classified into “terrestrial-source” and “marine-source” groups based on a cluster analysis. The two sources presented different stratigraphical profiles, indicating distinct mechanisms governing their delivery. Bulk proxies indicate the predominance of marine OM, although terrestrial input also affected the total OM deposition. The highest marine productivity, observed between 50 and 39 ka BP, was driven by the combined effects of the South Atlantic Central Water upwelling promoted by Brazil Current eddies and fluvial nutrient inputs from the adjacent coast. After the last deglaciation, decreased phytoplankton productivity and increased archaeal productivity suggest a stronger oligotrophic tropical water presence. The highest terrestrial OM accumulation occurred between 30 and 20 ka BP, with its temporal evolution controlled mainly by continental moisture evolution. Sea level fluctuations affected the distance between the coastline and the sampling site. In contrast, continental moisture affected the phytogeography, changing from lowlands covered by grasses and saltmarshes to a landscape dominated by mangroves and the Atlantic Forest. Our results suggest how the OM cycle in the South Brazil Bight may respond to warmer and dryer climate conditions.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Plant growth-promoting and non-promoting rhizobacteria from avocado trees differentially emit volatiles that influence growth of Arabidopsis thaliana - Roberto Gamboa-Becerra; Damaris Desgarennes; Jorge Molina-Torres; Enrique Ramírez-Chávez; Ana L. Kiel-Martínez; Gloria Carrión; Randy Ortiz-Castro (Protoplasma, 2022)

Correction to: Even generalist and resilient species are affected by anthropic disturbance: evidence from wild boar activity patterns in a Mediterranean landscape - Luís M. Rosalino; Daniela Teixeira; Cláudia Camarinha; Guilherme Pereira; Ana Magalhães; Guilherme Castro; Cátia Lima; Carlos Fonseca (Mammal Research, 2022)

Even generalist and resilient species are affected by anthropic disturbance: evidence from wild boar activity patterns in a Mediterranean landscape - Luís M. Rosalino; Daniela Teixeira; Cláudia Camarinha; Guilherme Pereira; Ana Magalhães; Guilherme Castro; Cátia Lima; Carlos Fonseca (Mammal Research, 2022)

Movements of Hatchery-Reared Dusky Groupers Released in a Northeast Atlantic Coastal Marine Protected Area - Ana Filipa Silva; Bárbara Horta e Costa; José Lino Costa; Esmeralda Pereira; João Pedro Marques; João J. Castro; Pedro G. Lino; Ana Candeias-Mendes; Pedro Pousão-Ferreira; Inês Sousa; Luís Bentes; Jorge M. S. Gonçalves; et al. (Journal of Marine Science and Engineering, 2022)
No-take areas are key instruments to promote the effectiveness of Marine Protected Areas (MPAs), particularly concerning the protection of endangered species such as the dusky grouper (Epinephelus marginatus). However, despite the establishment of no-take areas and the prohibition of catching this species in a southwestern Portuguese MPA (SACVMP—‘Sudoeste Alentejano’ and ‘Costa Vicentina’ Marine Park) since 2011, there is still no evidence of population recovery. By using acoustic biotelemetry, this work aimed to evaluate the feasibility of restocking hatchery-reared adult dusky groupers in two no-take areas within the SACVMP. In 2019 and 2021, thirty groupers were tagged with acoustic transmitters and the site attachment and movements of the groupers were assessed in the releasing sites (no-take areas). None of the tagged fish settled down in either of the areas, leaving the no-take areas mainly at dusk and night. Some individuals displayed extended movements of more than a hundred kilometers along the Portuguese coast which was rarely reported for this species. At least in some coastal stretches, those movements were performed close to the shore, which may evidence the importance of coastal MPAs to protect and promote the connectivity of species more associated with rocky reef habitats. Following studies should focus on the conditions that promote site attachment and fidelity by hatchery-reared dusky groupers so that future large-scale restocking programs can be successful in MPAs with appropriate habitats.

Preparation of Ciguatoxin Reference Materials from Canary Islands (Spain) and Madeira Archipelago (Portugal) Fish - David Castro; Pablo Estévez; José Manuel Leao-Martins; Robert W. Dickey; Natalia García-Álvarez; Fernando Real; Pedro Reis Costa; Ana Gago-Martínez (Journal of Marine Science and Engineering, 2022)
Ciguatoxins (CTXs) are naturally occurring neurotoxins that can accumulate in fish and cause Ciguatera Poisoning (CP) in seafood consumers. Ciguatoxic fish have been detected in tropical and subtropical regions of the world including the Pacific and Indian Oceans, the Caribbean Sea, and more recently in the northeast Atlantic Ocean. The biogeographic distribution of ciguatoxic fish appears to be expanding; however, the paucity of CTX standards and reference materials limits the ability of public health authorities to monitor for these toxins in seafood supply chains. Recent reports establish that Caribbean Ciguatoxin-1 (C-CTX1) is the principal toxin responsible for CP cases and outbreaks in the northeast Atlantic Ocean and that C-CTX congener profiles in contaminated fish samples match those from the Caribbean Sea. Therefore, in this work, C-CTX reference materials were prepared from fish obtained from the northeast Atlantic Ocean. The collection of fish specimens (e.g., amberjack, grouper, or snapper) was screened for CTX-like toxicity using the in vitro sodium channel mouse neuroblastoma cytotoxicity assay (N2a cell assay). Muscle and liver tissues from toxic specimens were pooled for extraction and purified products were ultimately profiled and quantified by comparison with authentic C-CTX1 using LC-MS/MS. This work presents a detailed protocol for the preparation of purified C-CTX reference materials to enable continued research and monitoring of the ciguatera public health hazard. To carry out this work, C-CTX1 was isolated and purified from fish muscle and liver tissues obtained from the Canary Islands (Spain) and Madeira archipelago (Portugal).

Setting Performance Indicators for Coastal Marine Protected Areas: An Expert-Based Methodology - Mariana Cardoso-Andrade; Henrique Queiroga; Mafalda Rangel; Inês Sousa; Adela Belackova; Luís Bentes; Frederico Oliveira; Pedro Monteiro; Nuno Sales Henriques; Carlos M. L. Afonso; Ana F. Silva; Bernardo R. Quintella; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) require effective indicators to assess their performance, in compliance with the goals of relevant national and international commitments. Achieving and prioritizing shortlists of multidisciplinary indicators demands a significant effort from specialists to depict the multiple conservation and socioeconomic interests, and the large complexity of natural systems. The present paper describes a structured expert-based methodology (process and outputs) to co-define a list of multidisciplinary MPA performance indicators. This work was promoted by the management authority of coastal MPAs in mainland Portugal to gather a consensual and feasible list of indicators that would guide the design of a future national monitoring program. Hence, Portuguese coastal MPAs served as a case study to develop such a process between 2019 and 2020. In the end, participants (1) agreed on a shortlist of prioritized indicators ( i.e. , environmental, governance, and socioeconomic indicators) and (2) defined minimum monitoring frequencies for the indicators in this list, compatible with the potential replicability of the associated survey methods. The present approach recommends that management plans incorporate monitoring procedures and survey methods, with a validated list of indicators and associated monitoring periodicity, agreed among researchers, MPA managers and governance experts. The proposed methodology, and the lessons learned from it, can support future processes aiming to define and prioritize MPA performance indicators.

Hydrochlorothiazide use is associated with the risk of cutaneous and lip squamous cell carcinoma: A systematic review and meta-analysis - Ana Cláudia de Macedo Andrade; Fernanda Aragão Felix; Glória Maria França; Isabella Lima Arrais Ribeiro; Carlos Augusto Galvão Barboza; Ricardo Dias de Castro; Antônio de Lisboa Lopes Costa (European Journal of Clinical Pharmacology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Particulate matter–bound organic compounds: levels, mutagenicity, and health risks - Sofia Caumo; Aleinnys B. Yera; Ana Vicente; Célia Alves; Deborah A. Roubicek; Pérola de Castro Vasconcellos (Environmental Science and Pollution Research, 2022)

Detecting the attack of the fall armyworm (Spodoptera frugiperda) in cotton plants with machine learning and spectral measurements - Ana Paula Marques Ramos; Felipe David Georges Gomes; Mayara Maezano Faita Pinheiro; Danielle Elis Garcia Furuya; Wesley Nunes Gonçalvez; José Marcato Junior; Mirian Fernandes Furtado Michereff; Maria Carolina Blassioli-Moraes; Miguel Borges; Raúl Alberto Alaumann; Veraldo Liesenberg; Lúcio André de Castro Jorge; et al. (Precision Agriculture, 2022)

Eco-innovation assessment of biodigesters technology: an application in cassava processing industries in the south of Brazil, Parana state - Marco Antonio Sampaio de Jesus; Ana Regina de Aguiar Dutra; Claudia Brito Silva Cirani; Katia Regina Evaristo Jesus; Ruy Castro Sobrosa Neto; José Baltazar Andrade Guerra (Clean Technologies and Environmental Policy, 2022)

Pre-reproductive movements of potamodromous cyprinids in the Iberian Peninsula: when environmental variability meets semipermeable barriers - Ana García-Vega; Juan Francisco Fuentes-Pérez; Francisco Javier Bravo-Córdoba; Jorge Ruiz-Legazpi; Jorge Valbuena-Castro; Francisco Javier Sanz-Ronda (Hydrobiologia, 2022)

Genetic description of VanD phenotype vanA genotype in vancomycin-resistant Enterococcus faecium isolates from a Bone Marrow Transplantation Unit - Ana Paula Marchi; Lauro Vieira Perdigão Neto; Marina Farrel Côrtes; Victor Augusto Camarinha de Castro Lima; Roberta Cristina Ruedas Martins; Lucas Augusto Moyses Franco; Flavia Rossi; Vanderson Rocha; Anna S. Levin; Silvia Figueiredo Costa (Brazilian Journal of Microbiology, 2022)

Bioaerosol vertical fungal spores profile in Minas Gerais State, Brazil - Ana Paula Mendes Emygdio; Cristiane Degobbi; Federico Carotenuto; Dulcilena de Matos Castro e Silva; Thaysla Beluco Quintino; Rafael Henrique de Souza Zanetti; Mauricio C. Mantoani; Solana Meneghel Boschilia; Lara Chaves Carvalho Guerra; Pedro Leite da Silva Dias; Cindy E. Morris; Fábio Luiz Teixeira Gonçalves (Aerobiologia, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

The redundancy effect under morphogenetic and environmental fluctuations. The case of the Dianthus pungens group - Isaura Castro; João Rocha; Maria Martins; Valdemar Carnide; Juan Pedro Martín; Pedro Veiga; Ana Beatriz Serafim; Francisco Amich; Rubén Ramírez-Rodríguez; Giacomo Colombo; António Luis Crespí (Plant Biosystems, 2022)

Contamination gradient affects differently carbonic anhydrase activity of mollusks depending on their feeding habits - Cyntia Ayumi Yokota Harayashiki; Helen Sadauskas-Henrique; Luciana Rodrigues de Souza-Bastos; Nayara Gouveia; Ana Julya Luna; Antonio Ostrensky; Italo Braga Castro (Ecotoxicology, 2022)

Fish Upstream Passage through Gauging Stations: Experiences with Iberian Barbel in Flat-V Weirs - Francisco Javier Sanz-Ronda; Francisco Javier Bravo-Córdoba; Ana García-Vega; Jorge Valbuena-Castro; Andrés Martínez-de-Azagra; Juan Francisco Fuentes-Pérez (Fishes, 2021)
The monitoring of river discharge is vital for the correct management of water resources. Flat-V gauging weirs are facilities used worldwide for measuring discharge. These structures consist of a small weir with a triangular cross-section and a flat “V”-shaped notch. Their extensive use is a consequence of their utility in the measurement of both low and high flow conditions. However, depending on their size, local morphology and river discharge can act as full or partial hydraulic barriers to fish migration. To address this concern, the present work studies fish passage performance over flat-V weirs considering their hydraulic performance. For this, radio-tracking and video-monitoring observations were combined with computational fluid dynamics (CFD) models in two flat-V weirs, using Iberian barbel (Luciobarbus bocagei) as the target species. Results showed that fish passage is conditioned by both hydraulic and behavioral processes, providing evidence for scenarios in which flat-V weirs may act as full or partial barriers to upstream movements. For the studied flat-V weirs, a discharge range of 0.27–8 m3/s, with a water drop difference between upstream and downstream water levels lower than 0.7 m and a depth downstream of the weir of higher than 0.3 m can be considered an effective passage situation for barbels. These findings are of interest for quantifying flat-V weir impacts, for engineering applications and for establishing managing or retrofitting actions when required.

High prevalence of anti-Toxoplasma gondii antibodies in beef cattle in Midwestern Brazil - Maerle Oliveira Maia; Sayanne Luns Hatum de Almeida; Ana Carolina Schmidt; Anderson Castro Soares de Oliveira; Daniel Moura de Aguiar; Thaís Rabelo dos Santos-Doni; Richard de Campos Pacheco (Veterinary Research Communications, 2021)

Ecological risks associated to trace metals of contaminated sediments from a densely urbanized tropical eutrophic estuary - Christiane do Nascimento Monte; Ana Paula de Castro Rodrigues; Alexandre Rafael de Freitas; Bernardo Ferreira Braz; Aline Soares Freire; Renato Campello Cordeiro; Ricardo Erthal Santelli; Wilson Thadeu Valle Machado (Environmental Monitoring and Assessment, 2021)

Self-shading effect in the growth, photosynthesis and anatomy of Typha domingensis Pers. - Ana Lívia Martins Scarpa; Yasmini da Cunha Cruz; Marcio Paulo Pereira; Evaristo Mauro de Castro; Marcelo Polo; Vinícius Politi Duarte; Fabricio José Pereira (Brazilian Journal of Botany, 2021)

Aging disrupts the temporal organization of antioxidant defenses in the heart of male rats and phase shifts circadian rhythms of systolic blood pressure - Fernando Gabriel Altamirano; Ivanna Carla Castro-Pascual; Mariana Lucila Ferramola; Marina Luz Tula; Silvia Marcela Delgado; Ana Cecilia Anzulovich; María Gabriela Lacoste (Biogerontology, 2021)

The Impact of Variants in Four Genes: MC4R, FTO, PPARG and PPARGC1A in Overweight and Obesity in a Large Sample of the Brazilian Population - Gabriel Vaisam Castro; Ana Frederica Sutter Latorre; Fabíola Pozza Korndorfer; Lia Kubelka de Carlos Back; Sara Emelie Lofgren (Biochemical Genetics, 2021)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Reproductive cycle of sea urchin Echinometra vanbrunti (Echinodermata: Echinoidea) from the Gulf of California - Ana Gloria Villalba Villalba; Lerma Hanaiy Chan Chan; Irlanda Lagarda Diaz; Naomi Yerith Reyes Jiménez; Christian Minjarez Osorio; Reina Castro Longoria; Amir Maldonado Arce (Marine Biology Research, 2021)

Gray matter correlates of reading fluency deficits: SES matters, IQ does not - Marta Martins; Ana Mafalda Reis; São Luís Castro; Christian Gaser (Brain Structure and Function, 2021)

The role of rs242941, rs1876828, rs242939 and rs110402 polymorphisms of CRHR1 gene and the depression: systematic review and meta-analysis - Yazmín Hernández-Díaz; Thelma Beatriz González-Castro; Isela Esther Juárez-Rojop; Carlos Alfonso Tovilla-Zárate; María Lilia López-Narváez; Alma Delia Genis-Mendoza; Ana Fresan; Humberto Nicolini (Genes & Genomics, 2021)

First Assessment of the Impacts of the COVID-19 Pandemic on Global Marine Recreational Fisheries - Pablo Pita; Gillian B. Ainsworth; Bernardino Alba; Antônio B. Anderson; Manel Antelo; Josep Alós; Iñaki Artetxe; Jérôme Baudrier; José J. Castro; Belén Chicharro; Karim Erzini; Keno Ferter; et al. (Frontiers in Marine Science, 2021)
This work is the result of an international research effort to determine the main impacts of the COVID-19 pandemic on marine recreational fishing. Changes were assessed on (1) access to fishing, derived from lockdowns and other mobility restrictions; (2) ecosystems, because of alterations in fishing intensity and human presence; (3) the blue economy, derived from alterations in the investments and expenses of the fishers; and (4) society, in relation to variations in fishers’ health and well-being. For this, a consultation with experts from 16 countries was carried out, as well as an international online survey aimed at recreational fishers, that included specific questions designed to capture fishers’ heterogeneity in relation to behavior, skills and know-how, and vital involvement. Fishers’ participation in the online survey (5,998 recreational fishers in 15 countries) was promoted through a marketing campaign. The sensitivity of the fishers’ clustering procedure, based on the captured heterogeneity, was evaluated by SIMPER analysis and by generalized linear models. Results from the expert consultation highlighted a worldwide reduction in marine recreational fishing activity. Lower human-driven pressures are expected to generate some benefits for marine ecosystems. However, experts also identified high negative impacts on the blue economy, as well as on fisher health and well-being because of the loss of recreational fishing opportunities. Most (98%) of the fishers who participated in the online survey were identified as advanced , showing a much higher degree of commitment to recreational fishing than basic fishers (2%). Advanced fishers were, in general, more pessimistic about the impacts of COVID-19, reporting higher reductions in physical activity and fish consumption, as well as poorer quality of night rest, foul mood, and raised more concerns about their health status. Controlled and safe access to marine recreational fisheries during pandemics would provide benefits to the health and well-being of people and reduce negative socioeconomic impacts, especially for vulnerable social groups.

Variation in susceptibility among three Caribbean coral species and their algal symbionts indicates the threatened staghorn coral, Acropora cervicornis, is particularly susceptible to elevated nutrients and heat stress - Ana M. Palacio-Castro; Caroline E. Dennison; Stephanie M. Rosales; Andrew C. Baker (Coral Reefs, 2021)

Genome size variation in Cactaceae and its relationship with invasiveness and seed traits - Sara Lopes; Lucie Mota; Mariana Castro; Gabrielle Nobre; Ana Novoa; David M. Richardson; João Loureiro; Sílvia Castro (Biological Invasions, 2021)

Understanding the dairy production systems in rural settlements in the Brazilian semi-arid region: characterization, typology, and holistic perception - Maria Samires Martins Castro; Delano de Sousa Oliveira; Raquel Oliveira dos Santos Fontenelle; Ana Paula Araújo do Nascimento; Robson Mateus Freitas Silveira; Wilder Hernando Ortiz Vega; Leonardo Costa da Silva; Ana Thaís Lira Soares; Angela Maria de Vasconcelos (Tropical Animal Health and Production, 2021)

Correction to: Taxonomic, functional and phylogenetic bat diversity decrease from more to less complex natural habitats in the Amazon - William Douglas Carvalho; Karen Mustin; Fábio Z. Farneda; Isaí Jorge de Castro; Renato R. Hilário; Ana Carolina Moreira Martins; João D. Miguel; Bruna da Silva Xavier; José Júlio de Toledo (Oecologia, 2021)

Taxonomic, functional and phylogenetic bat diversity decrease from more to less complex natural habitats in the Amazon - William Douglas Carvalho; Karen Mustin; Fábio Z. Farneda; Isaí Jorge de Castro; Renato R. Hilário; Ana Carolina Moreira Martins; João D. Miguel; Bruna da Silva Xavier; José Júlio de Toledo (Oecologia, 2021)

Correction to: Metabarcoding meiofauna biodiversity assessment in four beaches of Northern Colombia: effects of sampling protocols and primer choice - Lyda R. Castro; Rachel S. Meyer; Beth Shapiro; Sabrina Shirazi; Samuel Cutler; Ana M. Lagos; Sigmer Y. Quiroga (Hydrobiologia, 2021)

Metabarcoding meiofauna biodiversity assessment in four beaches of Northern Colombia: effects of sampling protocols and primer choice - Lyda R. Castro; Rachel S. Meyer; Beth Shapiro; Sabrina Shirazi; Samuel Cutler; Ana M. Lagos; Sigmer Y. Quiroga (Hydrobiologia, 2021)

Hydraulic and auto-depurative characteristics of the Gualaxo do Norte River after the Fundão dam rupture - Deyse Almeida dos Reis; Priscila Kelly da Silva; Igor Andrade Azevedo; Ana Letícia Pilz de Castro; Aníbal da Fonseca Santiago (Environmental Science and Pollution Research, 2021)

Unusual finding of the human-adapted hypervirulent serotype III/ST17 clone in a historical bovine Group B Streptococcus isolate from Brazil - Leandro Correa Simões; Ana Carolina Pires Silva; Crislaine Mateus Santos; Danielle Cristina Santos Silva Alvim; Débora Costa Morato Nery; Laura Maria Andrade Oliveira; Lucia Martins Teixeira; Tatiana Castro Abreu Pinto (Brazilian Journal of Microbiology, 2021)

Bauhinia holophylla (Bong.) Steud. leaves-derived extracts as potent anti-dengue serotype 2 - Michelli dos Santos; Thaiz Rodrigues Teixeira; Felipe Rocha da Silva Santos; William Gustavo Lima; Ariane Coelho Ferraz; Nathália Lucca Silva; Flávio José Leite; João Máximo Siqueira; Walter Luyten; Ana Hortência Fonseca de Castro; José Carlos de Magalhães; Jaqueline Maria Siqueira Ferreira (Natural Product Research, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

The development of anastomosed laticifers in the stem apical meristem and vascular cambium of Hancornia speciosa (Apocynaceae) is related to climatic seasonality - Ana Iris Ribeiro de Castro Souza; Karine Rodrigues Cordeiro; Mayara Pereira Gonçalves; Leonardo Monteiro Ribeiro; Maria Olívia Mercadante-Simões (Trees, 2021)

Semantic segmentation of citrus-orchard using deep neural networks and multispectral UAV-based imagery - Lucas Prado Osco; Keiller Nogueira; Ana Paula Marques Ramos; Mayara Maezano Faita Pinheiro; Danielle Elis Garcia Furuya; Wesley Nunes Gonçalves; Lucio André de Castro Jorge; José Marcato Junior; Jefersson Alex dos Santos (Precision Agriculture, 2021)

Risk factors for neurological complications in children with Flavivirus infection - Aline Almeida Bentes; Roberta Maia de Castro Romanelli; Paula Eillanny Silva Marinho; Ana Paula Correa Crispim; Karina Soares Loutfi; Eisler Cristiane Carvalho Viegas; Erna Geessien Kroon (Journal of NeuroVirology, 2021)

Ethosomes as Nanocarriers for the Development of Skin Delivery Formulations - Ana Cláudia Paiva-Santos; Ana Luísa Silva; Catarina Guerra; Diana Peixoto; Miguel Pereira-Silva; Mahdi Zeinali; Filipa Mascarenhas-Melo; Ricardo Castro; Francisco Veiga (Pharmaceutical Research, 2021)

The role of rhizofiltration and allelopathy on the removal of cyanobacteria in a continuous flow system - Ana Teresa Castro-Castellon; Jocelyne Mary Rose Hughes; Daniel Steven Read; Yaldah Azimi; Michael James Chipps; Nicholas Peter Hankins (Environmental Science and Pollution Research, 2021)

GABAergic deficits in absence of LPA1 receptor, associated anxiety-like and coping behaviors, and amelioration by interneuron precursor transplants into the dorsal hippocampus - Cristina Rosell-Valle; Magdalena Martínez-Losa; Elisa Matas-Rico; Estela Castilla-Ortega; Emma Zambrana-Infantes; Ana Isabel Gómez-Conde; Lourdes Sánchez-Salido; David Ladrón de Guevara-Miranda; Carmen Pedraza; Pedro Jesús Serrano-Castro; Jerold Chun; Fernando Rodríguez de Fonseca; et al. (Brain Structure and Function, 2021)

Optimizing Large-Scale Biodiversity Sampling Effort: Toward an Unbalanced Survey Design - Enrique Montes; Jonathan Lefcheck; Edlin Guerra Castro; Eduardo Klein; Ana Carolina de Azevedo Mazzuco; Gregorio Bigatti; Cesar Cordeiro; Nuno Simoes; Erasmo Macaya; Nicolas Moity; Edgardo Londoño-Cruz; Brian Helmuth; et al. (Oceanography, 2021)
Acquiring marine biodiversity data is difficult, costly, and time-consuming, making it challenging to understand the distribution and abundance of life in the ocean. Historically, approaches to biodiversity sampling over large geographic scales have advocated for equivalent effort across multiple sites to minimize comparative bias. When effort cannot be equalized, techniques such as rarefaction have been applied to minimize biases by reverting diversity estimates to equivalent numbers of samples or individuals. This often results in oversampling and wasted resources or inaccurately characterized communities due to undersampling. How, then, can we better determine an optimal survey design for characterizing species richness and community composition across a range of conditions and capacities without compromising taxonomic resolution and statistical power? Researchers in the Marine Biodiversity Observation Network Pole to Pole of the Americas (MBON Pole to Pole) are surveying rocky shore macroinvertebrates and algal communities spanning ~107° of latitude and 10 biogeographic ecoregions to address this question. Here, we apply existing techniques in the form of fixed-coverage subsampling and a complementary multivariate analysis to determine the optimal effort necessary for characterizing species richness and community composition across the network sampling sites. We show that oversampling for species richness varied between ~20% and 400% at over half of studied areas, while some locations were undersampled by up to 50%. Multivariate error analysis also revealed that most of the localities were oversampled by several-fold for benthic community composition. From this analysis, we advocate for an unbalanced sampling approach to support field programs in the collection of high-quality data, where preliminary information is used to set the minimum required effort to generate robust values of diversity and composition on a site-to-site basis. As part of this recommendation, we provide statistical tools in the open-source R statistical software to aid researchers in implementing optimization strategies and expanding the geographic footprint or sampling frequency of regional biodiversity survey programs.

Phytotoxic and antioxidant effects of dichloromethane fraction of Smilax Brasiliensis Sprengel - Myriam Almeida Barbosa; Juliana Costa Fonseca; Vany Ferraz; Ana Hortência Fonsêca Castro; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2021)

Evaluation of wheat genotypes for field resistance to wheat blast caused by Magnaporthe oryzae pathotype Triticum (MoT) and correlation between yield loss and disease incidence in the Brazilian Cerrado - Alexei de Campos Dianese; Ana Beatriz Zacaroni; Bruno Cézar Pereira de Souza; Ana Paula da Silva Pagani; Nelson Oliveira Pinheiro; Eduardo Monteiro de Castro Gomes; Gisele Abigail Montan Torres; Luciano Consoli; Adalberto Corrêa Café-Filho (Euphytica, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Cytotoxicity of glucoevatromonoside alone and in combination with chemotherapy drugs and their effects on Na+,K+-ATPase and ion channels on lung cancer cells - Naira Fernanda Zanchett Schneider; Danusa Menegaz; Andre Luiz Andreotti Dagostin; Lara Persich; Sayonarah C. Rocha; Ana Carolina Pacheco Ramos; Vanessa Faria Cortes; Carlos Frederico Leite Fontes; Rodrigo Maia de Pádua; Jennifer Munkert; Wolfgang Kreis; Fernão Castro Braga; et al. (Molecular and Cellular Biochemistry, 2021)

In vitro and in vivo anti-inflammatory activity and chemical composition of Renealmia petasites Gagnep - Aline Keller Couto Soares; Antônio Domingos de Sousa Júnior; Mariane Fioroti Lorençoni; Júlia Araujo de Castro; Flávia Vitorino de Araujo Porto; Iana Soares Pessoa; Marcos Vinicius Toledo e Silva; Ana Claudia Hertel Pereira; Flavia de Souza Andrade Moraes; Tadeu Uggere de Andrade; Denise Coutinho Endringer; Rodrigo Scherer; et al. (Inflammopharmacology, 2021)

Optic neuritis following SARS-CoV-2 infection - Mónica Saray Rodríguez-Rodríguez; Rosa María Romero-Castro; Claudia Alvarado-de la Barrera; María Gabriela González-Cannata; Ana Karen García-Morales; Santiago Ávila-Ríos (Journal of NeuroVirology, 2021)

Limonium mucronatum : plant communities and cytogenetic characterization of an endemic of the Moroccan Atlantic Coast - Laila Rhazi; Ana Rita Rebelo; Ana S. Róis; Sílvia Castro; João Loureiro; Mohammed El Madihi; Ana Paula Paes; Patrick Grillas; Mohammed Ibn Tattou; Ana D. Caperta (Plant Biosystems, 2021)

Spatial distribution of Toxoplasma gondii in cows and associated risk factors - Larissa Alves; Jaqueline Lima; Jade Melo; Ana Maria de Castro; Vando Soares; Gabriel Rossi; Weslen Teixeira; Lorena Ferreira; Breno Cruz; Gustavo Felippelli; Vanessa Oliveira; Paula Brom; et al. (Tropical Animal Health and Production, 2021)

Galactomannan of Delonix regia seeds reduces nociception and morphological damage in the rat model of osteoarthritis induced by sodium monoiodoacetate - Francisco Glerison da Silva Nascimento; Pedro Henrique de Souza Ferreira Bringel; Francisco Wildson Silva Maia; Carlos Pinheiro Chagas Lima; Rômulo Couto Alves; Judith Pessoa Andrade Feitosa; Mário Rogério Lima Mota; Ana Maria Sampaio Assreuy; Rondinelle Ribeiro Castro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Role of Modulation of Hippocampal Glucose Following Pilocarpine-Induced Status Epilepticus - Igor Santana de Melo; Yngrid Mickaelli Oliveira dos Santos; Amanda Larissa Dias Pacheco; Maisa Araújo Costa; Vanessa de Oliveira Silva; Jucilene Freitas-Santos; Cibelle de Melo Bastos Cavalcante; Reginaldo Correia Silva-Filho; Ana Catarina Rezende Leite; Daniel Góes Leite Gitaí; Marcelo Duzzioni; Robinson Sabino-Silva; et al. (Molecular Neurobiology, 2021)

Cardiorespiratory response to exercise in endurance-trained premenopausal and postmenopausal females - Beatriz Rael; Laura Barba-Moreno; Nuria Romero-Parra; Víctor M. Alfaro-Magallanes; Eliane A. Castro; Rocío Cupeiro; Ana B. Peinado (European Journal of Applied Physiology, 2021)

Microbiomes in agricultural and mining soils contaminated with arsenic in Guanajuato, Mexico - María Elena López-Pérez; Adriana Saldaña-Robles; Gabriela Ana Zanor; Jorge E. Ibarra; María Cristina Del Rincón-Castro (Archives of Microbiology, 2021)

PTPN22 gene functional polymorphism (rs2476601) in older adults with frailty syndrome - Rubén Rabaneda-Bueno; Norma Torres-Carrillo; José Alberto Ávila-Funes; Luis Miguel Gutiérrez-Robledo; Thalía Gabriela Pérez-Suárez; José Luis Acosta; Sara Torres-Castro; Ana Lilia Fletes-Rayas; Itzae Gutierrez-Hurtado; Elena Sandoval-Pinto; Rosa Cremades; Nora Magdalena Torres-Carrillo (Molecular Biology Reports, 2021)

Evaluation of copper-induced DNA damage in Vitis vinifera L. using Comet-FISH - Cláudia Castro; Ana Carvalho; Isabel Gaivão; José Lima-Brito (Environmental Science and Pollution Research, 2021)

First characterization of the ecotoxicity of paraffin particles: assessment of biochemical effects in the marine polychaete Hediste diversicolor - Ana Sofia Gomes; Bruno B. Castro; Bruno Nunes (Environmental Science and Pollution Research, 2020)

PLA-PEG nanospheres decorated with phage display selected peptides as biomarkers for detection of human colorectal adenocarcinoma - Aline de Souza; William Castro-Borges; Milton Hércules Guerra de Andrade; Yara Cristina de Paiva Maia; Luiz Ricardo Goulart; Elisa Gomes Lanna; Ana Carolina Ferreira de Brito; Ana Paula Moreira Barboza; Vanessa Carla Furtado Mosqueira; Karina Taciana Santos Rubio (Drug Delivery and Translational Research, 2020)

In Situ Transesterification of Marine Microalgae Biomass via Heterogeneous Acid Catalysis - Savienne M. F. E. Zorn; Cristiano E. R. Reis; Heitor B. S. Bento; Ana Karine F. de Carvalho; Messias B. Silva; Heizir F. De Castro (BioEnergy Research, 2020)

Holoplankton and meroplankton of three western Atlantic sedimentary basins - Cristina de Oliveira Dias; Ana Cristina Teixeira Bonecker; Márcia Salustiano de Castro; Pedro Freitas de Carvalho; Rodolfo Paranhos; Sérgio Luiz Costa Bonecker (Marine Biology Research, 2020)

First Spatial Distribution Analysis of Male Sea Turtles in the Southern Gulf of Mexico - Eduardo Cuevas; Nathan F. Putman; Abigail Uribe-Martínez; Melania C. López-Castro; Vicente Guzmán-Hernández; Sandra A. Gallegos-Fernández; María de los Ángeles Liceaga-Correa; Jorge A. Trujillo-Córdova; Raúl de Jesús González-Díaz-Mirón; Ana Negrete-Phillipe; Héctor H. Acosta-Sánchez; Rosa C. Martínez-Portugal; et al. (Frontiers in Marine Science, 2020)
In the Gulf of Mexico, the bulk of published studies for sea turtles have focused on northern (United States) waters where economic resources are centered, with fewer studies in the southern portion of the basin, resulting in significant knowledge gaps in these underrepresented areas. Similarly, publications on adult sea turtles are dominated by research on females that come ashore to nest and can be readily studied (e.g., through the collection of biological samples and the application of satellite-telemetry devices), whereas information on adult male sea turtles is scarce. The goal of this paper is to begin filling these knowledge gaps by synthesizing available data on adult male sea turtles in the southern Gulf of Mexico. We used satellite-telemetry, boat- and drone-based surveys, and stranding records combined with ocean circulation modeling to better understand the spatial distribution of male loggerhead ( Caretta caretta ), green ( Chelonia mydas ), hawksbill ( Eretmochelys imbricata ), and Kemp’s ridley ( Lepidochelys kempii ) sea turtles in the southern Gulf of Mexico. These spatially explicit analyses will provide context for opportunistically collected data on male sea turtles and better contribute to the management and restoration of sea turtle populations that use the Gulf of Mexico. Moreover, this synthesis can serve as a launching point for directed studies on male sea turtles in this region.

Analysis of predisposing factors for the development of Clostridioides difficile infection recurrence - Ana-Teresa Marques-Afonso; Iván Fernández-Castro; Néstor Vázquez-Agra; Lucía Barrera-López; Vanesa Alende-Castro; Cristina Macía-Rodríguez; Lara Mateo-Mosquera; Ignacio Novo-Veleiro (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Cr(VI) reduction and adsorption by bimetallic nanoparticles from Li-ion batteries - Sthefany dos Santos Sena; Jean Castro da Cruz; Ana Paula de Carvalho Teixeira; Renata Pereira Lopes (Environmental Science and Pollution Research, 2020)

Multilocus and morphological analysis of south‐eastern Iberian Wall lizards (Squamata, Podarcis ) - Marta Bassitta; Joana M. Buades; Ana Pérez‐Cembranos; Valentín Pérez‐Mellado; Barbara Terrasa; Richard P. Brown; Pilar Navarro; Javier Lluch; Jesús Ortega; Jose A. Castro; Antònia Picornell; Cori Ramon (Zoologica Scripta, 2020)
The phylogenetic relationships among the wall lizards of the Podarcis hispanicus complex that inhabit the south‐east (SE) of the Iberian Peninsula and other lineages of the complex remain unclear. In this study, four mitochondrial and two nuclear markers were used to study genetic relationships within this complex. The phylogenetic analyses based on mtDNA gene trees constructed with ML and BI, and a species tree using *BEAST support three divergent clades in this region: the Valencia, Galera and Albacete/Murcia lineages. These three lineages were also corroborated in species delimitation analyses based on mtDNA using bPTP, mPTP, GMYC, ABGD and BAPS. Bayesian inference species delimitation method (BPP) based on both nuclear data and a combined data set (mtDNA + nuclear) showed high posterior probabilities for these three SE lineages (≥0.94) and another Bayesian analysis (STACEY) based on combined data set recovered the same three groups in this region. Divergence time dating of the species tree provided an estimated divergence of the Galera lineage from the other SE group ( Podarcis vaucheri , (Albacete/Murcia, Valencia)) at 12.48 Ma. During this period, the Betic–Rifian arc was isolated, which could have caused the isolation of the Galera form distributed to the south of the Betic Corridor. Although lizards from the Albacete/Murcia and Galera lineage are morphologically similar, they clearly represent distinct genetic lineages. The noteworthy separation of the Galera lineage enables us to conclude that this lineage must be considered as a new full species.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Education principles and practises turned to sustainability in primary school - Arthur William Pereira da Silva; Ana Lúcia de Araújo Lima Coelho; Helaine Cristine Carneiro dos Santos; Alípio Ramos Veiga Neto; Ahiram Brunni Cartaxo de Castro; Walid Abbas El-Aouar (Environment, Development and Sustainability, 2020)

Phenolic compounds: antioxidant and larvicidal potential of Smilax brasiliensis Sprengel leaves - Paula Avelar Amado; Ana Hortência Fonsêca Castro; Stênio Nunes Alves; Denise Brentan Silva; Carlos Alexandre Carollo; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2020)

Major mutations in the NS3 gene region of hepatitis C virus related to the resistance to direct acting antiviral drugs: a systematic review - Ana Elisa de Figueiredo Miranda Mundim; Fernanda de Oliveira Feitosa de de Castro; Marina Brandão Braz Albuquerque; Cesar Augusto Sam Tiago Vilanova-Costa; Irmtraut Araci Hoffmann Pfrimer; Antonio Márcio Teodoro Cordeiro Silva (VirusDisease, 2020)

Infection and colonization by Corynebacterium pseudodiphtheriticum: a 9-year observational study in a university central hospital - Sofia R. Valdoleiros; Catarina Sousa Neves; João Abranches Carvalho; Celina Gonçalves; Paulo Pereira; Olga Vasconcelos; Ana Paula Castro; Maria Helena Ramos (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Production of Value-Added Microbial Metabolites: Oleaginous Fungus as a Tool for Valorization of Dairy By-products - Carolina A. Braz; Ana K. F. Carvalho; Heitor B. S. Bento; Cristiano E. R. Reis; Heizir F. De Castro (BioEnergy Research, 2020)

Astronium fraxinifolium Schott Exerts Leishmanicidal Activity by Providing a Classically Polarized Profile in Infected Macrophages - Milena Aguiar Braga; Raphael de Oliveira Rodrigues; Juliana Navarro Ueda Yaochite; Greyce Luri Sasahara; Flávia Almeida Santos; Francisco Rafael Marciano Fonseca; Naya Lucia de Castro Rodrigues; Maria Jânia Teixeira; João Tavares Calixto Junior; Ana Livya Moreira Rodrigues; Selene Maia de Morais; Aparecida Tiemi Nagao-Dias (Acta Parasitologica, 2020)

As time goes by: 20 years of changes in the aquatic macroinvertebrate metacommunity of Mediterranean river networks - Miguel Cañedo‐Argüelles; Cayetano Gutiérrez‐Cánovas; Raúl Acosta; Daniel Castro‐López; Núria Cid; Pau Fortuño; Antoni Munné; Cesc Múrria; Ana Rita Pimentão; Romain Sarremejane; Maria Soria; Pol Tarrats; et al. (Journal of Biogeography, 2020)
Aim To analyse temporal metacommunity dynamics in river networks in relation to hydrological conditions and dispersal. Location Fifteen river reaches from the Llobregat, Besòs and Foix catchments in the North‐Eastern Iberian Peninsula. Taxon Aquatic macroinvertebrates belonging to 99 different families. Methods We sampled aquatic macroinvertebrate communities during spring in 20 consecutive years. We built two environmental distances (one related with water chemistry and another one with river flow regime) and two spatial distances (network distance and topographic distance). Then we used Mantel tests (accounting for spatial autocorrelation) to relate macroinvertebrate dissimilarity with environmental and spatial distances. Additionally, we determined the dry and wet years using the Standardized Precipitation Index (SPI) and we classified macroinvertebrate families based on their ability to fly and to drift. Finally, we ran a linear regression model including the correlation value ( r ) of each Mantel test as response variable and distance type (environmental or spatial), SPI, dispersal mode, their pairwise interactions and a three‐way interaction as predictor variables. Results Metacommunity organization varied over time and it was significantly affected by precipitation, which can be related to river network connectivity. The environmental filters, mainly the flow regime, were generally more important than the spatial filters in explaining community dissimilarity over the study period. However, this depended on the dispersal abilities of the organisms. Network fragmentation due to flow intermittence during the dry years significantly reduced the dispersal capacity of strong aerial dispersers, leading to spatially structured metacommunities. For strong drift dispersers, community dissimilarity patterns were generally best explained by environmental filters regardless of SPI. Main conclusions A significant temporal variation in metacommunity organization can be expected in highly dynamic systems (e.g. Mediterranean rivers) and it might depend on the dispersal modes and abilities of the organisms, since they determine the response to changes in environmental and landscape filters.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Oceanographic Determinants of the Abundance of Common Dolphins (Delphinus delphis) in the South of Portugal - Joana Castro; Ana Couto; Francisco O. Borges; André Cid; Marina I. Laborde; Heidi C. Pearson; Rui Rosa (Oceans, 2020)
Off mainland Portugal, the common dolphin (Delphinus delphis) is the most sighted cetacean, although information on this species is limited. The Atlantic coast of Southern Portugal is characterized by an intense wind-driven upwelling, creating ideal conditions for common dolphins. Using data collected aboard whale-watching boats (1929 sightings and 4548 h effort during 2010–2014), this study aims to understand the relationships between abundance rates (AR) of dolphins of different age classes (adults, juveniles, calves and newborns) and oceanographic [chlorophyll a (Chl-a) and sea surface temperature (SST)] variables. Over 70% of the groups contained immature animals. The AR of adults was negatively related with Chl-a, but not related to SST values. The AR of juveniles was positively related with SST. For calves and newborns, although the relationship between SST and AR is similar to that observed for juveniles, the effect could not be distinguished from zero. There was no relationship between Chl-a levels and the AR of juveniles, calves and newborns. These results corroborate previous findings that common dolphins tend to occur in highly productive areas demonstrating linkages between their abundance and oceanographic variables, and that this region may be a potential nursery ground.

Protective Effects of Agmatine Against Corticosterone-Induced Impairment on Hippocampal mTOR Signaling and Cell Death - Gislaine Olescowicz; Tuane B. Sampaio; Cristine de Paula Nascimento-Castro; Patricia S. Brocardo; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues (Neurotoxicity Research, 2020)

Heat-related mortality at the beginning of the twenty-first century in Rio de Janeiro, Brazil - João L. Geirinhas; Ana Russo; Renata Libonati; Ricardo M. Trigo; Lucas C. O. Castro; Leonardo F. Peres; Mônica de Avelar F. M. Magalhães; Baltazar Nunes (International Journal of Biometeorology, 2020)

Coral reef resilience to thermal stress in the Eastern Tropical Pacific - Mauricio Romero‐Torres; Alberto Acosta; Ana M. Palacio‐Castro; Eric A. Treml; Fernando A. Zapata; David A. Paz‐García; James W. Porter (Global Change Biology, 2020)
Coral reefs worldwide are threatened by thermal stress caused by climate change. Especially devastating periods of coral loss frequently occur during El Niño‐Southern Oscillation (ENSO) events originating in the Eastern Tropical Pacific (ETP). El Niño‐induced thermal stress is considered the primary threat to ETP coral reefs. An increase in the frequency and intensity of ENSO events predicted in the coming decades threatens a pan‐tropical collapse of coral reefs. During the 1982–1983 El Niño, most reefs in the Galapagos Islands collapsed, and many more in the region were decimated by massive coral bleaching and mortality. However, after repeated thermal stress disturbances, such as those caused by the 1997–1998 El Niño, ETP corals reefs have demonstrated regional persistence and resiliency. Using a 44 year dataset (1970–2014) of live coral cover from the ETP, we assess whether ETP reefs exhibit the same decline as seen globally for other reefs. Also, we compare the ETP live coral cover rate of change with data from the maximum Degree Heating Weeks experienced by these reefs to assess the role of thermal stress on coral reef survival. We find that during the period 1970–2014, ETP coral cover exhibited temporary reductions following major ENSO events, but no overall decline. Further, we find that ETP reef recovery patterns allow coral to persist under these El Niño‐stressed conditions, often recovering from these events in 10–15 years. Accumulative heat stress explains 31% of the overall annual rate of change of living coral cover in the ETP. This suggests that ETP coral reefs have adapted to thermal extremes to date, and may have the ability to adapt to near‐term future climate‐change thermal anomalies. These findings for ETP reef resilience may provide general insights for the future of coral reef survival and recovery elsewhere under intensifying El Niño scenarios.

Enzymatic Hydrolysis of Chicken Viscera to Obtain Added-Value Protein Hydrolysates with Antioxidant and Antihypertensive Properties - Jessika Gonçalves dos Santos Aguilar; Ana Karoliny Santos de Souza; Ruann Janser Soares de Castro (International Journal of Peptide Research and Therapeutics, 2020)

Magnetic biomonitoring of atmospheric dust using tree leaves of Ficus benjamina in Querétaro (México) - Ana G. Castañeda-Miranda; Marcos A. E. Chaparro; Adolfo Pacheco-Castro; Mauro A. E. Chaparro; Harald N. Böhnel (Environmental Monitoring and Assessment, 2020)

Validated spectrophotometric method for quantification of total triterpenes in plant matrices - Alessandra Moraes Pedrosa; Whocely Victor de Castro; Ana Hortência Fonseca Castro; Joaquim M. Duarte-Almeida (DARU Journal of Pharmaceutical Sciences, 2020)

Shiga Toxin-Producing and Enteroaggregative Escherichia coli in Animal, Foods, and Humans: Pathogenicity Mechanisms, Detection Methods, and Epidemiology - Ana C. C. Paletta; Vinicius S. Castro; Carlos A. Conte-Junior (Current Microbiology, 2020)

The analysis of green roof’s runoff volumes and its water quality in an experimental study in Porto Alegre, Southern Brazil - Andréa Souza Castro; Joel Avruch Goldenfum; André Lopes da Silveira; Ana Luiza Bertani DallAgnol; Larissa Loebens; Carolina Faccio Demarco; Diuliana Leandro; Willian Cézar Nadaleti; Maurizio Silveira Quadro (Environmental Science and Pollution Research, 2020)

Acidithiobacillus ferrianus sp. nov.: an ancestral extremely acidophilic and facultatively anaerobic chemolithoautotroph - Paul R. Norris; Carmen Falagán; Ana Moya-Beltrán; Matías Castro; Raquel Quatrini; D. Barrie Johnson (Extremophiles, 2020)
Strain MG, isolated from an acidic pond sediment on the island of Milos (Greece), is proposed as a novel species of ferrous iron- and sulfur-oxidizing Acidithiobacillus . Currently, four of the eight validated species of this genus oxidize ferrous iron, and strain MG shares many key characteristics with these four, including the capacities for catalyzing the oxidative dissolution of pyrite and for anaerobic growth via ferric iron respiration. Strain MG also grows aerobically on hydrogen and anaerobically on hydrogen coupled to ferric iron reduction. While the 16S rRNA genes of the iron-oxidizing Acidi-thiobacillus species (and strain MG) are located in a distinct phylogenetic clade and are closely related (98–99% 16S rRNA gene identity), genomic relatedness indexes (ANI/dDDH) revealed strong genomic divergence between strain MG and all sequenced type strains of the taxon, and placed MG as the first cultured representative of an ancestral phylotype of iron oxidizing acidithiobacilli. Strain MG is proposed as a novel species, Acidithiobacillus ferrianus sp. nov. The type strain is MG T (= DSM 107098 T = JCM 33084 T ). Similar strains have been found as isolates or indicated by cloned 16S rRNA genes from several mineral sulfide mine sites.

Will the emblematic southern conifer Araucaria angustifolia survive to climate change in Brazil? - Monik Begname Castro; Ana Carolina Maioli Campos Barbosa; Patrícia Vieira Pompeu; Pedro V. Eisenlohr; Gabriel de Assis Pereira; Deborah Mattos Guimarães Apgaua; João Carlos Pires-Oliveira; João Paulo Rodrigues Alves Delfino Barbosa; Marco Aurélio Leite Fontes; Rubens Manoel dos Santos; David Yue Phin Tng (Biodiversity and Conservation, 2020)

Emergence of community-acquired methicillin-resistant Staphylococcus aureus EMRSA-15 clone as the predominant cause of diabetic foot ulcer infections in Portugal - Vanessa Silva; Francisco Almeida; José António Carvalho; Ana Paula Castro; Eugénia Ferreira; Vera Manageiro; María Teresa Tejedor-Junco; Manuela Caniça; Gilberto Igrejas; Patrícia Poeta (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Evaluation of seaweed extracts for the control of the Asian citrus psyllid Diaphorina citri - Ana Laura González-Castro; Mauricio Muñoz-Ochoa; Gustavo Hernández-Carmona; Juan Manuel López-Vivas (Journal of Applied Phycology, 2019)

Central and peripheral nervous system involvement in Zika virus infection in a child - Paula Eillanny Silva Marinho; Pedro Paulo Martins Alvarenga; Mauricio Teixeira Lima; Adriana de Souza Andrade; Talitah Michel Sanchez Candiani; Ana Paula Correa Crispim; Mirela Cristina Soares Gasparini; Fabrizia Santos Castro; Aline Zocrato Alves de Sousa; Eisler Cristiane Carvalho Viegas; Danilo Bretas de Oliveira; Paulo Pereira Christo; et al. (Journal of NeuroVirology, 2019)

Climate change impact on a wine‐producing region using a dynamical downscaling approach: Climate parameters, bioclimatic indices and extreme indices - Daniel Blanco‐Ward; Alexandra Monteiro; Myriam Lopes; Carlos Borrego; Carlos Silveira; Carolina Viceto; Alfredo Rocha; António Ribeiro; João Andrade; Manuel Feliciano; João Castro; David Barreales; et al. (International Journal of Climatology, 2019)
Climate change is of major relevance to wine production as most of the wine‐growing regions of the world are located within relatively narrow latitudinal bands with average growing‐season temperatures (GSTs) limited to 13–21°C. This study focuses on the incidence of climate variables and indices that are relevant both for climate change assessment and for grape production, with emphasis on grapevine bioclimatic indices and extreme events (e.g., cold waves, storms, heatwaves). Dynamical downscaling of European Reanalysis‐Interim and Max Planck Institute Earth System low‐resolution global simulations forced with a Representative Concentration Pathway 8.5 (RCP8.5) greenhouse gas emission scenario was performed with the Weather Research and Forecast (WRF) model to a regional scale including the Douro Valley of Portugal for recent‐past (1986–2005) and future periods (2046–2065, 2081–2100). The number, duration and intensity of events were superimposed over critical phenological phases estimated by using a specific local grapevine varietal phenological model in order to assess their positive or negative implications for wine production in the region. An assessment of the relevance of climate parameters and indices and their progression in recent‐past and future climate scenarios with regard to the potential impact on wine production was performed. Results indicate a positive relation between higher growing‐season heat accumulations and greater vintage yields. A moderate incidence of very hot days (daily maximum temperature above 35°C) and drought from pre‐ véraison phenological conditions have a positive association with vintage ratings. However, the mid‐ and long‐term WRF‐MPI RCP8.5 future climate scenarios reveal shifts to warmer and drier conditions, with the mean GST not remaining within range for quality wine production in the long‐term future climate scenario. These results indicate potential impacts that suggest a range of strategies to maintain wine production and quality in the region.

High spatial resolution climatology of drought events for Spain: 1961–2014 - Fernando Domínguez‐Castro; Sergio M. Vicente‐Serrano; Miquel Tomás‐Burguera; Marina Peña‐Gallardo; Santiago Beguería; Ahmed El Kenawy; Yolanda Luna; Ana Morata (International Journal of Climatology, 2019)
This study characterizes the climatology of drought events over the mainland Spain and the Balearic Islands using high‐resolution (1.21 km 2 ) meteorological data from 1961 to 2014. The climatology of drought was assessed based on two widely‐recognized drought indices: the Standardized Precipitation Index (SPI) and the Standardized Precipitation‐Evapotranspiration Index (SPEI), considering four different timescales (1‐, 3‐, 6‐ and 12‐months). Drought events were simply defined as sequences of months with negative values of the indices. We analysed the spatial and temporal variability of the frequency, duration and magnitude of the drought events. In general, the frequency of drought events is higher in the northern than in the southern regions. Conversely, the average duration and magnitude of the drought events in central and southwestern regions duplicate those recorded in northern areas. Although drought characteristics exhibit a general north–south gradient irrespective of the drought timescale and the drought index analysed, we found important spatial differences in terms of both drought duration and severity. As opposed to the SPI, the SPEI shows, on average, higher drought durations and magnitudes at 1‐, 3‐ and 6‐months timescales. Albeit of the absence of significant temporal changes in drought duration or magnitude at the regional scale, a nonsignificant tendency toward higher drought duration and magnitude is observed over the majority of Spain. Our result provide valuable guidance to stakeholders and decision‐makers on detecting, monitoring and adapting to drought impacts at local, regional and national scale in Spain.

Neurocognitive Impairment in mdx Mice - Clarissa M. Comim; Letícia Ventura; Viviane Freiberger; Paula Dias; Daiane Bragagnolo; Matheus L. Dutra; Ricardo A. Amaral; Ana Lucia S. Camargo-Fagundes; Patrícia A. Reis; Hugo C. Castro-Faria-Neto; Mariz Vainzof; Maria I. Rosa (Molecular Neurobiology, 2019)

Papaver rhoeas L. mapping with cokriging using UAV imagery - Montserrat Jurado-Expósito; Ana Isabel de Castro; Jorge Torres-Sánchez; Francisco Manuel Jiménez-Brenes; Francisca López-Granados (Precision Agriculture, 2019)

Biofilm production and distribution of pilus variants among Streptococcus agalactiae isolated from human and animal sources - Danielle Cristina Santos Silva Alvim; Ana Flávia Martinho Ferreira; Matheus Amaral Leal; Laura Maria Andrade Oliveira; Ana Maria Nunes Botelho; Ana Caroline Nunes Botelho; Agnes Marie Sá Figueiredo; Sergio Eduardo Longo Fracalanzza; Lucia Martins Teixeira; Tatiana Castro Abreu Pinto (Biofouling, 2019)

Reference genes for real-time RT-PCR expression studies in an Antarctic Pseudomonas exposed to different temperature conditions - César X. García-Laviña; Susana Castro-Sowinski; Ana Ramón (Extremophiles, 2019)

Virulence potential of Corynebacterium striatum towards Caenorhabditis elegans - Cassius de Souza; Liliane Simpson-Louredo; Higor Franceschi Mota; Yuri Vieira Faria; Fellipe de Oliveira Cabral; Sabrina dos Santos Colodette; Maria E. Freire Castro Canellas; Andrezza do Espirito Santo Cucinelli; Maria das Graças de Luna; Cintia da Silva Santos; Lílian de Oliveira Moreira; Ana Luíza Mattos-Guaraldi (Antonie van Leeuwenhoek, 2019)

Septic arthritis incidence and risk factors: a 5-year cross-sectional study - Inês Rego de Figueiredo; Rita Vieira Alves; Sara Guerreiro Castro; Ana Margarda Antunes; Heidi Gruner; António Panarra (Infectious Diseases, 2019)

Protective effect of glycerol and PEG-methyl ether methacrylate coatings on viability of alginate-immobilized Synechococcus elongatus after cold storage - M. del Pilar Sánchez-Saavedra; Ceres Anabel Molina-Cárdenas; Fátima Yadira Castro-Ochoa; Ana B. Castro-Ceseña (Journal of Applied Phycology, 2019)

ERP Source Analysis Guided by fMRI During Familiar Face Processing - Maria A. Bobes; Agustin Lage-Castellanos; Ela I. Olivares; Jhoanna Perez Hidalgo-Gato; Jaime Iglesias; Ana Maria Castro-Laguardia; Pedro Valdes-Sosa (Brain Topography, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Bioconversion of Chicken Feather Meal by Aspergillus niger: Simultaneous Enzymes Production Using a Cost-Effective Feedstock Under Solid State Fermentation - Cassio Carmo de Oliveira; Ana Karoliny Santos de Souza; Ruann Janser Soares de Castro (Indian Journal of Microbiology, 2019)

The mycma_1113 Gene from Mycobacterium abscessus subsp. massiliense is Related to Siderophore Synthesis - Fábio Muniz de Oliveira; Viviane Lopes Rocha Corrêa; André França Corrêa; Adeliane Castro da Costa; Victor Oliveira Procopio; Ana Paula Junqueira-Kipnis; André Kipnis (Indian Journal of Microbiology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Growth of Typha domingensis as related to leaf physiological and anatomical modifications under drought conditions - Yasmini da Cunha Cruz; Ana Lívia Martins Scarpa; Marcio Paulo Pereira; Evaristo Mauro de Castro; Fabricio José Pereira (Acta Physiologiae Plantarum, 2019)

Vegetable oil and carbohydrate-rich diets marginally affected intestine histomorphology, digestive enzymes activities, and gut microbiota of gilthead sea bream juveniles - Carolina Castro; Ana Couto; Alexandre F. Diógenes; Geneviève Corraze; Stéphane Panserat; Cláudia R. Serra; Aires Oliva-Teles (Fish Physiology and Biochemistry, 2019)

A Watermelon mosaic virus clone tagged with the yellow visual maker phytoene synthase facilitates scoring infectivity in melon breeding programs - Verónica Aragonés; Ana Pérez-de-Castro; Teresa Cordero; Jaime Cebolla-Cornejo; Carmelo López; Belén Picó; José-Antonio Daròs (European Journal of Plant Pathology, 2019)

Two epizootic Perkinsus spp. events in commercial oyster farms at Santa Catarina, Brazil - Ana C. Luz Cunha; Vitor de A. Pontinha; Maria Alcina M. de Castro; Simone Sühnel; Sthefanie C. Medeiros; Ângela M. Moura da Luz; Ricardo Harakava; Leonardo Tachibana; Danielle F. Mello; Naissa M. Danielli; Alcir L. Dafre; Aimê R. M. Magalhães; et al. (Journal of Fish Diseases, 2019)
Perkinsus spp. have been detected in various bivalve species from north‐east Brazil. Santa Catarina is a South Brasil state with the highest national oyster production. Considering the pathogenicity of some Perkinsus spp., a study was carried out to survey perkinsosis in two oyster species cultured in this State, the mangrove oyster Crassostrea gasar and the Pacific oyster Crassostrea gigas . Sampling involved eight sites along the state coast, and oyster sampling was collected during the period between January 2013 and December 2014. For the detection of Perkinsus , Ray's fluid thioglycollate medium (RFTM) and histology were used, and for the identification of the species, PCR and DNA sequencing were used. Perkinsus spp. was found by RFTM in C. gigas and C. gasar from São Francisco do Sul. This pathology was also detected in C. gasar from Balneário Barra do Sul both, by RFTM and histology. Perkinsus marinus was identified in C. gigas and C. gasar from São Francisco do Sul and Perkinsus beihaiensis in C. gasar from Balneário Barra do Sul. This is the first report of P. marinus in C. gigas from South America. Results of this preliminary study suggest that both oyster species tolerate the species of Perkinsus identified, without suffering heavy lesions.

Exploitation of new endophytic bacteria and their ability to promote sugarcane growth and nitrogen nutrition - Adriana Parada Dias da Silveira; Raquel de Paula Freitas Iório; Fernanda Castro Correia Marcos; Ana Olívia Fernandes; Silvana Aparecida Creste Dias de Souza; Eiko Eurya Kuramae; Matheus Aparecido Pereira Cipriano (Antonie van Leeuwenhoek, 2019)

Climate change resilience of a globally important sea turtle nesting population - Ana R. Patrício; Miguel R. Varela; Castro Barbosa; Annette C. Broderick; Paulo Catry; Lucy A. Hawkes; Aissa Regalla; Brendan J. Godley (Global Change Biology, 2019)
Few studies have looked into climate change resilience of populations of wild animals. We use a model higher vertebrate, the green sea turtle, as its life history is fundamentally affected by climatic conditions, including temperature‐dependent sex determination and obligate use of beaches subject to sea level rise ( SLR ). We use empirical data from a globally important population in West Africa to assess resistance to climate change within a quantitative framework. We project 200 years of primary sex ratios (1900–2100) and create a digital elevation model of the nesting beach to estimate impacts of projected SLR . Primary sex ratio is currently almost balanced, with 52% of hatchlings produced being female. Under IPCC models, we predict: (a) an increase in the proportion of females by 2100 to 76%–93%, but cooler temperatures, both at the end of the nesting season and in shaded areas, will guarantee male hatchling production; (b) IPCC SLR scenarios will lead to 33.4%–43.0% loss of the current nesting area; (c) climate change will contribute to population growth through population feminization, with 32%–64% more nesting females expected by 2120; (d) as incubation temperatures approach lethal levels, however, the population will cease growing and start to decline. Taken together with other factors (degree of foraging plasticity, rookery size and trajectory, and prevailing threats), this nesting population should resist climate change until 2100, and the availability of spatial and temporal microrefugia indicates potential for resilience to predicted impacts, through the evolution of nest site selection or changes in nesting phenology. This represents the most comprehensive assessment to date of climate change resilience of a marine reptile using the most up‐to‐date IPCC models, appraising the impacts of temperature and SLR , integrated with additional ecological and demographic parameters. We suggest this as a framework for other populations, species and taxa.

Genetically based phenotypic differentiation between native and introduced tetraploids of Oxalis pes-caprae - Daniela Tavares; João Loureiro; Ana Martins; Mariana Castro; Sergio Roiloa; Sílvia Castro (Biological Invasions, 2019)

Effects of hydrodynamic conditions and feeding period on size, growth and cirral behavior of the stalked-barnacle Pollicipes pollicipes - Maria Inês Seabra; Maria Santos; David Jacinto; David Mateus; Joana Fernandes; Ana Pombo; Teresa Silva; João Castro; Teresa Cruz (Frontiers in Marine Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Synthesis, antitrypanosomal activity and molecular docking studies of pyrimidine derivatives - Sebastião José de Melo; Zenaide Severina do Monte; Aline Caroline da Silva Santos; Ana Catarina Cristovão Silva; Luiz Felipe Gomes Rebello Ferreira; Marcelo Zaldini Hernandes; Ricardo Oliveira Silva; Emerson Peter da Silva Falcão; Maria Carolina Accioly Brelaz-de-Castro; Rajendra M. Srivastava; Valeria Rêgo Alves Pereira (Medicinal Chemistry Research, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Prevalence of naturally occurring amino acid substitutions associated with resistance to hepatitis C virus NS3/NS4A protease inhibitors in São Paulo state - Regina Célia Moreira; Ana Paula de Torres Santos; Gaspar Lisboa-Neto; Maria Cássia Jacintho Mendes-Corrêa; Marcilio Figueiredo Lemos; Fernanda Mello Malta; Rúbia Anita Ferraz Santana; Gregório Tadeu Fernando Dastoli; Vanessa Fusco Duarte de Castro; João Renato Rebello Pinho (Archives of Virology, 2018)

Production and characterization of lectin from Bauhinia holophylla (Fabaceae:Cercideae) calli - Ana Hortência Fonseca Castro; Harley da Silva Tavares; Sarah Ribeiro Furtado Pereira; Paulo Afonso Granjeiro; José Antônio da Silva; Alexsandro Sobreira Galdino (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Brain-Derived Neurotrophic Factor Prevents Depressive-Like Behaviors in Early-Symptomatic YAC128 Huntington’s Disease Mice - Victor Silva da Fonsêca; André R. da Silva Colla; Cristine de Paula Nascimento-Castro; Evelini Plácido; Julia Macedo Rosa; Marcelo Farina; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues; Patricia S. Brocardo (Molecular Neurobiology, 2018)

Characterization of esterase activity from an Acetomicrobium hydrogeniformans enzyme with high structural stability in extreme conditions - Patricia S. Kumagai; Raissa F. Gutierrez; Jose L. S. Lopes; Julia M. Martins; David M. Jameson; Aline M. Castro; Luiz F. Martins; Ricardo DeMarco; Nelma R. S. Bossolan; B. A. Wallace; Ana P. U. Araujo (Extremophiles, 2018)

The potential for RGB images obtained using unmanned aerial vehicle to assess and predict yield in sugarcane fields - Guilherme Martineli Sanches; Daniel Garbellini Duft; Oriel Tiago Kölln; Ana Claudia dos Santos Luciano; Sérgio Gustavo Quassi De Castro; Fábio Makoto Okuno; Henrique Coutinho Junqueira Franco (International Journal of Remote Sensing, 2018)

Smooth hammerhead sharks (Sphyrna zygaena) observed off the Portuguese southern coast - Ana Couto; Nuno Queiroz; James T. Ketchum; Eduardo Sampaio; Miguel Furtado; André A. Cid; Joana Castro; Rui Rosa (Environmental Biology of Fishes, 2018)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

Genistein modulates the expression of Toll-like receptors in experimental autoimmune encephalomyelitis - Alyria Teixeira Dias; Sandra Bertelli Ribeiro de Castro; Caio César de Souza Alves; Marcilene Gomes Evangelista; Luan Cristian da Silva; Daniele Ribeiro de Lima Reis; Marco Antonio Machado; Maria Aparecida Juliano; Ana Paula Ferreira (Inflammation Research, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A morphological database for 606 Colombian bird species - Paola Montoya; Mailyn A. Gonzalez; Elkin A. Tenorio; Juan Pablo López‐Ordóñez; Alejandro Pinto Gómez; Diego Cueva; Aldemar A. Acevedo Rincón; Camilo Angarita Yanes; Héctor Manuel Arango Martínez; Orlando Armesto; Jefry S. Betancur; Angela Caguazango Castro; et al. (Ecology, 2018)
Colombia is the country with the highest bird diversity in the world. Despite active research in ornithology, compelling morphological information of most bird species is still sparse. However, morphological information is the baseline to understand how species respond to environmental variation and how ecosystems respond to species loss. As part of a national initiative, the Instituto Alexander von Humboldt in collaboration with 12 Colombian institutions and seven biological collections, measured up to 15 morphological traits of 9,892 individuals corresponding to 606 species: 3,492 from individuals captured in field and 6,400 from museum specimens. Species measured are mainly distributed in high Andean forest, páramo, and wetland ecosystems. Seven ornithological collections in Colombia and 18 páramo complexes throughout Colombia were visited from 2013 to 2015. The morphological traits involved measurements from bill (total and exposed culmen, bill width and depth), wing (length, area, wingspan, and the distance between longest primary and longest secondary), tail (length and shape), tarsus (length), hallux (length and claw hallux), and mass. The number of measured specimens per species was variable, ranging from 1 to 321 individuals with a median of four individuals per species. Overall, this database gathered morphological information for >30% of Colombian bird diversity. No copyright, proprietary, or cost restrictions apply; the data should be cited appropriately when used.

Water-soluble inorganic ions of size-differentiated atmospheric particles from a suburban site of Mexico City - Telma Castro; Oscar Peralta; Dara Salcedo; José Santos; María I. Saavedra; María L. Espinoza; Alejandro Salcido; Ana-Teresa Celada-Murillo; Susana Carreón-Sierra; Harry Álvarez-Ospina; Giovanni Carabali; Valter Barrera; et al. (Journal of Atmospheric Chemistry, 2018)

Effects of nitrogen source and irradiance on Porphyridium cruentum - M. del Pilar Sánchez-Saavedra; Fátima Y. Castro-Ochoa; Viridiana Margarita Nava-Ruiz; Duahmet A. Ruiz-Güereca; Ana Laura Villagómez-Aranda; Fabián Siqueiros-Vargas; Ceres A. Molina-Cárdenas (Journal of Applied Phycology, 2018)

Morphological characterization of the cucumber (Cucumis sativus L.) collection of the COMAV’s Genebank - José Vicente Valcárcel; Rosa María Peiró; Ana Pérez-de-Castro; María José Díez (Genetic Resources and Crop Evolution, 2018)

Usefulness of a single-assay chemiluminescence test (Tularaemia VIRCLIA IgG + IgM monotest) for the diagnosis of human tularemia. Comparison of five serological tests - África Cubero; Carlos Durántez; Ana Almaraz; Luis Fernández-Lago; María P. Gutiérrez; María J. Castro; Miguel A. Bratos; María Simarro; Gabriel A. March; Antonio Orduña (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Chemical composition, antioxidant and cytotoxic activities of extracts from the leaves of Smilax brasiliensis Sprengel (Smilacaceae) - Paula Avelar Amado; Vany Ferraz; Denise Brentan da Silva; Carlos Alexandre Carollo; Ana Hortência Fonsêca Castro; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2018)

Structural and physiological responses of Halodule wrightii to ocean acidification - Geniane Schneider; Paulo Antunes Horta; Emiliano Nicolas Calderon; Clovis Castro; Adalto Bianchini; Camilla Reis Augusto da Silva; Isabel Brandalise; José Bonomi Barufi; João Silva; Ana Claudia Rodrigues (Protoplasma, 2018)

Arsenic toxicity in soybean alleviated by a symbiotic species of Bradyrhizobium - Eliana Bianucci; Andrea Godoy; Ana Furlan; Juan Manuel Peralta; Luis E. Hernández; Ramón O. Carpena-Ruiz; Stella Castro (Symbiosis, 2018)

The future of fish passage science, engineering, and practice - Ana T. Silva; Martyn C. Lucas; Theodore Castro‐Santos; Christos Katopodis; Lee J. Baumgartner; Jason D. Thiem; Kim Aarestrup; Paulo S. Pompeu; Gordon C. O'Brien; Douglas C. Braun; Nicholas J. Burnett; David Z. Zhu; et al. (Fish and Fisheries, 2018)
Much effort has been devoted to developing, constructing and refining fish passage facilities to enable target species to pass barriers on fluvial systems, and yet, fishway science, engineering and practice remain imperfect. In this review, 17 experts from different fish passage research fields (i.e., biology, ecology, physiology, ecohydraulics, engineering) and from different continents (i.e., North and South America, Europe, Africa, Australia) identified knowledge gaps and provided a roadmap for research priorities and technical developments. Once dominated by an engineering‐focused approach, fishway science today involves a wide range of disciplines from fish behaviour to socioeconomics to complex modelling of passage prioritization options in river networks. River barrier impacts on fish migration and dispersal are currently better understood than historically, but basic ecological knowledge underpinning the need for effective fish passage in many regions of the world, including in biodiversity hotspots (e.g., equatorial Africa, South‐East Asia), remains largely unknown. Designing efficient fishways, with minimal passage delay and post‐passage impacts, requires adaptive management and continued innovation. While the use of fishways in river restoration demands a transition towards fish passage at the community scale, advances in selective fishways are also needed to manage invasive fish colonization. Because of the erroneous view in some literature and communities of practice that fish passage is largely a proven technology, improved international collaboration, information sharing, method standardization and multidisciplinary training are needed. Further development of regional expertise is needed in South America, Asia and Africa where hydropower dams are currently being planned and constructed.

Active packaging as a solution for lipid oxidation - Frederico Castro; Mariana Andrade; Ana Sanches Silva; Fernanda Vilarinho (Frontiers in Marine Science, 2018)

Effect of food density and hydrodynamic conditions on the survival and growth of the stalked barnacle Pollicipes pollicipes - Ana Torres; Ana Pombo; Joana Fernandes; Daniela Nobre; Maria Seabra; Teresa Silva; João Castro; Sofia Franco; Anthony Clare; David Jacinto; Teresa Cruz (Frontiers in Marine Science, 2018)

Evaluation of antibacterial activity of the bark and leaf extracts of Brosimum gaudichaudii Trécul against multidrug resistant strains - Joelma da Costa Borges; Michele Cezimbra Perim; Rodrigo Orlandini de Castro; Thiago Antônio de Sousa Araújo; Tadeu José da Silva Peixoto Sobrinho; Ana Carolina Oliveira da Silva; Sandra Maria Botelho Mariano; Solange Cristina Carreiro; Maria Cristina da Silva Pranchevicius (Natural Product Research, 2017)

Soil Infiltration, Permeability, and Rock Fracturing Assessment to Establish Water Flow Patterns in a Mine with Acid Mine Drainage - Ana Alejandrina Castro-Rodríguez; María Guadalupe Isidro-Angeles; Angeles Neri-Oliva; Osvaldo Flores-Castrellón; Javier Arellano-Gil; José Enrique Santos-Jallath (Mine Water and the Environment, 2017)

Candida albicans Germ-Tube Antibody: Evaluation of a New Automatic Assay for Diagnosing Invasive Candidiasis in ICU Patients - Manuel Parra-Sánchez; Ismail Zakariya-Yousef Breval; Carmen Castro Méndez; Silvia García-Rey; Ana Loza Vazquez; Alejandro Úbeda Iglesias; Desiree Macías Guerrero; Ana Romero Mejías; Cristobal León Gil; Estrella Martín-Mazuelos (Mycopathologia, 2017)

A fucan of a brown seaweed and its antitumoral property on HT-29 and immunomodulatory activity in murine RAW 264.7 macrophage cell line - Thuane de Sousa Pinheiro; Marilia da S. Nascimento Santos; Luiza Sheyla E. P. Will Castro; Almino Afonso de O. Paiva; Luciana G. Alves; Ana Katarina M. Cruz; Leonardo Thiago D. B. Nobre; Monique Gabriela das C. F. Alves; Edda Lisboa Leite (Journal of Applied Phycology, 2017)

Seroprevalence and risk factors for leptospirosis in cattle, sheep, and goats at consorted rearing from the State of Piauí, northeastern Brazil - Ângela Piauilino Campos; Dayane Francisca Higino Miranda; Huanna Waleska Soares Rodrigues; Micherlene da Silva Carneiro Lustosa; Gustavo Henrique Chaves Martins; Ana Lys Bezerra Barradas Mineiro; Vanessa Castro; Sérgio Santos Azevedo; Silvana Maria Medeiros de Sousa Silva (Tropical Animal Health and Production, 2017)

Case Series Study of Invasive Pulmonary Aspergillosis - Ana I. Aller-García; Carmen Castro-Méndez; Ana Alastruey-Izquierdo; Elena M. Marín-Martínez; Ismail Zakariya-Yousef Breval; Carmen Couto-Caro; Juan C. López-Marín; Nicolás Peña-Griñán; Maite Ruiz de Pipaon; Ana M. Romero-Mejías; Estrella Martín-Mazuelos (Mycopathologia, 2017)

Occupational and life-style factors-acquired mutagenicity in agric-workers of northeastern Brazil - Tatiana Vieira Souza Chaves; Muhammad Torequl Islam; Manoel Odoríco de Moraes; Marcus Vinícius Oliveira Barros de Alencar; Débora Cássia Vieira Gomes; Rodrigo Mendes de Carvalho; Sharbel Weider Maluf; Fabrício Pires de Moura do Amaral; Márcia Fernanda Correia Jardim Paz; Gilberto Santos Cerqueira; Hercília Maria Lins Rolim; João Marcelo de Castro e Sousa; et al. (Environmental Science and Pollution Research, 2017)

Cytotoxicity and genotoxicity of Guaribas river water (Piauí, Brazil), influenced by anthropogenic action - João Marcelo de Castro e Sousa; Ana Paula Peron; Louridânya da Silva e Sousa; Mércia de Moura Holanda; Ataíde de Macedo Vieira Lima; Vitor Alves de Oliveira; Felipe Cavalcanti Carneiro da Silva; Leonardo Henrique Guedes de Morais Lima; Leomá Albuquerque Matos; Sandra Maria Mendes de Moura Dantas; Raí Pablo Sousa de Aguiar; Muhammad Torequl Islam; et al. (Environmental Monitoring and Assessment, 2017)

Anaerobic Metabolism in T4 Acanthamoeba Genotype - Daniella de Sousa Mendes Moreira Alves; Luciano Moreira Alves; Tatiane Luiza da Costa; Ana Maria de Castro; Marina Clare Vinaud (Current Microbiology, 2017)

Chromosomal characteristics of rDNA in a conserved karyotype of two Sternopygus macrurus (Gymnotiformes: Sternopygidae) populations from upper Paraná River basin - Carlos Alexandre Fernandes; Lucas Baumgärtner; Leonardo Marcel Paiz; Vladimir Pavan Margarido; Ana Luiza de Brito Portela-Castro (Biologia, 2017)

Life cycle assessment from early development stages: the case of gelatin extracted from tilapia residues - Ana Paula C. Sampaio; Men de Sá M. de Sousa Filho; Ana Lídia A. Castro; Maria Cléa B. de Figueirêdo (The International Journal of Life Cycle Assessment, 2017)

Characterization of bacterial communities from Masseiras, a unique Portuguese greenhouse agricultural system - Cristina Becerra-Castro; Ana Rita Lopes; Sara Teixeira; M. Elisabete F. Silva; Elisabete Pimenta; Célia M. Manaia; Olga C. Nunes (Antonie van Leeuwenhoek, 2017)

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Jairo Patiño; Robert J. Whittaker; Paulo A.V. Borges; José María Fernández‐Palacios; Claudine Ah‐Peng; Miguel B. Araújo; Sergio P. Ávila; Pedro Cardoso; Josselin Cornuault; Erik J. de Boer; Lea de Nascimento; Artur Gil; et al. (Journal of Biogeography, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography , by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross‐disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.

Skeletal dissolution kinetics and mechanical tests in response to morphology among coral genera - Orión C. Norzagaray-López; Luis E. Calderon-Aguilera; Ana B. Castro-Ceseña; Gustavo Hirata; José M. Hernández-Ayón (Facies, 2017)

Herbicide 2,4-D: A Review of Toxicity on Non-Target Organisms - Ana Claudia de Castro Marcato; Cleiton Pereira de Souza; Carmem Silvia Fontanetti (Water, Air, & Soil Pollution, 2017)

Identification and genetic characterization of classical swine fever virus isolates in Brazil: a new subgenotype - Marta N. F. Silva; Diogo M. F. Silva; Adriana S. Leite; Ana L. V. Gomes; Antonio C. Freitas; Jose W. Pinheiro-Junior; Roberto S. Castro; Andre L. S. Jesus (Archives of Virology, 2017)

Activity of the endophytic fungi Phlebia sp. and Paecilomyces formosus in decolourisation and the reduction of reactive dyes’ cytotoxicity in fish erythrocytes - Lígia Maria Crubelati Bulla; Julio Cesar Polonio; Ana Luiza de Brito Portela-Castro; Vanessa Kava; João Lúcio Azevedo; João Alencar Pamphile (Environmental Monitoring and Assessment, 2017)

Paratuberculosis in buffaloes in Northeast Brazil - Marilene de Farias Brito; Alessandra dos Santos Belo-Reis; José Diomedes Barbosa; Daniel Guimarães Ubiali; Ana Paula de Castro Pires; Elizabeth Sampaio de Medeiros; Renata Pimentel Bandeira de Melo; Pedro Paulo Feitosa de Albuquerque; Elise Yamasaki; Rinaldo Aparecido Mota (Tropical Animal Health and Production, 2016)

Chemical composition and anti-inflammatory activity of the leaves of Byrsonima verbascifolia - Aline Aparecida Saldanha; Lucas Fernandes do Carmo; Sara Batista do Nascimento; Natália Alves de Matos; Clarice de Carvalho Veloso; Ana Hortência Fonsêca Castro; Ric C. H. De Vos; André Klein; João Máximo de Siqueira; Carlos Alexandre Carollo; Thalita Vieira do Nascimento; Mônica Cristina Toffoli-Kadri; et al. (Journal of Natural Medicines, 2016)

Biological control of the invasive Asian clam, Corbicula fluminea: can predators tame the beast? - Joana Luísa Pereira; Sónia Pinho; Ana Ré; Patricia Ana Costa; Raquel Costa; Fernando Gonçalves; Bruno B. Castro (Hydrobiologia, 2016)

Design of a Water Soluble Fluorescent 3-Hydroxy-4-Pyridinone Ligand Active at Physiological pH Values - Andreia Leite; Ana M. G. Silva; Catarina Coutinho; Luís Cunha-Silva; Baltazar de Castro; Maria Rangel (Journal of Fluorescence, 2016)

Nitrogen oxides and ozone in Portugal: trends and ozone estimation in an urban and a rural site - José Manuel Fernández-Guisuraga; Amaya Castro; Célia Alves; Ana Calvo; Elisabeth Alonso-Blanco; Carlos Blanco-Alegre; Alfredo Rocha; Roberto Fraile (Environmental Science and Pollution Research, 2016)

Toxicity of two fungicides in Daphnia: is it always temperature-dependent? - Ana P. Cuco; Nelson Abrantes; Fernando Gonçalves; Justyna Wolinska; Bruno B. Castro (Ecotoxicology, 2016)

INFRAFRONTIER: a European resource for studying the functional basis of human disease - Michael Raess; Ana Ambrosio de Castro; Valérie Gailus-Durner; Sabine Fessele; Martin Hrabě de Angelis (Mammalian Genome, 2016)

Optimization of entrapment efficiency and evaluation of nutrient removal (N and P) of Synechococcus elongatus in novel core-shell capsules - Ana B. Castro-Ceseña; M. del Pilar Sánchez-Saavedra; Duahmet A. Ruíz-Güereca (Journal of Applied Phycology, 2016)

Accumulation of loganin by genotypes of Palicourea rigida and related differential gene expression as determined by cDNA-SRAP - Mayara Valdevite; Bianca Waléria Bertoni; Silvia Helena Taleb Contini; Suzelei de Castro França; Ana Maria Soares Pereira (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Eliciting effect of jasmonates from Botryosphaeria rhodina enhances coumarin production in Mikania laevigata plants - Miriam Verginia Lourenço; Wellington Soares; Bianca Waleria Bertoni; Ana Paula Oliveira; Sarazete Izidia Vaz Pereira; Ana Maria Soares Pereira; Suzelei Castro Franca (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

The Role of a Catechol-O-Methyltransferase (COMT) Val158Met Genetic Polymorphism in Schizophrenia: A Systematic Review and Updated Meta-analysis on 32,816 Subjects - Thelma Beatriz González-Castro; Yazmin Hernández-Díaz; Isela Esther Juárez-Rojop; María Lilia López-Narváez; Carlos Alfonso Tovilla-Zárate; Ana Fresan (NeuroMolecular Medicine, 2016)

The first meteorological observations at a tropical high elevation site: Antisana, 1846 - Ana Mª M. Farrona; Fernando Domínguez-Castro; Mª Cruz Gallego; José M. Vaquero (Journal of Mountain Science, 2016)

Association of IFNL3 and IFNL4 polymorphisms with hepatitis C virus infection in a population from southeastern Brazil - Ana Catharina de Seixas Santos Nastri; Fernanda de Mello Malta; Márcio Augusto Diniz; Alessandra Yoshino; Kiyoko Abe-Sandes; Sidney Emanuel Batista dos Santos; André de Castro Lyra; Flair José Carrilho; João Renato Rebello Pinho (Archives of Virology, 2016)

Early season weed mapping in sunflower using UAV technology: variability of herbicide treatment maps against weed thresholds - Francisca López-Granados; Jorge Torres-Sánchez; Angélica Serrano-Pérez; Ana I. de Castro; Fco.-Javier Mesas-Carrascosa; José-Manuel Peña (Precision Agriculture, 2016)

Mine land valorization through energy maize production enhanced by the application of plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi - Helena Moreira; Sofia I. A. Pereira; Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Environmental Science and Pollution Research, 2016)

Deficit in digestive capabilities of bamboo shark early stages under climate change - Rui Rosa; Marta Pimentel; Juan G. Galan; Miguel Baptista; Vanessa M. Lopes; Ana Couto; Miguel Guerreiro; Eduardo Sampaio; Joana Castro; Catarina Santos; Ricardo Calado; Tiago Repolho (Marine Biology, 2016)

Phytotoxicity of natural soils using physiological and biochemical endpoints reveals confounding factors: can a weight of evidence tackle uncertainty? - Sara C. Antunes; Bruno B. Castro; Maria Celeste Dias; José Moutinho-Pereira; Carlos M. Correia; Maria T. Claro; Ana Gavina; Conceição Santos; Fernando Gonçalves; Glória Pinto (Journal of Soils and Sediments, 2016)

Effect of glycerol and PEGMA coating on the efficiency of cell holding in alginate immobilized Synechococcus elongatus - Ana B. Castro-Ceseña; M. del Pilar Sánchez-Saavedra (Journal of Applied Phycology, 2016)

Effects of fish oil replacement by vegetable oil blend on digestive enzymes and tissue histomorphology of European sea bass (Dicentrarchus labrax) juveniles - Carolina Castro; Ana Couto; Amalia Pérez-Jiménez; Cláudia R. Serra; Patricia Díaz-Rosales; Rui Fernandes; Geneviève Corraze; Stéphane Panserat; Aires Oliva-Teles (Fish Physiology and Biochemistry, 2016)

The impact of salinity on the symbiosis between Casuarina glauca Sieb. ex Spreng. and N2-fixing Frankia bacteria based on the analysis of Nitrogen and Carbon metabolism - Nuno Duro; Paula Batista-Santos; Mário da Costa; Rodrigo Maia; Isabel V. Castro; Margarida Ramos; José C. Ramalho; Katharina Pawlowski; Cristina Máguas; Ana Ribeiro-Barros (Plant and Soil, 2016)

White anglerfish (Lophius piscatorius) in northern Iberian waters and northernmost Atlantic areas: weight-length relationships and other population parameters from a decade of research. - Landa Jorge; Antolínez Ana; Castro Begoña; Autón Urbano; Hernández Carmen; Dueñas-Liaño Clara; Navarro Maria Rosario; Villamor Begoña (Frontiers in Marine Science, 2016)

Science, technology and society initiative to minimise unwanted catches in European fisheries – the MINOUW Project (EU H2020 RIA) - Rangel Mafalda; Anjos Mariana; Bentes Luis; Borges Teresa; Campos Aida; Castro Margarida; Eichert Morritz; Fonseca Paulo; Gaspar Miguel; Gonçalves Jorge; Guimarães Helena; Marçalo Ana; et al. (Frontiers in Marine Science, 2016)

Is bait worms’ importation an introduction vector for non-indigenous species in Portugal? - Sá Erica; Costa Pedro; Da Fonseca Luis; Alves Ana; Castro Nuno; Cabral Sara; Chainho Paula; Canning-Clode João; Melo Pedro; Pombo Ana; Costa José (Frontiers in Marine Science, 2016)

Polychaete annelids as live bait in Portugal: harvesting activity in estuarine systems - Cabral Sara; Alves Ana; Castro Nuno; Fidalgo E Costa Pedro; Sá Erica; Castro João; Cancela Da Fonseca Luís; Chainho Paula; Canning-Clode João; Picard David; Pombo Ana; Costa José Lino (Frontiers in Marine Science, 2016)

Cell Viability, Mitotic Index and Callus Morphology of Byrsonima verbascifolia (Malpighiaceae) - Raquel Bezerra Chiavegatto; Ana Hortência Fonsêca Castro; Mayra Gonçalves Marçal; Marlúcia Souza Pádua; Eduardo Alves; Vânia Helena Techio (Tropical Plant Biology, 2015)

Erratum to: Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system - Juliana Lenzi; Andre Felipe Rodrigues; Adriana de Sousa Rós; Amanda Blanski de Castro; Daniela Delwing de Lima; Débora Delwing Dal Magro; Ana Lúcia Bertarello Zeni (Metabolic Brain Disease, 2015)

Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system - Juliana Lenzi; Andre Felipe Rodrigues; Adriana de Sousa Rós; Bianca Blanski de Castro; Daniela Delwing de Lima; Débora Delwing Dal Magro; Ana Lúcia Bertarello Zeni (Metabolic Brain Disease, 2015)

Plants of the Cerrado naturally selected by grazing sheep may have potential for inhibiting development of Haemonchus contortus larva - Franciellen Morais-Costa; Ana Cláudia Maia Soares; Gabriela Almeida Bastos; Yule Roberta Ferreira Nunes; Luciana Castro Geraseev; Fernão Castro Braga; Walter dos Santos Lima; Eduardo Robson Duarte (Tropical Animal Health and Production, 2015)

Strontium ranelate analgesia in arthritis models is associated to decreased cytokine release and opioid-dependent mechanisms - Rodolfo de Melo Nunes; Morgana Ramos Martins; Francisco Saraiva da Silva Junior; Ana Caroline Rocha de Melo Leite; Virgínia Claudia Carneiro Girão; Fernando de Queiroz Cunha; Aryana Lushese Lima Feitosa Marinho; Ana Carolina Matias Dinelly Pinto; Francisco Airton Castro Rocha (Inflammation Research, 2015)

Molecular modeling study of a series of amodiaquine analogues with antimalarial activity - Ana Carolina Corrêa de Sousa; Nuria Cirauqui Diaz; Alessandra Mendonça Teles de Souza; Lúcio Mendes Cabral; Helena Carla Castro; Magaly Girão Albuquerque; Carlos Rangel Rodrigues (Medicinal Chemistry Research, 2015)

Atlantic and Mediterranean synoptic drivers of central Spanish juniper growth - Jan Esper; Janine Großjean; Jesús Julio Camarero; Ana I. García-Cervigón; José M. Olano; J. Fidel González-Rouco; Fernando Domínguez-Castro; Ulf Büntgen (Theoretical and Applied Climatology, 2015)

MiR-9 and miR-21 as prognostic biomarkers for recurrence in papillary thyroid cancer - Adriana Sondermann; Flavia Maziero Andreghetto; Ana Carolina Bernardini Moulatlet; Elivane da Silva Victor; Marilia Germanos de Castro; Fábio Daumas Nunes; Lenine Garcia Brandão; Patricia Severino (Clinical & Experimental Metastasis, 2015)

Evaluation of sodium tripolyphosphate-alginate coating and re-calcifying on the entrapment of microalgae in alginate beads - Ana B. Castro-Ceseña; M. del Pilar Sánchez-Saavedra (Journal of Applied Phycology, 2015)

Dispersive liquid–liquid microextraction and HPLC to analyse fluoxetine and metoprolol enantiomers in wastewaters - Ana R. Ribeiro; Virgínia M. F. Gonçalves; Alexandra S. Maia; Cláudia Ribeiro; Paula M. L. Castro; Maria E. Tiritan (Environmental Chemistry Letters, 2015)

Early Invasive Pulmonary Aspergillosis in a Kidney Transplant Recipient Caused by Aspergillus lentulus: First Brazilian Report - Viviane Reis de Azevedo Bastos; Daniel Wagner de Castro Lima Santos; Ana Carolina Barbosa Padovan; Analy Salles Azevedo Melo; Milene de Abreu Mazzolin; Luis Fernando Aranha Camargo; Arnaldo Lopes Colombo (Mycopathologia, 2015)

Liver Biomarkers and Their Applications to Nutritional Interventions in Animal Studies - Cynthia Aparecida de Castro; Manoela Maciel dos Santos Dias; Karina Ana da Silva; Sandra Aparecida dos Reis; Lisiane Lopes da Conceição; Letícia De Nadai Marcon; Luis Fernando de Sousa Moraes; Maria do Carmo Gouveia Peluzio (Exposure and Health, 2015)

Obesogens: molecular signaling pathways in fish - Santos Miguel; Lyssimachou Angeliki; Marques Mónica; Capitão Ana; Fonseca Elza; Ruivo Raquel; Castro Luis (Frontiers in Marine Science, 2015)

Ontogenetic stomach development in catshark Scyliorhinus canicula. - Goncalves Odete; Castro Filipe; Freitas Renata; Ferreira Patricia; Aguas Ana; Barroso Fabio; Mazan Sylvie; Coimbra João; Wilson Jonathan (Frontiers in Marine Science, 2015)

Human T-lymphotropic virus type 2 subtype b in a patient with chronic neurological disorder - Carolina Rosadas; Ana C. P. Vicente; Louise Zanella; Mauro J. Cabral-Castro; José M. Peralta; Marzia Puccioni-Sohler (Journal of NeuroVirology, 2014)

Particulate matter in the indoor and outdoor air of a gymnasium and a fronton - Célia Alves; Ana I. Calvo; Liliana Marques; Amaya Castro; Teresa Nunes; Esther Coz; Roberto Fraile (Environmental Science and Pollution Research, 2014)

Technical Evaluation of Glauconies as Alternative Potassium Fertilizer from the Salamanca Formation, Patagonia, Southwest Argentina - Corina Franzosi; Liliana N. Castro; Ana María Celeda (Natural Resources Research, 2014)

Ethanol-Induced Gastric Injury: Microscopic Analysis of the Protective Effect of Frutalin - Ana Paula Vasconcellos Abdon; Renata Prado Vasconcelos; Carolina Araújo Castro; Marjorie Moreira Guedes; Adriana da Rocha Tomé; André Luiz Herzog Cardoso; Thiago de Melo Santiago; Luciana Magalhães Rebêlo; Renato de Azevedo Moreira; Ana Cristina de Oliveira Monteiro-Moreira; Adriana Rolim Campos (International Journal of Peptide Research and Therapeutics, 2014)

Antioxidant and antifungal activities of Smilax campestris Griseb. (Smilacaceae) - Marcela Isis Morais; Maria Eduarda Amaral Pinto; Sthéfane Guimarães Araújo; Ana Hortência Fonsêca Castro; Joaquim Mauricio Duarte-Almeida; Luiz Henrique Rosa; Carlos Augusto Rosa; Susana Johann; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2014)

Phytomanagement of Cd-contaminated soils using maize (Zea mays L.) assisted by plant growth-promoting rhizobacteria - Helena Moreira; Ana P. G. C. Marques; Albina R. Franco; António O. S. S. Rangel; Paula M. L. Castro (Environmental Science and Pollution Research, 2014)

Coral health rapid assessment in marginal reef sites - Ricardo Rogers; Gabriel de Oliveira Correal; Thiago Cunha de Oliveira; Leonardo Lara de Carvalho; Patrícia Mazurek; Juliana Eymara Fernandes Barbosa; Luciana Chequer; Thaisa Francielle Souza Domingos; Kelly de Andrade Jandre; Luciana Sanches Dourado Leão; Laura de Andrade Moura; Gisele Exel Occhioni; et al. (Marine Biology Research, 2014)

Leptospirosis seroprevalence and risk factors for sheep in Maranhão state, Brazil - Sônia Maria de Carvalho; Ana Lys B. B. Mineiro; Vanessa Castro; Margareth E. Genovez; Sérgio Santos Azevedo; Francisco A. L. Costa (Tropical Animal Health and Production, 2014)

DNMT3B C46359T and SHMT1 C1420T polymorphisms in the folate pathway in carcinogenesis of head and neck - Maysa Succi; Tialfi Bergamin de Castro; Ana Lívia Silva Galbiatti; Lidia Maria Rebolho Batista Arantes; Jéssika Nunes Gomes da Silva; José Victor Maniglia; Luiz Sérgio Raposo; Érika Cristina Pavarino; Eny Maria Goloni-Bertollo (Molecular Biology Reports, 2014)

Isolation of key retinoid signalling and metabolic modules in invertebrates - André Ana; Castro L. Filipe; Ruivo Raquel; Santos Miguel (Frontiers in Marine Science, 2014)

Developing simple tools for transferring the biology to the management in small scale fisheries: the case of a sword razor clam fishery in Galicia - Hernández Otero Alba; Macho Gonzalo; Martinez Castro Cristina; Torres Machado Ana; Pérez Esther; Ferreiro Pedro; Gaspar Miguel; Vázquez Elsa (Frontiers in Marine Science, 2014)

In vitro antimicrobial activity of 20 selected climber species from the Bignoniaceae family - Carola Analía Torres; Iris Catiana Zampini; María Beatriz Nuñez; María Inés Isla; Marcela Paola Castro; Ana María Gonzalez (Natural Product Research, 2013)

Broad-scale cruciferous weed patch classification in winter wheat using QuickBird imagery for in-season site-specific control - Ana Isabel de Castro; Francisca López-Granados; Montserrat Jurado-Expósito (Precision Agriculture, 2013)

Reproductive strategy of the invasive Oxalis pes-caprae: distribution patterns of floral morphs, ploidy levels and sexual reproduction - Sílvia Castro; Victoria Ferrero; Joana Costa; Ana João Sousa; Mariana Castro; Luis Navarro; João Loureiro (Biological Invasions, 2013)

Reduced glutathione export during programmed cell death of Neurospora crassa - Andreia S. Fernandes; Ana Castro; Arnaldo Videira (Apoptosis, 2013)

One-Electron Reduction of 6-Hydroxydopamine Quinone is Essential in 6-Hydroxydopamine Neurotoxicity - Monica Villa; Patricia Muñoz; Ulises Ahumada-Castro; Irmgard Paris; Ana Jiménez; Isabel Martínez; Francisca Sevilla; Juan Segura-Aguilar (Neurotoxicity Research, 2013)

Flow cytometric and karyological analyses of Calendula species from Iberian Peninsula - Sofia Nora; Sílvia Castro; João Loureiro; Ana Carla Gonçalves; Helena Oliveira; Mariana Castro; Conceição Santos; Paulo Silveira (Plant Systematics and Evolution, 2013)

The dimensionality of ecological networks - Anna Eklöf; Ute Jacob; Jason Kopp; Jordi Bosch; Rocío Castro‐Urgal; Natacha P. Chacoff; Bo Dalsgaard; Claudio de Sassi; Mauro Galetti; Paulo R. Guimarães; Silvia Beatriz Lomáscolo; Ana M. Martín González; et al. (Ecology Letters, 2013)
How many dimensions (trait‐axes) are required to predict whether two species interact? This unanswered question originated with the idea of ecological niches, and yet bears relevance today for understanding what determines network structure. Here, we analyse a set of 200 ecological networks, including food webs, antagonistic and mutualistic networks, and find that the number of dimensions needed to completely explain all interactions is small (

Anti-inflammatory and Immunomodulatory Effect of an Extract of Coccidioides posadasii in Experimental Arthritis - Ana Carolina Matias Dinelly Pinto; Rossana de Aguiar Cordeiro; José Julio Costa Sidrim; Ana Karine Rocha de Melo Leite; Ana Caroline Rocha de Melo Leite; Virgínia Cláudia Carneiro Girão; Raimunda Sâmia Nogueira Brilhante; Marcos Fábio Gadelha Rocha; Fernando de Queiroz Cunha; Francisco Airton Castro Rocha (Mycopathologia, 2013)

Genetic control and mapping of Solanum chilense LA1932, LA1960 and LA1971-derived resistance to Tomato yellow leaf curl disease - Ana Pérez de Castro; Olga Julián; María José Díez (Euphytica, 2013)

Enantioselective HPLC analysis and biodegradation of atenolol, metoprolol and fluoxetine - Ana Rita Ribeiro; Carlos Magalhães Afonso; Paula M. L. Castro; Maria Elizabeth Tiritan (Environmental Chemistry Letters, 2013)

No association between catechol-o-methyltransferase Val108/158Met polymorphism and schizophrenia or its clinical symptomatology in a Mexican population - Carlos Tovilla-Zárate; Beatriz Camarena Medellín; Ana Fresán; Lilia López-Narváez; Thelma Beatriz Gonzalez Castro; Isela Juárez Rojop; Julián Ramírez-Bello; Alma Genis; Humberto Nicolini (Molecular Biology Reports, 2013)

Life-history responses of salinity-tolerant and salinity-sensitive lineages of a stenohaline cladoceran do not confirm clonal differentiation - Cláudia Loureiro; Bruno B. Castro; Ana P. Cuco; M. Arminda Pedrosa; Fernando Gonçalves (Hydrobiologia, 2013)

Biometrical, biological, biochemical and molecular characteristics of Meloidogyne incognita isolates and related species - Marcilene Fernandes Almeida dos Santos; Cleber Furlanetto; Maria Rita Alves Almeida; Marina Dechechi Gomes Carneiro; Fabiane Castro Mota; Ana Cristina Meneses Mendes Gomes; Natália Orrú Reis Silveira; Joelma Gardênia Pereira Silva; Philippe Castagnone-Sereno; Myrian Silvana Tigano; Regina Maria Dechechi Gomes Carneiro (European Journal of Plant Pathology, 2012)

Leaflet secretory structures of five taxa of the genus Zornia J.F. Gmel. (Leguminosae, Papilionoideae, Dalbergieae) and their systematic significance - Ana Paula Fortuna-Perez; Marilia de Moraes Castro; Ana Maria Goulart de Azevedo Tozzi (Plant Systematics and Evolution, 2012)

Antioxidant, cytotoxic and hemolytic effects of sulfated galactans from edible red alga Hypnea musciformis - Monique Gabriela das Chagas Faustino Alves; Celina Maria Pinto G. Dore; Allisson Jhonatan G. Castro; Marília Silva do Nascimento; Ana Katarina M. Cruz; Eliane M. Soriano; Norma M. Barros Benevides; Edda Lisboa Leite (Journal of Applied Phycology, 2012)

Chiral pharmaceuticals in the environment - Ana R. Ribeiro; Paula M. L. Castro; Maria E. Tiritan (Environmental Chemistry Letters, 2012)

Swim training does not protect mice from skeletal muscle oxidative damage following a maximum exercise test - Tatiane Oliveira Barreto; Lorena Sabino Cleto; Carolina Rosa Gioda; Renata Sabino Silva; Ana Carolina Campi-Azevedo; Junia de Sousa-Franco; José Carlos de Magalhães; Claudia Lopes Penaforte; Kelerson Mauro de Castro Pinto; Jader dos Santos Cruz; Etel Rocha-Vieira (European Journal of Applied Physiology, 2012)

Airborne multi-spectral imagery for mapping cruciferous weeds in cereal and legume crops - Ana Isabel de Castro; Montserrat Jurado-Expósito; José M. Peña-Barragán; Francisca López-Granados (Precision Agriculture, 2012)

Effect of hydropriming and acclimation treatments on Quercus rugosa acorns and seedlings - Libertad Castro-Colina; Miguel Martínez-Ramos; Maria Esther Sánchez-Coronado; Pilar Huante; Ana Mendoza; Alma Orozco-Segovia (European Journal of Forest Research, 2012)

New contributions to the study of common double mutants in the human LDL receptor gene - M. Teresa Tejedor; Ana Cenarro; Diego Tejedor; Marianne Stef; Lourdes Palacios; Isabel de Castro; Ángel L. García-Otín; Luis V. Monteagudo; Fernando Civeira; Miguel Pocovi (The Science of Nature, 2011)

Freezing solution containing dimethylsulfoxide and fetal calf serum maintains survival and ultrastructure of goat preantral follicles after cryopreservation and in vitro culture of ovarian tissue - Simone Vieira Castro; Adeline Andrade de Carvalho; Cleidson Manoel Gomes da Silva; Luciana Rocha Faustino; Cláudio Cabral Campello; Carolina Madeira Lucci; Sônia Nair Báo; José Ricardo de Figueiredo; Ana Paula Ribeiro Rodrigues (Cell and Tissue Research, 2011)

Heavy Metal Accumulation in Plant Species Indigenous to a Contaminated Portuguese Site: Prospects for Phytoremediation - Helena Moreira; Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Water, Air, & Soil Pollution, 2011)

Mass balance in the monitoring of pollutants in tidal rivers of the Guanabara Bay, Rio de Janeiro, Brazil - Raquel Pinhão da Silveira; Ana Paula de Castro Rodrigues; Ricardo Erthal Santelli; Renato Campello Cordeiro; Edison Dausacker Bidone (Environmental Monitoring and Assessment, 2011)

Chromosome polymorphism in Rineloricaria pentamaculata (Loricariidae, Siluriformes) of the Paraná River basin - Fernanda Errero Porto; Ana Luiza de Brito Portela-Castro; Isabel Cristina Martins-Santos (Ichthyological Research, 2011)

Phylotype diversity in a benthic cyanobacterial mat community on King George Island, maritime Antarctica - Cecilia Callejas; Paul R. Gill; Ana I. Catalán; Gastón Azziz; Susana Castro-Sowinski; Silvia Batista (World Journal of Microbiology and Biotechnology, 2011)

Evaluation of the Sub-lethal Toxicity of Bleached Kraft Pulp Mill Effluent to Carassius auratus and Dicentrarchus labrax - Mário S. Diniz; Ruth Pereira; Ana C. Freitas; Teresa A. P. Rocha-Santos; Luisa Castro; Isabel Peres; Armando C. Duarte (Water, Air, & Soil Pollution, 2011)

RETRACTED: Remediation of Heavy Metal Contaminated Soils: An Overview of Site Remediation Techniques - Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Critical Reviews in Environmental Science and Technology, 2011)

Relationship between Mercury Concentrations in the Blood with that in the Muscle of Four Estuarine Tropical Fish Species, Rio de Janeiro State, Brazil - Ana Paula de Castro Rodrigues; Patrícia Oliveira Maciel; Luiz César Cavalcanti Pereira da Silva; Nádia Regina Pereira Almosny; José Vanderli Andreata; Edison Dausacker Bidone; Zuleica Carmen Castilhos (Bulletin of Environmental Contamination and Toxicology, 2011)

The selective COX-2 inhibitor Etoricoxib reduces acute inflammatory markers in a model of neurogenic laryngitis but loses its efficacy with prolonged treatment - Manuel Lima-Rodrigues; Nuno Lamas; Ana Valle-Fernandes; Andrea Cruz; Artur Vieira; Pedro Oliveira; Jorge Pedrosa; António G. Castro; Rui M. Reis; Fátima Baltazar; Armando Almeida (Inflammation Research, 2010)

Nucleotide diversity of a ND5 fragment confirms that population expansion is the most suitable explanation for the mtDNA haplotype polymorphism of Drosophila subobscura - José A. Castro; Eladio Barrio; Ana González; Antònia Picornell; Maria Misericòrdia Ramon; Andrés Moya (Genetica, 2010)

Effects of tertiary treatment by fungi on organic compounds in a kraft pulp mill effluent - Teresa Rocha-Santos; Filipe Ferreira; Lurdes Silva; Ana Cristina Freitas; Ruth Pereira; Mário Diniz; Luísa Castro; Isabel Peres; Armando Costa Duarte (Environmental Science and Pollution Research, 2010)

Effect of age on cytokine response in an experimental model of osteomyelitis - Felícito García-Alvarez; Marta Navarro-Zorraquino; Angel Castro; José María Grasa; Cristina Pastor; Marta Monzón; Ana Martínez; Ignacio García-Alvarez; Javier Castillo; Ricardo Lozano (Biogerontology, 2009)

Haplotype and quantitative transcript analyses of Portuguese breast/ovarian cancer families with the BRCA1 R71G founder mutation of Galician origin - Catarina Santos; Ana Peixoto; Patrícia Rocha; Ana Vega; Maria José Soares; Nuno Cerveira; Susana Bizarro; Manuela Pinheiro; Deolinda Pereira; Helena Rodrigues; Fernando Castro; Rui Henrique; et al. (Familial Cancer, 2009)

Characterization of Desmodesmus pleiomorphus isolated from a heavy metal-contaminated site: biosorption of zinc - Cristina M. Monteiro; Ana P. G. C. Marques; Paula M. L. Castro; F. Xavier Malcata (Biodegradation, 2009)

Remediation of Heavy Metal Contaminated Soils: Phytoremediation as a Potentially Promising Clean-Up Technology - Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Critical Reviews in Environmental Science and Technology, 2009)

Toxicity evaluation of three pesticides on non-target aquatic and soil organisms: commercial formulation versus active ingredient - Joana L. Pereira; Sara C. Antunes; Bruno B. Castro; Catarina R. Marques; Ana M. M. Gonçalves; Fernando Gonçalves; Ruth Pereira (Ecotoxicology, 2009)

Histopathology findings in common marmosets (Callithrix jacchus Linnaeus, 1758) with chronic weight loss associated with bile tract obstruction by infestation with Platynosomum (Loos, 1907) - Maria Bernardete Cordeiro Sousa; Adriano Castro Leão; José Flávio Vidal Coutinho; Ana Maria de Oliveira Ramos (Primates, 2008)

Isozyme polymorphisms within Pyrenophora tritici-repentis population in Argentina - María Virginia Moreno; María S. Tacalitti; Ana M. Castro; Analía E. Perelló (World Journal of Microbiology and Biotechnology, 2008)

Occurrence of two cytotypes in Bryconamericus aff. iheringii (Characidae): karyotype analysis by C- and G-banding and replication bands - Ana Luiza de Brito Portela-Castro; Horácio Ferreira Julio; Isabel Cristina Martins dos Santos; Carla Simone Pavanelli (Genetica, 2008)

Identification of a CAPS marker tightly linked to the Tomato yellow leaf curl disease resistance gene Ty-1 in tomato - Ana Pérez de Castro; José Miguel Blanca; María José Díez; Fernando Nuez Viñals (European Journal of Plant Pathology, 2007)

Efficiency of endozoochorous seed dispersal in six dry-fruited species (Cistaceae): from seed ingestion to early seedling establishment - María E. Ramos; Ana B. Robles; Jorge Castro (Plant Ecology, 2006)

The behavior of the atmosphere in long-range transport - Roberto Fraile; Ana Isabel Calvo; Amaya Castro; Delia Fernández-González; Eduardo García-Ortega (Aerobiologia, 2006)

Interaction of stannous chloride leads to alteration in DNA, triphosphate nucleotides and isolated bases - José C. P. de Mattos; Claudia Lage; Flávio J. S. Dantas; Milton O. Moraes; Ana P. M. Nunes; Roberto J. A. C. Bezerra; Mauro V. Castro Faria; Alvaro C. Leitão; Adriano Caldeira-de-Araujo (Molecular and Cellular Biochemistry, 2005)

Preclinical pharmacology of F-98214-TA, a novel potent serotonin and norepinephrine uptake inhibitor with antidepressant and anxiolytic properties - Inés Artaiz; Arturo Zazpe; Ana Innerárity; Elena del Olmo; Alvaro Díaz; José Angel Ruiz-Ortega; Elena Castro; Ruth Pena; Luis Labeaga; Angel Pazos; Aurelio Orjales (Psychopharmacology, 2005)

Ancestral origins of the prion protein gene D178N mutation in the Basque Country - Ana B. Rodríguez-Martínez; Christian Barreau; Isabelle Coupry; Jordi Yagüe; Raquel Sánchez-Valle; Luis Galdós-Alcelay; Agustín Ibáñez; Antón Digón; Ignacio Fernández-Manchola; Cyril Goizet; Azucena Castro; Nerea Cuevas; et al. (Human Genetics, 2005)

A case of eumycetoma due to Madurella grisea in northern Brazil - Raquel Vilela; Olga M. V. Duarte; Carlos A. Rosa; Joao G. F. Castro; Sandra Lyon; Roberta L. Motta; Ana C. L. Moura (Mycopathologia, 2004)

Luis A. Carneiro - Rui Oliveira; David Gonçalves; Joana Jordão; Albert Ros; Katharina Hirschenhauser; Teresa Fagundes; Tânia Oliveira; Rui Andrade; João Saraiva; Ana Silva; Nídia Castro; Lúcia Costa (acta ethologica, 2003)

A general theory on fish aggregation to floating objects: An alternative to the meeting point hypothesis - José J. Castro; José A. Santiago; Ana T. Santana-Ortega (Reviews in Fish Biology and Fisheries, 2002)

New occurrence of microchromosomes B in Moenkhausia sanctaefilomenae (Pisces, Characidae) from the Paraná River of Brazil: analysis of the synaptonemal complex - Ana Luiza de Brito Portela-Castro; Horácio Ferreira Júlio Júnior; Patrícia Belini Nishiyama (Genetica, 2000)

Effect of zinc administration on thyrotropin releasing hormone-stimulated prolactinemia in healthy men - Ana Valéria B. Castro; Berenice B. Mendonça; Walter Bloise; Tadao Shuhama; José Brandão-Neto (BioMetals, 1999)

Interleukin-2 increases intracellular glutathione levels and reverses the growth inhibiting effects of cyclophosphamide on B16 melanoma cells - Teodoro Palomares; Ana Alonso-Varona; Antonia Alvarez; Begoña Castro; Yolanda Calle; Pedro Bilbao (Clinical & Experimental Metastasis, 1997)

Cholinesterase activities in developing amphibian embryos following exposure to the insecticides dieldrin and malathion - Monica C. de Llamas; Adriana C. de Castro; Ana M. Pechen de D'Angelo (Archives of Environmental Contamination and Toxicology, 1985)